Scenario discovery for a just low-carbon transition - Nicola Campigotto; Marco Catola; André Cieplinski; Simone D’Alessandro; Tiziano Distefano; Pietro Guarnieri; Till Heydenreich (Ecological Economics, 2026)

Comprehensive chemical and multivariate characterization of Amazonian guarana (Paullinia cupana) seed coats: Insights for sustainable valorization - Maria Paula Pimenta Vilas Boas; Simone de Nazaré Melo Ramos; Marcos Fellipe da Silva; Natalia Costa da Silva; Michel Rocha Baqueta; Joyce Grazielle Siqueira Stürmlinger; Tatiane Pereira de Souza; Helena Teixeira Godoy; Rosana Goldbek Coelho; Priscilla Efraim; Juliana Azevedo Lima Pallone (Food Research International, 2026)

Ecotoxicity and recovery of Poecilia reticulata exposed to cosmetic effluent, graphene oxide, iron oxide nanoparticles and magnetic graphene oxide - Walter de Souza Rodrigues; João Marcos de Lima Faria; Diego Stéfani Teodoro Martinez; Theodoro da Rosa Salles; Victoria Costa da Silva; Débora dos Santos Pereira; Ryan Marques Rezende; Ana Luiza Torres Soares; Isabela Cristina Louza Goulart; Jordana Duarte de Souza; Lucas Camilo Moraes Alves; Simone Maria Teixeira de Sabóia-Morais (Aquatic Toxicology, 2026)

Sustainable valorization of citrus pomace waste: biochar production and in vitro bioactivities - Cristina Spedale; Vincenzo Chiofalo; Matteo Dell’Anno; Sara Frazzini; Marco Puglia; Simone Pedrazzi; Alessandra Moscatelli; Elisabetta Onelli; Luciana Rossi (Veterinary Research Communications, 2026)

“Bad rebounds” and the circular economy: are plastic waste from bottled water and separated plastic collection complements or substitutes? - Alessio D'Amato; Marco De Simone; Ivano Dileo; Elisabetta Marzano (Sustainable Production and Consumption, 2026)

Impact of extreme flood on fecal and metal contamination in Lake Guaíba, southern Brazil - Juliana Schmitt de Nonohay; Simone Caterina Kapusta; Guilherme Gomes Ferrioli; Thaís Dalzochio; Roberta Plangg Riegel; Marco Antonio Siqueira Rodrigues; Luciano Basso da Silva (Limnologica, 2026)

Application of extracellular polymeric substances recovered from aerobic granular sludge as bio-based hydrogels for plant cultivation systems - Antonio Pescatore; Benedetta Pagliaccia; Tommaso Lotti; Claudio Lubello; Riccardo Campo; Simone Orlandini; Marco Napoli (Journal of Environmental Management, 2026)

Virome of neotropical Sabethes mosquitoes reveals two novel viruses in the Spiciviridae family - Endrya do Socorro Foro Ramos; Lilian de Oliveira Guimaraes; Geovani de Oliveira Ribeiro; Marcos Anicete Santos; Ramendra Pati Pandey; Simone Luchetta Reginato; Juliana Telles-de-Deus; Eduardo Sterlino Bergo; Luis Filipe Mucci; Vera Lucia Fonseca de Camargo-Neves; Antonio Charlys da Costa; Elcio Leal; et al. (Virus Genes, 2026)
The family Spiciviridae , belonging to the order Ghabrivirales , is currently composed of only one officially recognized genus, Spicivirus . However, metagenomic studies have revealed an increasing diversity of related viruses, suggesting that the current classification may underestimate their evolutionary complexity. In this context, the aim of the present study was to detect and characterize new viruses related to the Spiciviridae in the family Culicidae mosquitoes. A total of nineteen mosquito pools were sequenced and analyzed using metagenomic approaches and bioinformatics tools. Among these, two novel viruses were identified in four pools (S4, S11, S18, and S19), provisionally named Sabethes virus 1 (SV1) and Sabethes virus 2 (SV2). Phylogenetic inference revealed clades with strong statistical support and genetic divergences greater than 20% in the RNA-dependent RNA polymerase (RdRp) protein. These findings contribute to a detailed analysis of the genomic diversity associated with Spiciviridae . Although Spicivirus is currently the only genus officially recognized, our results suggest the presence of viruses that may represent new taxonomic groupings not yet described by the ICTV.

Wildfire ash impacts the early development of the sea urchin Paracentrotus lividus - Roberta Miroglio; Pietro Soro; Sara Ferrando; Giacomo Rosa; Michele Oneto; Paolo Bianchini; Marco Faimali; Simone Farina; Chiara Gambardella (Marine Environmental Research, 2026)

Organic matter, microplastics and macrofaunal communities associated with Posidonia oceanica meadows - Marco Martinez; Roberta Minetti; Emanuela Claudia La Marca; Valeria Montalto; Alessandro Rinaldi; Elisa Costa; Francesca Garaventa; Simone Mirto; Francesca Ape (Marine Environmental Research, 2026)

Integrated reverse osmosis and electrochemical oxidation for the removal of pharmaceuticals and antimicrobial-resistant bacteria from real hospital wastewater: efficiency, concentrate management, and environmental risk assessment - Diego U. Rizzana; Lucas Hansen; Tatiana K. Silva; Simone U. Picoli; Luciano B. da Silva; Marcos F. Debastiane; Rafael Liden; Andrea M. Bernardes; Louidi L. Albornoz; Salatiel W. da Silva; Alexandre Giacobbo; Marco A.S. Rodrigues (Journal of Environmental Chemical Engineering, 2026)

Mitigating traffic-related particulate matter with evergreen shrubs: A real-world field study in bergamo, Italy - Maria Luisa Feo; Gregorio Sgrigna; Marco Torre; Francesca Marcovecchio; Chiara Anselmi; Dania Valli; Mattia Perilli; Simone Serrecchia; Giulio Esposito; Emanuela Tempesta; Francesca Trapasso; Ettore Guerriero; et al. (Environmental Pollution, 2026)

Sliding joint masonry infill with deformable contact material: interaction with the RC frame and design guidelines - Simone Pelucco; Riccardo R. Milanesi; Paolo Morandi; Valentino Bolis; Andreas Stavridis; Guido Magenes; Marco Preti (Bulletin of Earthquake Engineering, 2026)
The seismic vulnerability of traditionally constructed masonry infilled frames has been repeatedly highlighted in post-event surveys, as well as by experimental and numerical studies. Infill walls with sliding joints can improve the seismic response of these structures. The paper describes some design equations derived from a parametric numerical analysis focusing on the interaction between the RC frame and the masonry infill with sliding joints. A previously proposed analytical model, able to predict the lateral strength contribution and the column shear overload due to the infill-frame interaction, is here extended to widen its field of application to walls with column-to-infill contact material characterized by and elastic response instead of an elastic-plastic one. A previously validated finite element modelling method is used to conduct a parametric study examining the role of the key design parameters of ductile masonry infill walls that implement sliding joints. The main model parameters are calibrated using data obtained from a previous comprehensive experimental campaign. A comparison of numerical and experimental results is also reported. The influence of different infill-frame contact material stiffnesses is analysed together with other design parameters, such as the bay length, the masonry properties, the layout of sliding and contact joints.

Forest structure and multi-taxonomic diversity in Apennine beech forests subjected to conservation-oriented interventions - Mirko Legnaro Diamanti; Giacomo Cangelmi; Luciano Ludovico Maria De Benedictis; Lorenzo Balducci; Renato Benesperi; Elisabetta Bianchi; Emanuela Carli; Andrea Ceci; Francesco Chianucci; Giampiero Ciaschetti; Leopoldo De Simone; Andrea De Toma; et al. (Plant Biosystems, 2026)

Mapping the advancements in floristic knowledge of Italy (2005–2025) - Gianniantonio Domina; Gianluigi Bacchetta; Fabrizio Bartolucci; Marco D’Antraccoli; Lorenzo Peruzzi; Adriano Stinca; Alessandro Alessandrini; Liliana Bernardo; Francesco Boscutti; Daniela Bouvet; Maurizio Bovio; Giacomo Calvia; et al. (Plant Biosystems, 2026)
Based on the evaluation of 3,902 local floristic references published between 2005 and 2025, an update to the floristic knowledge map of Italy is presented. To measure the progress in floristic knowledge across Italy’s administrative regions, the ‘Index of Floristic Knowledge Advancement’ (IFA) is proposed here. This index categorizes regions based on the proportion of potential improvement that has actually been achieved. Results showed an improvement in knowledge, most notably for Northern and Central Italy. Emilia-Romagna emerged as the most comprehensively documented region with the highest IFA value (0.81), followed by Lombardia (0.60), Friuli-Venezia Giulia (0.54), Trentino-Alto Adige and Veneto (0.53). In central Italy, Lazio (0.50), Sardegna (0.45) and Toscana (0.36) registered the highest scores. Over the past twenty years, 453 specific and subspecific taxa have been described from the Italian territory, the majority of which (443) are Italian endemics. Hieracium is the most represented genus (147 taxa). The marked progress documented is likely due to the accelerated impact of coordinated scientific projects, citizen science programs, the development of digital databases, and an increased focus on taxonomic research.

The Biodiversity of Retreating Glaciers Leaves an Ecological Legacy in Emerging Soil Communities - Isabel Cantera; Silvio Marta; Alexis Carteron; Alessia Guerrieri; Simone Giachello; Aurélie Bonin; Roberto Ambrosini; Roberto Sergio Azzoni; Marco Caccianiga; Francesca Pittino; Andrea Simonicini; Barbara Valle; et al. (Global Change Biology, 2026)
Glacier retreat is transforming high‐mountain and polar landscapes, replacing ice with vast, newly exposed terrains where soil development and ecological succession start. Although ecosystems developing in deglaciated terrains are often viewed as starting from scratch, glaciers host diverse communities whose links with emerging soils remain unquantified. Using environmental DNA metabarcoding, we provide the first multi‐taxa assessment of biodiversity transitions across the supraglacial–proglacial interface across five glacier systems in Svalbard, the Alps and Patagonia. We analysed 212 samples from the surfaces of retreating glaciers and their forelands, spanning a chronosequence from 1 to 483 years since deglaciation. Recently deglaciated soils (≤ 10 years since glacier retreat) showed taxonomic and functional similarity to supraglacial communities. This ecological continuity was highly taxon‐specific, being pronounced for communities of microorganisms (Bacteria, Fungi, Protista) but weak for animals (e.g., Collembola, Insecta). For microbes, similarity diminished rapidly over succession as community turnover increased, and functional composition shifted from phototrophic and saprotrophic dominance toward heterotrophic and symbiotic assemblages. Shared microbial taxa and functions indicate a transient glacial influence during early soil succession. Our results suggest that early soil communities are not assembled independently of glacier ecosystems, but are initially linked to them through diverse ecological pathways that diminish over time. The observed glacier–proglacial connectivity challenges the view of succession on deglaciated terrains as beginning on lifeless substrates and instead points to a glacial legacy in emerging soils. As glaciers rapidly disappear under climate change, the unique biodiversity they host is also being lost, underscoring the urgent need to study supraglacial and proglacial systems together. Such integration is essential to understand ecological succession in proglacial ecosystems, which are expected to play an increasingly important role in this century.

Silica nanoparticles alter cadmium partitioning and physiological responses within the substrate–plant system of soybean - Jaqueline da Silva Santos; Salete Aparecida Gaziola; Marco Aurélio Zezzi Arruda; Lilian Seiko Kato; Montcharles da Silva Pontes; Gilberto José de Arruda; Simone Yasuda Fernandes; Ricardo Antunes Azevedo (Plant and Soil, 2026)
Background and aims Cadmium (Cd) is a toxic and bioaccumulative element introduced into agricultural systems through phosphate fertilizers, anthropogenic inputs, and accidental contamination, thereby endangering crop productivity and food safety. Its high mobility in soil also raises concerns regarding environmental dispersal and ecological exposure. Silica nanoparticles (SiO₂ NPs) have been proposed as mitigators of metal-induced stress, yet their effects in soybean remain unclear. We tested whether substrate-applied SiO₂ NPs (400 mg·kg⁻ 1 ) could alleviate Cd toxicity across concentrations ranging from environmentally relevant to severely contaminated levels (0, 8, 16, and 64 mg·kg⁻ 1 ). Methods Non-transgenic (NTS) and transgenic (TS) soybean genotypes were evaluated through integrated morphological, physiological, biochemical, and substrate analyses. Results SiO₂ NPs increased Cd concentrations in the extractable fraction of the substrate (45.1% → 54.8% at 8 mg·kg⁻ 1 Cd), reduced root-to-shoot translocation by > 50% in TS, and reduced the apparent difference between the applied Cd dose and the summed concentrations across compartments (Δ Cd; ~ 44.6% → ~ 33.9%), consistent with changes in Cd partitioning within the substrate–plant system. In soybean, SiO₂ NPs modulated Cd stress responses in a dose-, parameter-, and occasionally genotype-dependent manner, with stronger mitigation at 8–16 mg·kg⁻ 1 Cd. In NTS, SiO₂ NPs reduced Cd-induced increases in pigment levels, whereas in TS, they more consistently attenuated antioxidant enzyme responses (SOD, GSH-Px, GPx). Conclusion Overall, SiO₂ NPs increased the extractable Cd fraction in the substrate and reduced Cd accumulation in roots and leaves. These findings highlight the potential role of SiO₂ NPs in modulating Cd dynamics in contaminated agricultural systems, with potential implications for food safety.

Biodegradable and conventional microplastics differentially affect soil nutrient availability and stress responses in spinach (Spinacia oleracea L.) - Giorgia Santini; Lucia Santorufo; Giulia Costanzo; Carmen Arena; Simone Landi; Sergio Esposito; Gabriella Di Natale; Marco Trifuoggi; Giulia Maisto (Applied Soil Ecology, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Seismic design approach for reinforced concrete frames infilled with sliding joint ductile infills - Simone Pelucco; Van Sang Doan; Marco Preti (Bulletin of Earthquake Engineering, 2026)
This study investigates the seismic performance of reinforced concrete (RC) frames infilled with deformable masonry panels that include horizontal sliding joints. These innovative infill systems are designed to mitigate the seismic deficiencies commonly observed in conventional RC buildings with rigid infills, where the strong interaction between the frame and the infill often causes brittle and undesirable failures. The study analyses the response of three RC structural frames with three, five, and seven storeys, by varying the infill properties and the design ductility classes, to evaluate how these parameters influence the overall seismic response. A further case study is introduced to reflect the common practice of including an opening, such as a door or window, in the masonry infill, leading to a reduced infill stiffness. The structural performance is assessed through linear, non-linear static, and non-linear dynamic time-history analyses, considering different seismic performance limit states. Particular attention is given to ductility verification, collapse mechanisms, and the evaluation of the behaviour factor capacity. Comparative results demonstrate that deformable infills incorporating sliding joints can effectively enhance structural performance and energy dissipation under seismic loading. The findings support their possible integration into performance-based seismic design methodologies and confirm that simplified analyses, such as response spectrum and pushover analyses, can provide reliable estimates of seismic demand when such ductile infill contributions are properly accounted for.

A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

A dataset of plant communities invaded by Acacia sp. pl. and Robinia pseudoacacia in Italy - Eugenia Siccardi; Alice Misuri; Alicia Teresa Rosario Acosta; Claudia Angiolini; Dario Azzaro; Gianluigi Bacchetta; Simonetta Bagella; Elena Barni; Giuseppe Bazan; Maria E. Boi; Gianmaria Bonari; Giuseppe Brundu; et al. (Plant Biosystems, 2026)
The full extent of the ecological threat posed by non-native invasive leguminous N-fixing trees to Italian ecosystems has not been thoroughly documented at the national level. This study, conducted by the Working Group on Alien Species of the Italian Botanical Society, aims to develop a comprehensive dataset that provides information on invaded and non-invaded areas, supporting multi-scale ecological analyses on the impact of black locust ( Robinia pseudoacacia ) and different Acacia sensu lato species across Italy. We conducted paired vegetation surveys across 18 distinct invasion contexts, comparing invaded and non-invaded plant communities. These invasion contexts were selected opportunistically by the participating research groups, based on the availability of well-documented sites where the focal species were already established and exerting ecologically relevant effects. Overall, we conducted 342 vegetation surveys across 10 Italian administrative regions and identified 824 plant species. Our surveys highlighted areas affected by five invasive species, including A. dealbata, A. mearnsii, A. saligna , Vachellia karroo , and R. pseudoacacia . Most of the surveys focused on areas invaded by A. saligna . The plant formations investigated fall under 23 EUNIS habitat codes and 10 Natura 2000 habitats. The most frequently occurring vegetation types under the EUNIS code are temperate and Mediterranean-montane scrub, and the most frequently investigated habitat is priority habitat 2250*: Coastal dunes with Juniperus sp. pl. This dataset provides a robust baseline that can facilitate more detailed assessments of the impacts of these invasive species on native ecosystems.

Holistic approach to restore marine ecosystems: RENOVATE project - Marco Marcelli; Sergio Scanu; Daniele Piazzolla; Simone Bonamano; Alice Madonia; Giorgio Fersini; Viviana Piermattei; Mar Bosch-Belmar; Francesco Paolo Mancuso; Giulia Ceccherelli; Annalisa Falace; Paola Del Negro; et al. (Frontiers in Marine Science, 2026)
Mediterranean coastal ecosystems are increasingly threatened by multiple anthropogenic pressures and climate change. As a result, these impacts have caused the decline of key endemic habitats such as Posidonia oceanica meadows and coralligenous reefs. Due to the slow natural recovery of these habitats after degradation, restoration actions play a key role in accelerating ecosystem recovery, reestablishing ecological structure and functional processes, and preventing further biodiversity and ecosystem service loss. Given the frequent habitat fragmentation and high levels of endemism, effective restoration efforts require a multidisciplinary, ecosystem-based approach that integrates marine science, engineering, socioeconomics, and policy. This study describes the holistic approach adopted in the RENOVATE project, which established an integrated framework to address the combined impacts of climate change and human pressures on vulnerable ecosystems. The framework employs advanced observational technologies, field data, and numerical modeling within an adaptive management loop, enabling site-specific, evidence-based restoration planning and assessment of ecosystem services recovery. Additionally, the study reports results from the northern Tyrrhenian coast (Latium, Italy), where RENOVATE aims to protect EU priority habitats and species from human pressures and climate-related threats. Although project activities are still in early stages, results from active restoration in the northern Latium coast show initial establishment and survival at pilot sites, highlighting the framework’s potential to guide effective, replicable interventions in coastal ecosystems. Beyond the regional case study, the proposed framework contributes to global marine restoration efforts by providing a transferable methodology for the management of coastal ecosystems.

Abnormal periodic and aperiodic resting-state electroencephalographic markers in Lewy body and Alzheimer’s diseases with cognitive decline - Matteo Carpi; Antonio Pio Afragola; Mina De Bartolo; Susanna Lopez; Burcu Bölükbaş; Claudio Del Percio; Veronica Henao Isaza; Roberta Lizio; Giuseppe Noce; Lorenc Barjami; Filippo Carducci; Andrea Soricelli; et al. (GeroScience, 2026)
Lewy body disease (LBD) and Alzheimer’s disease (AD) are the most common causes of cognitive decline and dementia and are associated with characteristic alterations in resting-state electroencephalographic (rsEEG) activity. This multicenter exploratory study investigated periodic and aperiodic rsEEG features in patients with cognitive decline due to Lewy body disease (LBCD) and Alzheimer’s disease (ADCD), compared with cognitively unimpaired older adults (Nold), and examined the clinical relevance of these markers in LBCD. A total of 140 LBCD, 135 ADCD, and 118 Nold datasets from the PDWAVES archive underwent spectral parameterization to decompose rsEEG power spectra (1–30 Hz) into periodic peaks and aperiodic background activity. Both clinical groups showed a significant slowing of the individual alpha frequency (IAF), more pronounced in LBCD, along with reduced periodic alpha and beta power reflected in a lower vigilance index. The aperiodic exponent was elevated in both groups, and the aperiodic offset was also higher in LBCD, suggesting steeper spectral profiles consistent with increased inhibitory cortical tone. Within the LBCD group, poorer cognition was associated with higher low-frequency alpha power, whereas better cognition was predicted by higher high-frequency alpha power. A reduced vigilance index was associated with the presence of visual hallucinations, while no associations emerged for other symptoms. These findings suggest that combined periodic and aperiodic rsEEG features may provide relevant markers of altered vigilance regulation in LBCD. Future studies should evaluate whether these EEG markers can inform targeted interventions, such as neuromodulatory or audiovisual stimulation, to stabilize quiet-vigilance states and improve clinical outcomes. Graphical abstract Panel A shows the spectral parameterization of rsEEG activity into periodic and aperiodic components. Panel B summarizes the main group differences in key rsEEG markers across LBCD, ADCD, and Nold participants. Panel C shows the topographical associations between the vigilance index and cognition and visual hallucinations in LBCD; colors reflect the direction and strength of the associations. For the visual hallucinations map, negative log-odds indicate lower odds of hallucinations for higher vigilance index values, whereas positive log-odds indicate higher odds; values around ± 1.5 correspond approximately to odds ratios of 0.22 and 4.5, respectively. Abbreviations: rsEEG, resting-state electroencephalography; LBCD, cognitive decline due to Lewy body disease; ADCD, cognitive decline due to Alzheimer’s disease; Nold, cognitively unimpaired older adults; IAF, individual alpha frequency; MMSE, Mini-Mental State Examination; p , standardized regression coefficient; log-odds, logistic regression coefficient.

Simulations of Wave–Structure Interactions in Incompressible SPH Using Modified Dynamic Boundary Conditions - Marco Simone; Giovanni Cannata; Georgios Fourtakas (Journal of Marine Science and Engineering, 2026)
The simulation of free-surface flows in hydraulic engineering presents several challenges due to the intrinsic complexity of modeling a fluid that continuously deforms and evolves over time. In this context, the Smoothed Particle Hydrodynamics (SPH) method, a Lagrangian approach that represents the fluid as a set of moving particles, is better suited than traditional grid-based methods. However, compared to the latter, the SPH method also exhibits certain drawbacks, including increased difficulty in handling wall boundary conditions and a higher computational cost. This work proposes an original wall boundary treatment technique that, to the best of our knowledge, is applied in the Incompressible SPH (ISPH) approach for the first time. The proposed treatment relies on boundary particles external to the fluid and internal extrapolation points, where pressure is computed to enforce Neumann boundary conditions in a consistent manner. During the development of this technique, several intrinsic advantages over existing methods in the literature are identified. A series of numerical benchmarks are conducted to verify the validity of the proposed ISPH model. Numerical results show good agreement with experimental data reported in the literature, confirming the effectiveness of the proposed numerical model in reproducing free-surface flow hydraulic phenomena.

The adipokinetic hormones of stored product pest insects: can this help to combat these insects? - Heather G. Marco; Simone König; Gerd Gäde (Journal of Stored Products Research, 2026)

Development of a multi-channel diffusive sampling system for the analysis of Semi-Volatile Organic Compounds in the vapor phase using TD-GC/MS - Flaminia Fois; Simone Serrecchia; Marco Torre; Patrizio Tratzi; Elisabetta Santarelli; Benedetta Giannelli Moneta; Massimiliano Frattoni; Valerio Paolini; Ettore Guerriero (Analytica Chimica Acta, 2026)

Magnetic resonance-guided stereotactic body radiotherapy (MRIgSBRT) for nodal disease in oligometastatic setting: a single-institution study - Giuditta Chiloiro; Giulia Panza; Angela Romano; Rosa Autorino; Ciro Mazzarella; Gabriele Turco; Marco Valerio Antonelli; Matteo Nardini; Simone Raggio; Lorenzo Placidi; Maria Antonietta Gambacorta; Luca Boldrini (Clinical & Experimental Metastasis, 2026)

Habitat suitability model for predicting the occurrence of scleractinian cold-water corals in the Gulf of Naples (Tyrrhenian Sea): A tool for restoration planning and governance of deep-sea ecosystems - Fabio Di Giovanna; Giorgio Castellan; Michela Angiolillo; Vincenzo Botte; Simonetta Fraschetti; Valentina Grande; Daniele Iudicone; Florian Kokoszka; Paolo Montagna; Mariacristina Prampolini; Giorgio Simone; Marco Taviani; et al. (Marine Environmental Research, 2026)

Modular building system with rocking cross-laminated timber panels for reusable construction: Experimental seismic assessment - Stylianos Kallioras; Marco Lamperti Tornaghi; Dionysios Bournas; Simone Peloso; Francisco Javier Molina (Engineering Structures, 2026)

Comparing traditional vs. environmental DNA monitoring protocols. The case of the Eurasian otter (Lutra lutra) re-expansion in Central Italy - Simone Giovacchini; Enrico Mirone; Pushpinder Singh Jamwal; Pamela Monaco; Fausto Ramazzotti; Emiliano Pioltelli; Andrea Galimberti; Antonia Bruno; Francesco Belluardo; Antonio Canu; Marco Galaverni; Mirko Di Febbraro; et al. (European Journal of Wildlife Research, 2026)
Once widespread in Italy, in the last century the Eurasian otter ( Lutra lutra ) went to the brink of extinction in this country, only surviving in a few southern river basins. Being included in the Habitats Directive 92/43/EEC, it is mandatory for State Members to monitor its conservation status over time, making cost effective and accurate monitoring protocols a relevant issue. We compared the efficiency of environmental DNA (eDNA) and traditional field survey techniques in detecting the presence of Eurasian otter at the border of the current expansion range of the Eurasian otter in Latium, Central Italy. Water sampling for eDNA detection through species-specific assay and systematic field surveys were run in six river basins. Results from the two approaches were compared at the scale of sampling site, 5 km and 10 km radius upstream. Both techniques agreed in revealing the expansion of Eurasian otter in southern Latium and in confirming otter absence in the northern part of the study area. eDNA allowed to detect otters at two more river catchments compared to field surveys, one of which is located northward in a tributary of the river Tiber, and showed a higher detection rate (0.41), both at sampling site (0.06, p = 0.01), 5 km (0.23) or 10 km radius (0.35) scale. These results suggest that eDNA is a more sensitive method in revealing Eurasian otter presence, providing a useful reference for future standardized monitoring of the species at the country level, especially in expansion areas.

The Italian effort toward a coordinated observation of Essential Variables (EOV, ECV, EBV) in European Marine Environments. Long-term observation in the central Mediterranean seas and Italian coasts - Simone Toller; Emilio Urbinati; Debora Bellafiore; Caterina Bergami; Francesca De Pascalis; Marcello G. Magaldi; Marco Bellacicco; Federico Bellati; Maristella Berta; Angelo Boccacci; Roberto Bozzano; Fabio Brunetti; et al. (Frontiers in Marine Science, 2026)
Monitoring Essential Ocean, Climate, and Biodiversity Variables (EOVs, ECVs and EBVs) collected through the marine Research Infrastructures (RIs) is critical for assessing environmental status, improving scientific knowledge and defining environmental policies. This study evaluates the capacity of the Italian marine monitoring system, including facilities such as fixed stations, buoys, autonomous platforms, and mobile systems across the Mediterranean Sea, to produce those variables. Conducted in 2023 within the framework of the ITINERIS project ( https://itineris.cnr.it/ ), which aims to strengthen coordination among national and ESFRI RIs (European Strategy Forum on Research Infrastructures), the analysis systematically examines the spatial, thematic, and technological coverage of EOVs, ECVs, EBVs observations and their alignment with international standards for environmental monitoring of 155 facilities from eight Italian and pan-European marine RIs. Of the 107 EVs recognized, 50% were actively produced by the RIs considered, with over 90% meeting the established requirements for EVs. These numbers will be updated to reflect the new equipment acquired during the project’s implementation up to early 2026, which is expected to boost EVs production by approximately 38-40%. The national monitoring network demonstrates a high degree of maturity for oceanic and climate variables, while biodiversity observations remain less represented, indicating the need for further technological innovation and automation. These findings emphasize the importance of enhancing coordination and harmonization among RIs to ensure balanced and interoperable monitoring. The study provides key recommendations to strengthen Italy’s capacity to contribute to the global characterization of EOVs, ECVs, and EBVs and to support evidence-based environmental assessments and the development of robust environmental management strategies at European level.

Perfluoroalkyl substances (PFASs) and brominated flame retardants (BFRs) in wildlife of the central apennine mountains, Italy: Assessment of background contamination - Arianna Stramenga; Tamara Tavoloni; Ester Lucidi; Francesco Griffoni; Martina Ciriaci; Marco Gobbi; Alice Ranucci; Melania Siracusa; Simone Bacchiocchi; Arianna Piersanti (Chemosphere, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Effective remediation of refractory tank-washing wastewaters by combined anodic oxidation and biotreatment - Emanuele Oddo; Simone Gelosa; Luca Magagnin; Marco Derudi (Journal of Water Process Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Switching between ordinary and non-ordinary activity at Stromboli volcano: insights from short- and long-term thermal trends recorded from space - Marco Laiolo; Diego Coppola; Simone Aveni; Adele Campus; Francesco Massimetti; Alessandro Aiuppa; Lorenzo Innocenti; Giorgio Lacanna; Giovanni Lo Bue Trisciuzzi; Marco Pistolesi; Maurizio Ripepe; Marija Voloschina (Bulletin of Volcanology, 2026)
Ordinary, moderately explosive activity at Stromboli is sporadically interrupted by larger effusive and explosive events that can trigger hazardous phenomena such as sector collapses, tsunamis, and ballistic fallout. We analyze 25 years of satellite infrared data to characterize the thermal pattern associated with these larger events, including: (1) effusive eruptions, (2) lava overflows, (3) major explosions, and (4) paroxysms. Increased heat flux precedes effusive eruptions and overflow sequences, and is interpreted to reflect the progressive rise of the magma column in the conduit accompanying the transition between Strombolian and effusive regimes. Conversely, major explosions are not preceded by any detectable thermal increase, although they statistically occur during periods of frequent overflows in which the Volcanic Radiative Power (VRP) is punctuated by higher values. Paroxysms (which occurred at the beginning, during and at the end of the effusive eruptions) do not show systematic thermal patterns in the preceding days, but in most cases are followed by a VRP increase. Major explosions and paroxysmal events contribute minimally to the long-term energy released by the volcano. Instead, the energy output is primarily governed by the recurrent transitions between Strombolian- and effusive-dominated regimes, sustaining a long-term, steady-state VRP of approximately 14.5 MW. Overall, only ~ 25% of the thermal energy is radiated during Strombolian activity, whereas overflows and effusions account for ~ 15% and ~ 60%, respectively. Results highlight that satellite thermal analysis is a useful tool for tracking changes of surface activity at open-vent basaltic volcanoes with frequent switching from ordinary low-energy activity to more energetic explosive or effusive eruptions.

Numerical and experimental assessment of the seismic vulnerability of an existing bridge in presence of carbonation-induced corrosion - Simone Reale; Marco Furinghetti; Alberto Pavese (Soil Dynamics and Earthquake Engineering, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Polystyrene microplastics modulate the toxic effects of bisphenol A in the early stages of zebrafish development - Alessandra La Pietra; Teresa Mobilio; Gianluca Fasciolo; Simone Moggio; Angela Belletti; Gabriella Di Natale; Marco Trifuoggi; Paola Venditti; Ida Ferrandino (Environmental Toxicology and Pharmacology, 2026)

P and S wave finite-frequency tomography reveals the impact of slab interference on mantle flow beneath the greater Alpine region - Yuantong Mao; Xiaotian Tang; Liang Zhao; Marco G. Malusà; Stéphane Guillot; Anne Paul; Stefano Solarino; Xiaobing Xu; Coralie Aubert; Elena Eva; Silvia Pondrelli; Simone Salimbeni; et al. (Earth and Planetary Science Letters, 2026)

Potent carbonic anhydrase inhibition by ruthenium(II)-acetazolamide conjugates uncoupled from antiproliferative activity in vitro - Alberto Gobbo; Simone Giovannuzzi; Maria Luisa Massardi; Marta Turati; Lorenzo Biancalana; Stefano Zacchini; Marco Bortoluzzi; Claudiu T. Supuran; Fabio Marchetti (Chemico-Biological Interactions, 2026)

Application of computer vision for automated detection of different lesions in pig lungs: An exploratory study - Matteo Recchia; Lucia Scuri; Camilla Allegri; Claudia Romeo; Federico Scali; Antonio Marco Maisano; Giovanni Santucci; Giorgio Bontempi; Simone Canesi; Laura Sala; Camilla Recordati; Eugenio Scanziani; et al. (Preventive Veterinary Medicine, 2025)

Road mortality risk of a protected felid across fragmented and heterogeneous landscapes in Central Europe - Matteo Luca Bastianelli; Johanna Heeres; Malte Götz; Saskia Jerosch; Olaf Simon; Johannes Lang; Teresa Nava; Sabrina Streif; Christine Thiel-Bender; Tomma Lilli Middelhoff; Ole Anders; Sönke Twietmeyer; et al. (Journal of Environmental Management, 2025)

The cognitive-emotional dynamics of organic versus traditional wines: A comparative study - Marco Tommasi; Simone Arnò; Chiara di Marcantonio; Laura Picconi; Maria Rita Sergi; Aristide Saggino (International Journal of Gastronomy and Food Science, 2025)

Fuel consumption of diesel, natural gas, hybrid, full electric and hydrogen fuel cells based buses: A simulated comparison using standard road cycles and gradeability tests - Ahmet Fatih Kaya; Marco Puglia; Nicolò Morselli; Giulio Allesina; Simone Pedrazzi (Fuel, 2025)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Unveiling the impact of tillage radish on soil chemical, biological, and physical soil properties under reduced and conventional tillage - Antonio Pescatore; Antonio Delgado; Simone Orlandini; Marco Napoli (Soil and Tillage Research, 2025)

Drivers of vascular species diversity on floodplain poplar stands: An integrated approach for ecological and functional assessment - Anna Corli; Francesca Vannucchi; Silvia Traversari; Simone Orsenigo; Alessio Giovannelli; Pier Mario Chiarabaglio; Francesco Chianucci; Carlo Calfapietra; Andrea Scartazza; Marco Carlo Mascherpa; Maria Laura Traversi; Luca Cristaldi; et al. (Forest Ecology and Management, 2025)

Assessing the efficiency of the irrigation system in a horticulture field through time-lapse electrical resistivity tomography - Agnese Innocenti; Veronica Pazzi; Marco Napoli; Riccardo Fanti; Simone Orlandini (Irrigation Science, 2025)
The characterization by means of geophysical techniques of agricultural soils subjected to continuous irrigation cycles makes it possible to study the heterogeneity of a soil and the preferential pathways of water flows without disturbing soil and plants. A better knowledge of soil heterogeneity enables optimal water resource management in terms of crop, yield, and sustainability. In this study, time-lapse monitoring using electrical resistivity tomographies (ERT) is proposed as a reliable and non-invasive technique to quantify the movement of water flows and thus the variation of soil water content during the irrigation process. ERT surveys have been conducted in melon-growing soils in southern Tuscany (Italy). Five survey campaigns have been carried out between June and August 2022, in which ERT data have been collected by taking measurements before ( T 0 ), during ( T 1 ), and after ( T 2 ) the irrigation phase. The interpretation of the ERT results provided information on the spatial and temporal distribution of water fluxes in the soil and root zone of melons during the irrigation phases. The investigation made it possible to identify the preferential pathways of infiltration of irrigation water, the points where water is absorbed by the roots, and the points where water follows a preferential pathway instead distributing itself entirely below the root growth zone. Thus, this research suggests that the ERT technique can be used to evaluate the efficiency of the irrigation system in order to achieve optimal management of the water resource, avoiding preferential flow paths that lead to less water availability for the plant.

Iron oxide nanoparticles (γ-Fe2O3) combined with microcystin-LR induce severe histopathological damage with potential for recovery in the intestinal tissue of Poecilia reticulata - Lucas Camilo Moraes Alves; João Marcos de Lima-Faria; Milena Lima Brito; Jascieli Carla Bortolini; Bruno Oliveira Silva Duran; Simone Maria Teixeira de Sabóia-Morais (Ecotoxicology, 2025)

Coffee and tea intake and survival of cancer patients: a systematic review and meta-analysis - Marco Romelli; Patrizia Gnagnarella; Aurora Gaeta; Davide Serrano; Ilaria Ermini; Nora de’ Bonfioli Cavalcabo’; Calogero Saieva; Simone Iadevaia; Sara Gandini; Saverio Caini (Cancer Causes & Control, 2025)

Grazing halos reveal differential ecosystem vulnerabilities in vegetated habitats - Mario Minguito‐Frutos; Rohan Arthur; Jordi Boada; Candela Marco‐Méndez; Matthew P. Adams; Jordi F. Pagès; Xavier Buñuel; Albert Pessarrodona; Xavier Turon; Enric Ballesteros; Laura Tamburello; Simone Farina; et al. (Ecology, 2025)
The dynamic balance between primary production and herbivory is key to the resilience of plant‐dominated ecosystems across the world. However, many vegetated ecosystems are becoming increasingly susceptible to herbivore‐triggered collapses, as this balance is disrupted due to predator declines, increasing nutrients, and other interacting impacts of global change. Yet without accessible, cost‐effective tools to evaluate the production‐consumption relationship, it is difficult to know how close an ecosystem is to imminent overgrazing collapse. Here, we explore the effectiveness of individually formed sea urchin grazing halos as robust indicators of marine habitat vulnerability to overgrazing. Halos are grazed patches of bare rock on macrophyte‐dominated substrates that represent the balance between macrophyte production and per capita herbivore consumption. We measured 1211 halos in 31 locations across the Mediterranean Sea to characterize how plant‐herbivore interactions are mediated by endogenous (i.e., species identity, habitat type, and sea urchin size) and exogenous factors (i.e., environmental factors influencing biotic and abiotic contexts: depth, nutrients, temperature, or protection level). Our results show that halo size was effective in detecting differences in the effect of endogenous and exogenous factors on these interactions. Across locations, halo size was sensitive to differences in (i) species identity, with some species being more impactful than others; (ii) the type of habitat, with some habitats being more vulnerable than others; (iii) protection level, with halo size consistently lower inside marine protected areas; (iv) urchin size, with halo size increasing consistently with herbivore size; (v) nutrient conditions, with halo size increasing as nutrient availability decreased; as well as (vi) depth, with halo size increasing consistently with depth. These results indicate that overgrazing vulnerability is highly contingent on local ecological contexts, which strongly mediate plant‐herbivore interactions. While drivers of ecosystem collapse may be global, the ability of ecosystems to cope is often inherently local. We need locally responsive measures and contextually meaningful solutions to manage ecological integrity in the face of global change. In this context, individually measured grazing halos can be a powerful tool in assessing and managing the resilience of macrophyte ecosystems.

Surface-water-irrigation return flow dominates groundwater recharge, groundwater age and nitrate dynamics in an alluvial basin aquifer - Mariachiara Caschetto; Elisa Sacchi; Daniele L. Pinti; Carlo Riparbelli; Simone Bruno; Chiara Zanotti; Tullia Bonomi; Marco Rotiroti (Water Research, 2025)

Coalification patterns and thermal-depositional history of the Upper Cretaceous-Paleogene coal in the Eastern Cordillera Basin, Colombian Andes - Juan Sebastian Gomez-Neita; Ana Maria Pimentel Mizusaki; Taís Freitas da Silva; Sandra Rocio Manosalva-Sánchez; Jorge Eliecer Mariño-Martínez; César Augusto Mora-Hernández; Gleubis Belén Silveira-Moreno; Mauricio Alberto Bermúdez-Cella; Lady Alejandra Barrera-Chaparro; Marcos Müller Bicca; Simone Patricia Aranha da Paz (Marine and Petroleum Geology, 2025)

A multidimensional analytical framework for the selection of soft wheat varieties for dryland environments based on agronomic productivity, stability, nitrogen use efficiency and economic parameters - Qudratullah Soofizada; Antonio Pescatore; Simone Orlandini; Marco Napoli (European Journal of Agronomy, 2025)

Integrating ethical assessment and media content analysis to explore social conflicts over large carnivores - Simone Basile; Elena Mercugliano; Sally Carraro; Pierfrancesco Biasetti; Giulia Mascarello; Anna Pinto; Marco Zago; Veronica Nanni; Steven Seet; Roberto Guadagnini; Barbara de Mori (Biological Conservation, 2025)

Iron, manganese, and copper complexes protect saccharomyces cerevisiae from methyl methanesulfonate-induced genotoxicity and oxidative stress - Larissa M. M. Mattos; Davi A. Andrade; Alan N. S. Alves; Victória T. Ferreira; Simone S. C. Oliveira; Bruna B. Segat; André L. S. Santos; Adolfo Horn; Christiane Fernandes; Marcos D. Pereira (World Journal of Microbiology and Biotechnology, 2025)

Development, growth, and flower production of cut sunflower under tropical, subtropical, and temperate environments - Regina Tomiozzo; Lilian Osmari Uhlmann; Leosane Cristina Bosco; Márkilla Zunete Beckmann-Cavalcante; Petterson Baptista da Luz; José Carlos Sorgato; Simone Novaes Reis; Lívia Mendes de Carvalho; Anelise Tessari Perboni; Luana Moraes da Luz; Heberte Fernandes de Figueredo; Sebastião Marcos Silva Valentim; et al. (Horticulture, Environment, and Biotechnology, 2025)

Foraging behaviour of donkeys in encroached pastures in Gran Paradiso National Park, Italy - Jacopo Volpe; Ginevra Nota; Ramona Viterbi; Andrea Mainetti; Simone Ravetto Enri; Michele Lonati; Giampiero Lombardi; Marco Pittarello (Agroforestry Systems, 2025)
Since the 1950s, land abandonment in mountain areas has caused the progressive encroachment of pastures by woody species (shrubs and trees), resulting in a decrease in forage availability and quality for domestic livestock. The use of hardy species, such as donkeys, could represent a promising method allowing the exploitation of this alternative forage source in the context of silvopastoral systems while contrasting the expansion of shrubs and trees into open pastures. In this study, the feeding behaviour of donkeys was analysed through direct observations by evaluating their selection of different plant species throughout the grazing season. Specifically, we: (1) quantified the consumption of woody plant species; (2) evaluated whether certain woody plants, being palatable to donkeys, are preferentially consumed and their relative consumption increases with their abundance in the feeding station. The results showed a predilection of donkeys for herbaceous forage (89% of the diet), despite highlighting dietary flexibility with a significant ability to consume some woody species and ferns, especially when their abundance in the environment was high. Donkeys could therefore support management strategies aimed at conserving pastures facing shurb and tree encroachment in Alpine agro-ecosystems.

Hominin and carnivore roles during the formation of the early Middle Pleistocene site of Loreto (Venosa Basin, southern Italy) - Antonio Pineda; Beniamino Mecozzi; Alessio Iannucci; Marco Carpentieri; Raffaele Sardella; Suzanne Simone; Marie‐Hélène Moncel (Journal of Quaternary Science, 2025)
The site of Loreto (Venosa Basin, Italy) was first discovered in 1929 and subsequently excavated during the latter half of the 20th century. The excavation revealed three archaeo‐palaeontological levels, with the lowermost level (Level A) yielding the largest number of remains. Despite the site's notable fossil record, which underscores its importance within the framework of the early Middle Pleistocene, extant research on the site's substantial mammalian fauna has hitherto been confined to a modest number of palaeontological descriptions. The present study constitutes the first taphonomic research of the faunal remains recovered from Level A of Loreto. The anatomical and taxonomic diversity is low, with a marked predominance of cervids. However, the sample appears to be biased by the almost complete absence of small fragments and the high proportion of identifiable remains. The influence of water on the osteological assemblage is minimal, thereby ruling out a fluvial origin of the accumulation. Moreover, anthropogenic and carnivore activity is limited, suggesting that these predators did not significantly contribute to the formation of the assemblages as accumulating agents. It is hypothesised that carnivores and hominins acted in independent events on different carcasses, with little or no interaction among them, as part of the foraging and resource acquisition activities developed in the region. The comparison of these data with those presented for the nearby site of Notarchirico facilitates an understanding of hominin behaviour in the Venosa Basin during the early Middle Pleistocene.

ITV-net: a dataset of intraspecific leaf traits data across major Italian habitats - Stefano Chelli; Alessandro Bricca; Francesco Petruzzellis; Enrico Tordoni; Giacomo Calvia; Alicia T.R Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; et al. (Plant Biosystems, 2025)

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Technical Note: Different analytical approaches in the quantification of microbial crude protein pool in abomasal digesta of nursling goat kids - Jardeson de Souza Pinheiro; Paulo Sergio Dornelas Silva; Isadora Emily Ribeiro; Dhones Rodrigues Andrade; Natalia Veloso Trópia; Yame Fabres Robaina Sancler-Silva; Erollykens Ferreira Santos; Giarlã Cunha da Silva; Simone Eliza Facione Guimarães; Marcos Inacio Marcondes (Animal Feed Science and Technology, 2025)

CrowNet: a trail-camera canopy monitoring system - Francesco Chianucci; Alice Lenzi; Emma Minari; Matteo Guasti; Silvia Gisondi; Marco Gonnelli; Simone Innocenti; Carlotta Ferrara; Alessandro Campanaro; Paola Ciampelli; Andrea Cutini; Nicola Puletti (Agricultural and Forest Meteorology, 2025)

Impact of the COVID-19 pandemic on the operations of one regional musculoskeletal tissue bank - Francesco Puglia; Andrea Della Valle; Riccardo Compagnoni; Daniele Priano; Alessandra Menon; Lorenzo Teani; Giovanni Andrea La Maida; Marco Sacchi; Federico Ambrogi; Pietro Simone Randelli (Cell and Tissue Banking, 2025)

Exploring bee functional trait response to the agro-environment: a possible contribution to the future design of a farm-level indicator - Manuela Giovanetti; Emanuele Luigi Zenga; Marco d’Agostino; Simone Flaminio; Marta Galloni; Laura Bortolotti; Marino Quaranta (Environmental Monitoring and Assessment, 2025)

The ecology of the oxyscape in coastal ecosystems - Marco Fusi; Fabrice Stephenson; Sergio A. Navarrete; Fabian J. Tapia; John L. Largier; Ramona Marasco; Theresa Rueger; Chancey MacDonald; Daniele Daffonchio; Miriam Fernandez; Evie A. Wieters; Jenny Booth; et al. (Trends in Ecology & Evolution, 2025)

The reintroduction of Apennine chamois in the Majella National Park: An evaluation of long-term results - Antonio Antonucci; Alessandro Asprea; Roberta Chirichella; Simone Angelucci; Giovanna Di Domenico; Marco Apollonio (Journal for Nature Conservation, 2025)

Monitoring colonization dynamics and photosynthetic activity of lichens in the House of the Ancient Hunt, Pompeii (Italy), under the climate change scenario - Marta Cicardi; Mariagrazia Morando; Laura Guidorzi; Veronica Bellacicco; Simone Guion; Enrica Matteucci; Greta Rao-Torres; Alessia Romano; Arianna V. Scarcella; Daniele Castelli; Alessandro Lo Giudice; Valeria Meirano; et al. (International Biodeterioration & Biodegradation, 2025)

A morphometric analysis of embayed beaches: southern Sardinia Island - Antonio Usai; Simone Simeone; Daniele Trogu; Marco Porta; Sandro De Muro (Geomorphology, 2025)

The early Aptian marine stratigraphic record in the interior of Gondwana: New insights from the Araripe Basin, Northeastern Brazil - Henrique Parisi Kern; Jorge Villegas-Martín; Gerson Fauth; Fernanda Luft-Souza; Oscar Strohschoen; Lilian Maia Leandro; Alessandra Santos; Mauro Daniel Rodrigues Bruno; Edna de Jesus Francisco Tungo; Marcos Antonio Batista dos Santos Filho; Daiane Ceolin; Simone Baecker-Fauth; et al. (Marine and Petroleum Geology, 2025)

A critical review of the application of polymer of low concern and regulatory criteria to perfluoropolyethers - Hassan Javed; Graham K. Ansell; Frank Adamsky; Marco Malvasi; Paige K. Mulvaney; Pier Antonio Guarda; Robert H. Moffett; Simone Genna; Steve Johnston; Xian Liang (Journal of Fluorine Chemistry, 2025)

Hair analysis as a non-invasive method for assessing the exposure of wildlife to per- and poly-fluoroalkyl substances (PFAS) - Marco Picone; Simone Marangoni; Giulia Silan; Annamaria Volpi Ghirardini; Rossano Piazza; Tiziano Bonato (Environmental Pollution, 2025)

Enhancing ventilated roof performance: A study on Maisotsenko indirect evaporative cooling for school buildings - Nicolò Morselli; Marco Puglia; Michele Cossu; Simone Pedrazzi; Giulio Allesina; Paolo Tartarini; Alberto Muscio (Energy and Buildings, 2025)

Effect of the genotype and environment interaction on body weight traits in Nelore cattle (Bos indicus) - Raimundo Nonato Colares Camargo-Júnior; Cláudio Vieira de Araújo; Caio de Souza Teixeira; Simone Inoe de Araújo; Raysildo Barbosa Lôbo; Lílian Roberta Matimoto Nakabashi; Letícia M. Mendes de Castro; Flávio Luiz Menezes; André Guimarães Maciel e Silva; José Ribamar Felipe Marques; Welligton Conceição da Silva; Marco Aurélio Lopes Della Flora; et al. (Tropical Animal Health and Production, 2025)

Taxonomy for conservation: multi-taxa survey evidences a biodiversity hotspot in the Central Apennines (Salto-Cicolano District) - Pierangelo Crucitti; Danilo Russo; Giovanni Amori; Marcello Vitale; Corrado Battisti; Roberto Antonelli; Davide Brocchieri; Marco Giardini; Luigi Lenzini; Paolo Mazzei; Nicolò Pellecchia; Luca Tringali; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Landslide studying and monitoring by combining digital models from aerial visible and infrared photogrammetry - Simone Mineo; Davide Caliò; Marco Intelisano; Giovanna Pappalardo (Landslides, 2025)
In this paper, a methodological framework to study and monitor a landslide through visible and infrared photogrammetry is presented. The procedure is applied to a coastal landslide that occurred within a nature reserve in 1993, which was surveyed using aerial sensors. Two types of landslide dense point clouds were generated through photogrammetry algorithms: the first arose from photos taken in daylight, while the second was realized with infrared images taken in dark environmental conditions, providing an innovation hint to the study. The combined analysis of the two models allowed achieving a morphological characterization of the landslide, through the recognition and mapping of the main features. Both models gave also hints on the presence of major structural planes controlling the landsliding motif of the studied cliff, which were measured at both the cliff and rock mass scales, through digital rock mass surveys at selected outcrops. Results allowed recognizing two main discontinuity sets, likely related to the major tectonic systems crossing the area. Finally, since the daylight surveys were repeated in 2021 and 2024, the resulting models were compared also to a preliminary dense point cloud built by using some 2014 landslide perspective photos. The so set 10-year monitoring suggested that the zone of depletion is affected by secondary movements, such as minor rockfalls and shallow denudation, while the foot is undergoing erosion by wave action. The combined analysis of visible and thermal dense point clouds proved a successful procedure for a complete landslide morphological and structural characterization, resulting in a reliable operation alternative to conventional surveys in restricted areas. Moreover, the digital monitoring allowed evaluating the evolution of key parts of the landslides, providing useful information in the frame of possible stabilization works or territorial planning.

Exporting the just transition? The European Investment Bank, the European Green Deal and environmental and social rules for green projects outside the EU - Sara de Simone; Marco Nicolò; Louisa Parks (International Environmental Agreements: Politics, Law and Economics, 2025)
The European Union’s European Green Deal (EGD) aims for a just transition to carbon neutrality both within and beyond its borders. This contribution to the special issue on the external dimensions of the EGD focuses on the role of the European Investment Bank (EIB). As a newly declared climate bank and a major funder of ‘green’ projects, the EIB’s role in this vein deserves attention. Do the environmental and social principles the EIB uses to judge funding applications contribute to an environmentally just transition? We explore this question by identifying key issues in impact assessment processes in the literature, brought into focus through an original illustrative case study on the Gibe III hydroelectric dam inaugurated in 2016 in Ethiopia, and linking these to three central aspects of Environmental Justice: recognitional, procedural and redistributive justice. This forms the basis for an analysis of the EIB’s environmental and social statements over time, and a reflection on how far current rules address critical issues. While the EIB’s rules pay increasing attention to critical issues such as the content of Environmental and Social Impact Assessments (ESIAs), and questions around inclusion, timing, and trust, their contribution to a just transition could be strengthened by sharing responsibility for impact assessments with funding applicants and including rules about their co-design. A bottom-up approach to environmental and social issues could contribute to building shared norms amongst funders and a more universal adoption of ESIAs, and to strengthening networks of grassroots expertise to tackle power asymmetries.

Concerns linked to highly dispersed iron anchored within graphitic carbon nitride, is it a truly promising material to drive heterogeneous photo-Fenton treatments? - Simone Pellegrino; Iván Sciscenko; Fabrizio Caldera; Claudio Minero; Enzo Laurenti; Marco Minella (Chemosphere, 2025)

New records on autogenic behavior among populations of Ornithodoros fonsecai (Labruna and Venzal, 2009) (Ixodida: Argasidae) from northeastern Brazil - Ana Carolina Castro-Santiago; Leidiane Lima-Duarte; Jaqueline Valeria Camargo; Simone Michaela Simons; Ricardo Bassini-Silva; Ana Cláudia Calchi; Glauber Meneses Barboza de Oliveira; Maurício Cláudio Horta; Sebastián Muñoz-Leal; Marcelo Bahia Labruna; Marcos Rogério André; Rosangela Zacarias Machado; et al. (Veterinary Research Communications, 2025)

Phytoplankton taxonomic composition, nutrients utilization and biogeochemistry in the upper mixed layer in the coastal area of the Terra Nova Bay, Ross Sea, Antarctica - Luca Massi; Caterina Nuccio; Chiara Melillo; Silvia Becagli; Giovanna Mori; Lorenzo Verdiani; Simone Bonamano; Alice Madonia; Viviana Piermattei; Marco Marcelli; Luigi Lazzara (Frontiers in Marine Science, 2025)
Within BioAPRoS project (Biogenic Aerosol and Primary production in the Ross Sea) two research campaigns were conducted in the coastal area of Terra Nova Bay (TNB) in front of the Italian Base Mario Zucchelli Station, Ross Sea, Antarctica, spanning from 13/11/2018 to 30/01/2019 (BioAPRoS18), and from 01/12/2019 to 30/01/2020 (BioAPRoS19), an area classified as Marginal Ice Zone (MIZ) during this period. The goal was to study nutrient dynamics, phytoplankton biomass and taxonomic composition in the upper mixed layer (UML), exploring assimilation preferences of different phytoplankton assemblages and their biogeochemical effects. The findings were compared with similar 1990s campaigns in the same region. In line with the previous outcome, UML was persistent and always very shallow (5-18 m). Nutrient concentrations showed decreasing trends from spring to summer synchronously opposite to Chl a , highlighting pronounced consumption of nutrients during phytoplankton growth. Discrepancies emerged during phytoplankton summer bloom; in BioAPRoS18 N/P was about 40 due to ΔN/ΔP removal ratio of 11.8, a typical already known condition, while BioAPRoS19 showed an unprecedented N/P around 6 with ΔN/ΔP of 17.6. Also, differences in Si/P and Chl a /Si ratios emerged. Diatoms were the primary group in both campaigns, but they exhibited highly differentiated composition. In BioAPRoS18 pennate diatoms, notably Fragilariopsis curta , were prevalent as in ‘90s campaigns, while BioAPRoS19 experienced the dominance of centric diatoms, especially Dactyliosolen tenuijunctus , never occurred before. These differences in nutrients dynamics and taxonomic composition between the two diatom assemblages, most likely indicate different assimilation modalities of N and P, with Dactyliosolen tenuijunctus favouring N assimilation over P, unlike Fragilariopsis curta . Biological and biogeochemical characteristics of TNB, a pivotal marine ecosystem, are then displaying shifts after relative stability since the 1990s that could be the result of current climate change. These trends necessitate in-depth investigations and monitoring to comprehend and manage these shifts effectively.

Development of an eco-hydrological distance index and improved environmental flow assessment by integrating ecological monitoring and hydrological modeling - Chiara Arrighi; Marco De Simone; Gaia Checcucci; Isabella Bonamini; Stefano Bartalesi; Cristina Simoncini; Fabio Castelli (Science of The Total Environment, 2025)

Surviving in a Warmer Marine World: A Study on the Impact of Thermal Effluent on Posidonia oceanica Meadows and Associated Fish Assemblages in the Maltese Islands - Alessio Marrone; Alessandro Rinaldi; Valeria Montalto; Adam Gauci; Francesca Ape; Henri Ringeard; Marco Spoto; Marco Martinez; Emanuela Claudia La Marca; Simone Mirto; Alan Deidun (Journal of Marine Science and Engineering, 2025)
Ocean warming poses significant threats to coastal ecosystems. This study investigates the impact of thermal effluents from power plants, as proxies for climate-driven temperatures increase, on Posidonia oceanica meadows and associated fish communities. Using a gradient-based approach, we analyzed environmental variables, seagrass indicators, fish assemblages, and functional group (FG) dynamics across a thermal gradient extending from the effluent outfall itself. Results indicate that temperature is the dominant factor influencing P. oceanica, with reduced leaf length, shoot density, and rhizome weight characterizing samples closest to the effluent. Despite compensatory mechanisms, the overall photosynthetic biomass and resilience declined under thermal stress. Fish assemblages exhibited reduced species richness and biodiversity close to the thermal effluent, with opportunistic and thermophilic species dominating. An FG analysis revealed disrupted seasonal patterns, shifts in trophic dynamics, and functional compensation among species, highlighting potential ecological imbalances. Notably, transient predators thrived near the effluent, while more sedentary and temperate species were displaced. These findings underscore the cascading effects of rising temperatures on coastal habitats such as P. oceanica meadows and their associated communities, emphasizing the urgency for conservation measures. By identifying critical thresholds and adaptive responses, this study contributes valuable insights into the consequences of localized impacts of thermal stress on coastal biodiversity and ecosystem services.

Describing functional diversity of communities from environmental DNA - Isabel Cantera; Simone Giachello; Tamara Münkemüller; Marco Caccianiga; Mauro Gobbi; Gianalberto Losapio; Silvio Marta; Barbara Valle; Krzysztof Zawierucha; Wilfried Thuiller; Gentile Francesco Ficetola (Trends in Ecology & Evolution, 2025)

Glyphosate and glyphosate-based herbicides induce Poecilia reticulata to maintain redox equilibrium during and after coexposure to iron oxide nanoparticles (y-Fe2O3) - João Marcos de Lima Faria; Mariana Morozesk; Iara da Costa Souza; Victória Costa da Silva; Luiz Arthur Mendes Bataus; Simone Maria Teixeira de Sabóia-Morais; Marisa Narciso Fernandes (Aquatic Toxicology, 2025)

TNBS colitis induces architectural changes and alpha-synuclein overexpression in mouse distal colon: A morphological study - Arianna Casini; Giorgio Vivacqua; Ludovica Ceci; Stefano Leone; Rosa Vaccaro; Marco Tagliafierro; Filippo Maria Bassi; Sara Vitale; Emanuele Bocci; Luigi Pannarale; Simone Carotti; Antonio Franchitto; et al. (Cell and Tissue Research, 2025)

Fast, sensitive, and sustainable colorimetric detection of chlorogenic acid in artichoke waste material - Doretta Cuffaro; Pasquale Palladino; Maria Digiacomo; Simone Bertini; Maria Minunni; Marco Macchia (Food Chemistry, 2025)

A Multispecies Reactive Transport Model of Sequential Bioremediation and Pump-and-treat in a Chloroethenes-polluted Aquifer - Giulia Casiraghi; Daniele Pedretti; Giovanni P. Beretta; Lucia Cavalca; Simone Varisco; Marco Masetti (Water, Air, & Soil Pollution, 2025)

Evaluation of X-ray fluorescence for analysing critical elements in three electronic waste matrices: A comprehensive comparison of analytical techniques - Shaun T. Lancaster; Eskil Sahlin; Marcus Oelze; Markus Ostermann; Jochen Vogl; Valérie Laperche; Solène Touze; Jean-Philippe Ghestem; Claire Dalencourt; Régine Gendre; Jessica Stammeier; Ole Klein; et al. (Waste Management, 2024)

Functional changes of protist communities in soil after glacier retreat - Simone Giachello; Isabel Cantera; Alexis Carteron; Aurelie Bonin; Alessia Guerrieri; Roberto Ambrosini; Marco Caccianiga; Mauro Gobbi; Silvio Marta; Gentile Francesco Ficetola (Science of The Total Environment, 2024)

Spatially variable organic-matter-driven clogging in a stormwater infiltration pond: Isotopic, microbiological and hydrogeological evidence - Daniele Pedretti; Lucia Cavalca; Marco Masetti; Simone Signorini; Sarah Zecchin (Science of The Total Environment, 2024)

Seismic tomography reveals contrasting styles of subduction-channel and mantle-wedge exhumation controlled by upper plate divergent motion - Stefano Solarino; Marco G. Malusà; Elena Eva; Anne Paul; Stéphane Guillot; Silvia Pondrelli; Simone Salimbeni; Liang Zhao (Gondwana Research, 2024)

A serving of blueberry (Vaccinium corymbosum) improves peripheral vascular function but not metabolic and functional markers in older subjects: A randomized, controlled, crossover study - Massimiliano Tucci; Cristian Del Bo’; Daniela Martini; Simone Perna; Mirko Marino; Marco Rendine; Claudio Gardana; Alberto Battezzati; Alessandro Leone; Simona Bertoli; Giancarlo Aldini; Patrizia Riso (Food Research International, 2024)

Optimizing carotenoids NaHDES extraction for enhancing spreadable chocolate's nutritional value - Lucia Sportiello; Roberta Tolve; Fernanda Galgano; Marco Giarola; Simone Musollini; Fabio Favati (Food Bioscience, 2024)

An integrated approach for managing reservoir sedimentation, sediment transport and water supply: the case of Disueri dam, Italy - Cristina Zago; Simone Venturini; Nicolò Rundo; Aldo Bettinetti; Leonardo Santoro; Marco Bonvissuto; Salvatore Conoscenti; Salvatore Pignatone (Journal of Soils and Sediments, 2024)

Exploring the potential of Aeolus lidar mission for ocean color applications - Davide Dionisi; Simone Bucci; Claudia Cesarini; Simone Colella; Davide D'Alimonte; Lorenzo Di Ciolo; Paolo Di Girolamo; Marco Di Paolantonio; Noemi Franco; Giacomo Gostinicchi; Giovanni Giuliano; Tamito Kajiyama; et al. (Remote Sensing of Environment, 2024)

Electrical resistivity tomography: A reliable tool to monitor the efficiency of different irrigation systems in horticulture field - Agnese Innocenti; Veronica Pazzi; Marco Napoli; Rossano Ciampalini; Simone Orlandini; Riccardo Fanti (Journal of Applied Geophysics, 2024)

Cross-taxon analysis in the highly threatened Mediterranean dunes reveals consistent diversity patterns in butterfly and plant communities - Micaela del Valle Rasino; Simone Fattorini; Andrea Sciarretta; Marco Colacci; Angela Stanisci; Maria Laura Carranza (Biodiversity and Conservation, 2024)
Butterflies and plant species are widely used as model systems in biodiversity and conservation research. However, little is known about spatial patterns of butterfly diversity linked to plant communities across coastal dune ecotones. We explored the relation between butterfly and vegetation diversity in a Mediterranean protected dune system in Central Italy. We sampled butterfly and plant communities on shifting and fixed dunes and investigated their distribution patterns by diversity indexes and Species Abundance Diversity models (SADs). We also computed species beta-diversity and analyzed the relation between butterfly communities and vegetation by correlation analyses. Cross-taxon congruence in species richness, composition and abundance was assessed using Mantel correlation tests. Both butterfly and plant diversity were higher on the fixed dunes than on the shifting dunes. In both communities, SADs were adequately described by the geometric series model, which is typical of harsh environments with simple communities dominated by few species. Among both butterflies and plants, we identified species found only on either the shifting or the fixed dunes. Correlation between plant and butterfly diversity was higher for entomophilous plant species than for the more abundant anemophilous ones. Our results indicate that both plant and butterfly communities respond to the sea-inland environmental gradient, forming distinct communities with specialized taxa. Our findings also provide evidence of the importance of butterfly-plant relations for preserving biological diversity and ecosystem functioning in Mediterranean coastal areas.

Thermal modeling of the lunar South Pole: Application to the PROSPECT landing site - Michelangelo Formisano; Maria Cristina De Sanctis; Sarah Boazman; Alessandro Frigeri; David Heather; Gianfranco Magni; Matteo Teodori; Simone De Angelis; Marco Ferrari (Planetary and Space Science, 2024)

Comprehensive characterization of bacterial glycoconjugate vaccines by liquid chromatography - mass spectrometry - Fiammetta Di Marco; Agnes L. Hipgrave Ederveen; Guusje van Schaick; Alan B. Moran; Elena Domínguez-Vega; Simone Nicolardi; Constantin Blöchl; Carolien A. Koeleman; Renzo Danuser; Ali Al Kaabi; Viktoria Dotz; Jan Grijpstra; et al. (Carbohydrate Polymers, 2024)

An innovative formulation to improve spent coffee characteristics as soil fertilizer: Nutrient, chemical characterization and effects on plant germination - Simone Angeloni; Giovanni Caprioli; Marco Cespi; Laura Acquaticci; Ahmed M. Mustafa; Agnese Santanatoglia; Aldo D'Alessandro; Martina Coletta; Natasha Waris; Antonietta La Terza (Biocatalysis and Agricultural Biotechnology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Geophysical evidence of large-scale silica-rich fluid flow above the continental subduction interface - Yuantong Mao; Liang Zhao; Marco G. Malusà; Stefano Solarino; Silvia Pondrelli; Baolu Sun; Coralie Aubert; Simone Salimbeni; Elena Eva; Stéphane Guillot (Science China Earth Sciences, 2024)

Clay mineralogy in west Chryse Planitia, Mars: Comparison with present and future landing sites - Jeremy Brossier; Francesca Altieri; Maria Cristina De Sanctis; Alessandro Frigeri; Marco Ferrari; Simone De Angelis; Enrico Bruschini (Planetary and Space Science, 2024)

Multiple short-lived marine incursions into the interior of Southwest Gondwana during the Aptian - Gerson Fauth; Oscar Strohschoen; Simone Baecker-Fauth; Fernanda Luft-Souza; Marcos Antonio Batista dos Santos Filho; Alessandra Santos; Mauro Daniel Rodrigues Bruno; Patrícia Mescolotti; Guilherme Krahl; Mitsuru Arai; Francisco Henrique de Oliveira Lima; Mario Luis Assine (Marine Micropaleontology, 2024)

Heavy metals in surface sediments of Lake Patria wetland, southern Italy, and environmental risk - Michele Arienzo; Sergio Bravi; Maria Toscanesi; Carlo Donadio; Giuseppe De Simone; Corrado Stanislao; Luciano Ferrara; Vincenzo Allocca; Antonella Giarra; Marco Trifuoggi (Journal of Geochemical Exploration, 2024)

Characterization of cross-continental PM2.5: Insights into emissions and chemical composition - Caroline Scaramboni; Camila Novais Farias; Pérola de Castro Vasconcellos; Michael Levi; Ioannis Sadiktsis; Simone Andréa Pozza; Gisela de Aragão Umbuzeiro; Tetsushi Watanabe; Poliany Cristiny de Oliveira Rodrigues; Adriana Grandis; Débora Pagliuso; Marcos Silveira Buckeridge; et al. (Atmospheric Research, 2024)

Environmental life cycle assessment of rice production in northern Italy: a case study from Vercelli - Vinci Giuliana; Maddaloni Lucia; Ruggeri Marco; Vieri Simone (The International Journal of Life Cycle Assessment, 2024)
Purpose The study’s objective is to assess the environmental performance of rice production in Northern Italy, in particular in Piedmont, the first Italian and European district for the rice-growing area, and thus identify the most critical hotspots and agricultural processes. In particular, as a case study, a farm located in Vercelli (VC) has been chosen. Subsequently, the study results were compared with other different cultivation practices to evaluate the most sustainable choice. Methods The application of the LCA has been performed, highlighting the phases of rice production that have the most significant impact. Then, uncertainty and sensitivity analyses have been made to estimate the robustness of the results and assess the influence of changing some input variables on emission reduction. Finally, multivariate statistical, specifically a principal component analysis (PCA), was conducted to aid the interpretation of the output dataset of this case study. LCA, uncertainty analysis, and sensitivity analysis were performed with SimaPro 9.2.0, using ReCiPe 2016 Midpoint (H) methodology, and PCA with R software. Results and discussions The hotspot with the highest environmental load is irrigation, which compared to the other phases impacts more in 15 out of 18 categories, including 12 with impacts greater than + 75%. This is because irrigation causes direct impacts, related to the methanogenesis in rice fields, but also indirect impacts related mainly to the production of the energy mix required to move the large masses of irrigation water. Therefore, different water management systems were compared and results show that the irrigation systems based on intermittent paddy submergence (DSI) could result in − 40% lower impacts, resulting to be the preferable technique over the other irrigation systems analyzed, including the traditional one used in this study. Conclusions In order to reduce the environmental impacts related to the irrigation process, a water management system characterized by intermittent flooding of the paddy field (DSI) could be used as it reduces the environmental impacts the most (− 40%), while the least suitable system is one characterized by continuous flooding without drought periods, as it causes the highest impacts.

Combining fertilisation and mowing as an effective practice to control Brachypodium rupestre encroachment in an abandoned grassland of the Alps - Marco Pittarello; Alessandra Gorlier; Simone Ravetto Enri; Michele Lonati; Giampiero Lombardi (Agriculture, Ecosystems & Environment, 2024)

Meta-analysis of the Cetacea gut microbiome: Diversity, co-evolution, and interaction with the anthropogenic pathobiome - Elena Radaelli; Giorgia Palladino; Enrico Nanetti; Daniel Scicchitano; Simone Rampelli; Sabina Airoldi; Marco Candela; Marianna Marangi (Science of The Total Environment, 2024)

Numerical Study on the Performance of an OWC under Breaking and Non-Breaking Waves - Giovanni Cannata; Francesco Biondi; Marco Simone (Journal of Marine Science and Engineering, 2024)
A numerical model for the simulation of the performance of an oscillating water column (OWC) subjected to non-breaking and breaking waves is proposed in this paper. The numerical model consists of a hydrodynamic model specifically designed to simulate breaking waves and a pneumatic model that takes into account the air compressibility. The proposed numerical model was applied to evaluate the potential mean annual energy production from the waves of two coastal sites characterized by different hydrodynamic conditions: a deep-water condition, where the OWC interacts with non-breaking waves, and a shallow-water condition, where the OWC is subjected to breaking waves. The numerical results show that the effects of the air compressibility can be considered negligible only in numerical simulations of the performances of reduced-scale OWC devices, such as those used in laboratory experiments. We demonstrated that in real-scale simulations, the effect of the air compressibility within the OWC chamber significantly reduces its ability to extract energy from waves. The numerical results show that the effect of the air compressibility is even more significant in the case of a real-scale OWC located in the surf zone, where it interacts with breaking waves.

Preliminary spectroscopic investigation of a potential Mars analog site: Lake Bagno dell’Acqua, Pantelleria, Italy - Enrico Bruschini; Marco Ferrari; Cristina Mazzoni; Stefano Fazi; Francesco Latino Chiocci; Ilaria Mazzini; Giovanna Costanzo; Simone De Angelis; Maria Cristina De Sanctis; Francesca Altieri; Jeremy Brossier; Eleonora Ammannito (Planetary and Space Science, 2024)

Lactobacillus delbrueckii CIDCA 133 fermented milk modulates inflammation and gut microbiota to alleviate acute colitis - Luís Cláudio Lima de Jesus; Andria dos Santos Freitas; Joyce da Cruz Ferraz Dutra; Gabriela Munis Campos; Monique Ferrary Américo; Juliana Guimarães Laguna; Evandro Gonçalves Dornelas; Rodrigo Dias de Oliveira Carvalho; Kátia Duarte Vital; Simone Odília Antunes Fernandes; Valbert Nascimento Cardoso; Jamil Silvano de Oliveira; et al. (Food Research International, 2024)

Effectiveness of modified atmosphere and vacuum packaging in preserving the volatilome of Stelvio PDO cheese over time - Bruno Domingues Galli; Elisabetta Trossolo; Ilaria Carafa; Simone Squara; Andrea Caratti; Pasquale Filannino; Chiara Cordero; Marco Gobbetti; Raffaella Di Cagno (Food Chemistry, 2024)

Allografts use in orthopedic surgery: trend change over the past 11 years from a regional tissue bank - Andrea Della Valle; Riccardo Compagnoni; Francesco Puglia; Daniele Priano; Alessandra Menon; Lorenzo Teani; Giovanni Andrea La Maida; Tullia De Feo; Marco Sacchi; Federico Ambrogi; Alfonso Cicatelli; Pietro Simone Randelli (Cell and Tissue Banking, 2024)

Future distribution of demersal species in a warming Mediterranean sub-basin - Diego Panzeri; Marco Reale; Gianpiero Cossarini; Stefano Salon; Roberto Carlucci; Maria Teresa Spedicato; Walter Zupa; Nedo Vrgoč; Simone Libralato (Frontiers in Marine Science, 2024)
Predicting range shifts of marine species under different CO2 emission scenarios is of paramount importance to understand spatial potential changes in a context of climate change and to ensure appropriate management, in particular in areas where resources are critical to fisheries. Important tools which use environmental variables to infer range limits and species habitat suitability are the species distribution models or SDMs. In this work, we develop an ensemble species distribution model (e-SDM) to assess past, present and future distributions under Representative Concentration Pathway (RCP) 8.5 of nine demersal species and hotspot areas for their two life stages (adult and juvenile) in the Adriatic and Western Ionian Seas in four time windows (1999-2003, 2014-2018, 2031-2035 and 2046-2050). The e-SDM has been developed using three different models (and sub-models), i.e. (i) generalized additive models (GAM), (ii) generalized linear mixed model (GLMM), (iii) gradient boosting machine (GBM), through the combination of density data in terms of numbers of individuals km 2 and environmental variables. Then, we have determined the changes in the aggregation hotspots and distributions. Finally, we assess gains and losses areas (i.e. occupation area) in the future climate change scenario as new potential range shifts for the nine species and their life stages. The results show that densities of some key commercial species, such as Merluccius merluccius (European hake), Mullus barbatus (red mullet), and Lophius budegassa (anglerfish) will be shifting northwards.

Application of non-lethal bioSPME-LC-MS/MS for the detection of human pharmaceuticals in soft corals: A survey at the North Nilandhe atoll (Maldives) - Alessandro Becchi; Marco Mantovani; Marina Lasagni; Elena Collina; Simone Montano; Paolo Galli; Francesco Saliu (Chemosphere, 2024)

The power of Posidonia oceanica meadows to retain microplastics and the consequences on associated macrofaunal benthic communities - Marco Martinez; Roberta Minetti; Emanuela Claudia La Marca; Valeria Montalto; Alessandro Rinaldi; Elisa Costa; Fabio Badalamenti; Francesca Garaventa; Simone Mirto; Francesca Ape (Environmental Pollution, 2024)

Biological invasions are a population‐level rather than a species‐level phenomenon - Phillip J. Haubrock; Ismael Soto; Danish A. Ahmed; Ali R. Ansari; Ali Serhan Tarkan; Irmak Kurtul; Rafael L. Macêdo; Adrián Lázaro‐Lobo; Mathieu Toutain; Ben Parker; Dagmara Błońska; Simone Guareschi; et al. (Global Change Biology, 2024)
Biological invasions pose a rapidly expanding threat to the persistence, functioning and service provisioning of ecosystems globally, and to socio‐economic interests. The stages of successful invasions are driven by the same mechanism that underlies adaptive changes across species in general—via natural selection on intraspecific variation in traits that influence survival and reproductive performance (i.e., fitness). Surprisingly, however, the rapid progress in the field of invasion science has resulted in a predominance of species‐level approaches (such as deny lists), often irrespective of natural selection theory, local adaptation and other population‐level processes that govern successful invasions. To address these issues, we analyse non‐native species dynamics at the population level by employing a database of European freshwater macroinvertebrate time series, to investigate spreading speed, abundance dynamics and impact assessments among populations. Our findings reveal substantial variability in spreading speed and abundance trends within and between macroinvertebrate species across biogeographic regions, indicating that levels of invasiveness and impact differ markedly. Discrepancies and inconsistencies among species‐level risk screenings and real population‐level data were also identified, highlighting the inherent challenges in accurately assessing population‐level effects through species‐level assessments. In recognition of the importance of population‐level assessments, we urge a shift in invasive species management frameworks, which should account for the dynamics of different populations and their environmental context. Adopting an adaptive, region‐specific and population‐focused approach is imperative, considering the diverse ecological contexts and varying degrees of susceptibility. Such an approach could improve and refine risk assessments while promoting mechanistic understandings of risks and impacts, thereby enabling the development of more effective conservation and management strategies.

Aqueous enzymatic extraction of macauba (Acrocomia aculeata) pulp oil: A green and sustainable approach for high-quality oil production - Guilherme Dallarmi Sorita; Simone Palma Favaro; Dasciana de Sousa Rodrigues; Wellington Paula da Silva Junior; Wesley Gabriel de Oliveira Leal; Alan Ambrosi; Marco Di Luccio (Food Research International, 2024)

Thermal unrest at La Fossa (Vulcano Island, Italy): the 2021–2023 VIIRS 375 m MIROVA-processed dataset - Adele Campus; Simone Aveni; Marco Laiolo; Francesco Massimetti; Diego Coppola (Bulletin of Volcanology, 2024)

Phthalate levels in common sea anemone Actinia equina and Anemonia viridis: A proxy of short-term microplastic interaction? - Sara Vencato; Simone Montano; Francesco Saliu; Stefania Coppa; Alessandro Becchi; Immacolata Liotta; Tommaso Valente; Mariacristina Cocca; Marco Matiddi; Andrea Camedda; Giorgio Massaro; Davide Seveso; et al. (Marine Pollution Bulletin, 2024)

Clinical outcomes and complications of S53P4 bioactive glass in chronic osteomyelitis and septic non-unions: a retrospective single-center study - Simone Daniel Gatti; Diego Gaddi; Marco Turati; Giulio Leone; Jacobus J. Arts; Fabio Pessina; Mattia Carminati; Giovanni Zatti; Laura De Rosa; Marco Bigoni (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Identifying priority areas for spatial management of mixed fisheries using ensemble of multi‐species distribution models - Diego Panzeri; Tommaso Russo; Enrico Arneri; Roberto Carlucci; Gianpiero Cossarini; Igor Isajlović; Svjetlana Krstulović Šifner; Chiara Manfredi; Francesco Masnadi; Marco Reale; Giuseppe Scarcella; Cosimo Solidoro; et al. (Fish and Fisheries, 2024)
Spatial fisheries management is widely used to reduce overfishing, rebuild stocks, and protect biodiversity. However, the effectiveness and optimization of spatial measures depend on accurately identifying ecologically meaningful areas, which can be difficult in mixed fisheries. To apply a method generally to a range of target species, we developed an ensemble of species distribution models (e‐SDM) that combines general additive models, generalized linear mixed models, random forest, and gradient‐boosting machine methods in a training and testing protocol. The e‐SDM was used to integrate density indices from two scientific bottom trawl surveys with the geopositional data, relevant oceanographic variables from the three‐dimensional physical‐biogeochemical operational model, and fishing effort from the vessel monitoring system. The determined best distributions for juveniles and adults are used to determine hot spots of aggregation based on single or multiple target species. We applied e‐SDM to juvenile and adult stages of 10 marine demersal species representing 60% of the total demersal landings in the central areas of the Mediterranean Sea. Using the e‐SDM results, hot spots of aggregation and grounds potentially more selective were identified for each species and for the target species group of otter trawl and beam trawl fisheries. The results confirm the ecological appropriateness of existing fishery restriction areas and support the identification of locations for new spatial management measures.

Intraspecific variability of leaf form and function across habitat types - Giacomo Puglielli; Alessandro Bricca; Stefano Chelli; Francesco Petruzzellis; Alicia T. R. Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; Giacomo Calvia; et al. (Ecology Letters, 2024)
Trait‐based ecology has already revealed main independent axes of trait variation defining trait spaces that summarize plant adaptive strategies, but often ignoring intraspecific trait variability (ITV). By using empirical ITV‐level data for two independent dimensions of leaf form and function and 167 species across five habitat types (coastal dunes, forests, grasslands, heathlands, wetlands) in the Italian peninsula, we found that ITV: (i) rotated the axes of trait variation that define the trait space; (ii) increased the variance explained by these axes and (iii) affected the functional structure of the target trait space. However, the magnitude of these effects was rather small and depended on the trait and habitat type. Our results reinforce the idea that ITV is context‐dependent, calling for careful extrapolations of ITV patterns across traits and spatial scales. Importantly, our study provides a framework that can be used to start integrating ITV into trait space analyses.

Signature of the anthropogenic impacts on the epipelagic microbiome of the North-Western Adriatic Sea (Mediterranean Sea) - Giulia Trapella; Daniel Scicchitano; Lucia Foresto; Andrea Nicoló Dell’Acqua; Elena Radaelli; Silvia Turroni; Simone Rampelli; Cinzia Corinaldesi; Giorgia Palladino; Marco Candela (Frontiers in Marine Science, 2024)
Introduction In our paper, we explored the impact of different anthropogenic stressors, namely, mussel farming, methane extraction platforms, and summer mass tourism, on the epipelagic microbiomes of the North-Western Adriatic Sea. Methods By 16S rRNA gene sequencing, we provided the epipelagic microbiome layout from selected sites corresponding to each of the considered impacts. As an unimpacted reference, we used already published 16S rRNA sequencing data. Results According to our findings, each one of the anthropogenic stressors resulted in a peculiar increase of specific epipelagic microbial components, including copiotrophic R-strategists and host-restricted bacteria, as well as some pathobiome components, the latter being detected exclusively in impacted sites. Particularly, potentially harmful pathogenic species such as Legionella impletisoli and Staphylococcus epidermidis have been detected in proximity to the mussel farms, and Escherichia coli and Campylobacter ureolyticus were present close to the methane extraction platform and at the summer mass tourism site, respectively. Particularly, C. ureolyticus is an emerging human gastrointestinal pathogen, capable of destroying intestinal microvilli. Discussion In addition to providing evidence supporting the existence of recognizable and impact-driven fingerprints on the epipelagic marine microbiome peculiar to the different anthropogenic stressors, our findings also raise concern about the ecological relevance of the observed changes, in terms of possible loss of ecosystem services and also for the potential release of pathogenic microorganisms in the environment.

Routes of dispersion of antibiotic resistance genes from the poultry farm system - Daniel Scicchitano; Giulia Babbi; Giorgia Palladino; Silvia Turroni; Yitagele Terefe Mekonnen; Cédric Laczny; Paul Wilmes; Pimlapas Leekitcharoenphon; Andrea Castagnetti; Federica D'Amico; Patrizia Brigidi; Castrense Savojardo; et al. (Science of The Total Environment, 2024)

Parent-of-origin effects for the number of oocytes and embryos in Gir cattle - Renata de Fátima Bretanha Rocha; Arielly Oliveira Garcia; Mateus Guimarães dos Santos; Pamela Itajara Otto; Marcos Vinícius Barbosa da Silva; Marta Fonseca Martins; Marco Antônio Machado; João Claudio do Carmo Panetto; Mario P.L. Calus; Jeremie Vandenplas; Simone Eliza Facioni Guimarães (Livestock Science, 2024)

Oyster shell element composition as a proxy for environmental studies - Paulo Sergio Cardoso da Silva; Wellington de Moura Farias; Mauro Roger Batista Pousada Gomez; Jefferson Koyaishe Torrecilha; Flávio Roberto Rocha; Marcos Antônio Scapin; Rafael Henrique Lazzari Garcia; Luis Ricardo Lopes de Simone; Vanessa Simão de Amaral; Mouchi Vincent; Emmanuel Laurent; Paweł Rudnicki-Velasquez (Journal of South American Earth Sciences, 2024)

River–coastal–ocean continuum modeling along the Lazio coast (Tyrrhenian Sea, Italy): Assessment of near river dynamics in the Tiber delta - Simone Bonamano; Ivan Federico; Salvatore Causio; Viviana Piermattei; Daniele Piazzolla; Sergio Scanu; Alice Madonia; Nicola Madonia; Giovanni De Cillis; Eric Jansen; Giorgio Fersini; Giovanni Coppini; et al. (Estuarine, Coastal and Shelf Science, 2024)

Effects of Biophilic Design interventions on university students' cognitive performance: An audio-visual experimental study in an Immersive Virtual office Environment - Arianna Latini; Simone Torresin; Tin Oberman; Elisa Di Giuseppe; Francesco Aletta; Jian Kang; Marco D'Orazio (Building and Environment, 2024)

Dissecting the continuum and unravelling the phylogeographic knot of plastid DNA in European white oaks (Quercus sect. Quercus): ancient signatures and multiple diversity reservoirs - Paola Fortini; Romeo Di Pietro; Elisa Proietti; Simone Cardoni; Luca Quaranta; Marco Cosimo Simeone (European Journal of Forest Research, 2024)
Available knowledge on the European white oaks ( Quercus , sect. Quercus ) plastome still exhibits large gaps, mostly in respect of detailed phylogeny and information from southern Europe and adjacent Near East. We investigated DNA sequence polymorphism at two plastid loci on 270 individuals representing 13 white oak species/taxa and retrieved several hundred sequences of the same two DNA regions from GenBank to fill the above gaps, and contribute to a better understanding of white oak diversity and evolution. The modern European sect. Quercus species exhibits a poorly differentiated plastid DNA, despite its current highly diversified taxonomy. Twenty-nine haplotypes were identified across the Euro-Mediterranean and Near East regions, including two ancestral variants that are westerly and south-easterly partitioned. Other high- and low-frequency haplotypes also showed a well-structured geographic distribution consistent with the current phytogeographic framework of the European continent. The climatic and geological events that characterized the end of the Tertiary and Quaternary periods played a crucial role in triggering haplotype mixing, isolation, and in offering niche opportunities for more recent diversification. Euro-Mediterranean southern territories host a high and as yet poorly studied genetic variation; the role of the Italian Peninsula as a crossroad and threshold for haplotype diversity and distribution clearly emerges from this study.

Cardioprotective Effects of Leucine Supplementation against Doxorubicin-Induced Cardiotoxicity - Lucas C. Guimarães; Thiago M. Fidale; Talita C. R. Pereira; Paulo R. Lopes; Marcos D. Ferreira-Junior; Simone R. Deconte; Marcos L. Ferreira-Neto; Willams S. Brito; Rodrigo M. Gomes; Fernanda R. de Souza; Keilah V. N. Cavalcante; Gustavo C. Herrera; et al. (Cardiovascular Toxicology, 2024)

Foraging behavior of Highland cattle in silvopastoral systems in the Alps - Ginevra Nota; Mia Svensk; Davide Barberis; David Frund; Rebecca Pagani; Marco Pittarello; Massimiliano Probo; Simone Ravetto Enri; Michele Lonati; Giampiero Lombardi (Agroforestry Systems, 2024)
Trees and shrubs expanded in the last decades in European mountains due to land abandonment and the decrease in grazing pressure, and are expected to further spread also due to climate change. As a consequence of low forage quality and topographic constraints, the management of mountain environments dominated by woody vegetation with livestock is often challenging. Silvopastoral systems based on cattle hardy breeds able to forage on woody plants, such as Highland cattle, could be a suitable option for the management and restoration of such environments. In this study, we used direct observations to explore the foraging behavior of Highland cattle in four study areas across the western Alps. In particular, we assessed: (1) cattle diet composition, (2) the selection for more than 30 tree and shrub species, and (3) the relationships between species consumption and their abundance in the environment. Highland cattle fed on a mixture of both woody and herbaceous species, including between 15 and 46% of woody plants in the diet. Some trees (e.g., Celtis australis , Fraxinus spp., and Populus tremula ) and shrubs (e.g., Frangula alnus , Rhamnus spp., and Rubus idaeus ) were positively selected by cattle, thus they could be an important forage supplement to their diet. Moreover, the results highlighted that relative species consumption generally increased with increasing species abundance in the environment, suggesting that this cattle breed could be suitable to control shrub expansion in highly encroached areas. The outcomes of this study can support the development of targeted silvopastoral systems in the Alps.

Canopy-forming algae improve the colonization success of the vermetid reef-builder Dendropoma cristatum (Biondi 1859) on artificial substrates - Emanuela Claudia La Marca; Francesca Ape; Alessandro Rinaldi; Marco Spoto; Marco Martinez; Enrico Dini; Simone Mirto; Valeria Montalto (Frontiers in Marine Science, 2024)
Positive interactions among foundation species play a crucial role in achieving and maintaining a good state of the marine environment, enhancing the habitat stability, productivity, and the whole ecosystem functioning. In this regard, macroalgal canopies may affect the biotic and abiotic environmental features, improving the habitat quality for the establishment of other sedentary organisms. In this study, we investigated the effect of intertidal canopy-forming algae on the colonization success of the central-Mediterranean vermetid reef-builder Dendropoma cristatum (Biondi 1859) on artificial substrates produced for reef restoration purposes. An in situ experiment was carried out along the northwestern coast of Sicily during the breeding season of the vermetid snails, by using geopolymer concrete settlement discs with a topographic design to facilitate the vermetid settlement. The discs were placed on the seaward reef rim, underneath the macroalgal canopy, and on adjacent control bare reef areas. The canopy effect on the understory algal colonization and the environmental temperature at the vermetid settlement substrate were also surveyed. After 35 days of field exposure, the vermetid settlement increased by 1.7-fold on the discs underneath the macroalgal canopy compared with that on the bare settlement discs. Moreover, the understory algae showed a higher homogeneity and a lower percent cover on the settlement discs underneath the macroalgal canopy. The peaks of temperature were higher on the bare reef, and the macroalgal canopy also reduced temperature variability under maximum sun irradiance during the diurnal low tides. The vermetid settlement was positively correlated to the canopy cover, which, directly or indirectly, improved the success of colonization of the reef-builder snails on artificial substrates. The deployment of settlement discs where canopy-forming algae are naturally present may facilitate the gardening of vermetid clusters that may be translocated to restock the reef-builder density at degraded areas.

Ritual displays by a parasitic cuckoo: nuptial gifts or territorial warnings? - Simone Ciaralli; Martina Esposito; Stefano Francesconi; Daniela Muzzicato; Marco Gamba; Matteo Dal Zotto; Daniela Campobello (Animal Behaviour, 2024)

Removal of pharmaceutical compounds from the liquid phase of anaerobic sludge in a pilot-scale high-rate algae-bacteria pond - Marco Mantovani; Simone Rossi; Elena Ficara; Elena Collina; Francesca Marazzi; Marina Lasagni; Valeria Mezzanotte (Science of The Total Environment, 2024)

A Four-Year Video Monitoring Analysis of the Posidonia oceanica Banquette Dynamic: A Case Study from an Urban Microtidal Mediterranean Beach (Poetto Beach, Southern Sardinia, Italy) - Daniele Trogu; Simone Simeone; Andrea Ruju; Marco Porta; Angelo Ibba; Sandro DeMuro (Journal of Marine Science and Engineering, 2023)
This paper investigates the dynamics of the cross-shore extensions of banquettes, a sedimentary structure mostly made by rests of Posidonia oceanica (L.) Delile, in a sandy urban beach located in the Gulf of Cagliari, Italy, western Mediterranean. A video monitoring station was installed above the promontory south of the beach. We analysed a four-year image database and related these dynamics to wave and wind parameters (obtained from the Copernicus and ERA5 databases) from September 2016 to September 2020. Our results showed that banquette deposition occurred in concomitance with the presence of leaf litter in the surf zone associated with mild storm events. Erosion of the banquettes occurred during more intense storms. When leaf litter was not present in the surf zone, banquettes were not deposited even with mild storms. Wind can influence the banquette dynamics: under certain conditions of speed intensity, the banquettes may be removed offshore, supplying litter in the surf zone, or they may be covered by sediment. The permanence of the banquettes on the beaches also depended on their composition: when the banquettes were intertwined with reeds, their removal by the waves did not occur even during intense storms, and this sedimentary structure can protect the beach from flooding.

Geomorphic flood hazard mapping: from floodplain delineation to flood hazard characterization - Andrea Magnini; Michele Lombardi; Armir Bujari; Pietro Mattivi; Iuliia Shustikova; Simone Persiano; Marco Patella; Gabriele Bitelli; Paolo Bellavista; Francesco Lo Conti; Antonio Tirri; Stefano Bagli; et al. (Hydrological Sciences Journal, 2023)

Revamping kombucha production: Achieving consistency and probiotic potential through a tailor-made microbial consortium - Mariana Fensterseifer Fabricio; Bruna Krieger Vargas; Bruna Tischer; Roger Wagner; Stephanie Reis Ribeiro; Nereida Cordeiro; Simone Hickmann Flôres; Marco Antônio Záchia Ayub (International Journal of Gastronomy and Food Science, 2023)

Development and consumer acceptance testing of a honey-based beverage fermented by a multi-species starter culture - Gustavo Eidt; Alessandra Koehler; Paulo Roberto Dall Cortivo; Marco Antônio Záchia Ayub; Simone Hickmann Flôres; Rodrigo Alex Arthur (Food Bioscience, 2023)

A mixed-autonomous robotic platform for intra-row and inter-row weed removal for precision agriculture - Francesco Visentin; Simone Cremasco; Marco Sozzi; Luca Signorini; Moira Signorini; Francesco Marinello; Riccardo Muradore (Computers and Electronics in Agriculture, 2023)

Arsenic movement and fractionation in agricultural soils which received wastewater from an adjacent industrial site for 50 years - Cristiana Morosini; Elisa Terzaghi; Giuseppe Raspa; Marco Grotti; Stefano Armiraglio; Simone Anelli; Antonio Di Guardo (Science of The Total Environment, 2023)

Extraction method for the multiresidue analysis of legacy and emerging pollutants in marine mussels from the Adriatic Sea - Nicolò Interino; Rossana Comito; Patrizia Simoni; Silvia Franzellitti; Giorgia Palladino; Simone Rampelli; Anastasiia Mosendz; Roberto Gotti; Aldo Roda; Marco Candela; Emanuele Porru; Jessica Fiori (Food Chemistry, 2023)

The Evaluation of WaveSAX Power Generation to Support Port Energy Self-Sufficiency - Simone Bonamano; Maximo Aurelio Peviani; Giordano Agate; Calogero Giuseppe Burgio; Giorgio Fersini; Marco Marcelli (Journal of Marine Science and Engineering, 2023)
Remarkable advancements have been made in wave energy converters, notably the innovative WaveSAX technology—an oscillating water column system conceptually designed for coastal structures. Proven effective in existing installations, particularly at Civitavecchia Port, Italy, where the WaveSAX-1 prototype was tested in 2018 and the WaveSAX-2 was updated in 2021. The device’s power generation capacity was evaluated using a Simulating WAves Nearshore (SWAN) model that simulated 30 years of wave conditions. Validation with radar and Acoustic Doppler Profiler instruments showed excellent performance in wave height simulation. Results revealed higher wave power generation near the harbor breakwater, surpassing offshore levels, especially in central and northern sections. WaveSAX-2, featuring an improved Wells turbine, demonstrated a remarkable 37% increase in average efficiency compared to WaveSAX-1. If a linear WaveSAX array were installed, it could produce 4 GWh annually, satisfying 20% of the port’s energy needs and reducing around 2800 tCO2e/year. Doubling arrays and incorporating triangular modules could significantly enhance sustainability for port operations, offering a promising path toward self-sufficiency and environmental responsibility.

Hygrothermal simulation challenges: Assessing boundary condition choices in retrofitting historic European buildings - Simone Panico; Marco Larcher; Daniel Herrera Avellanosa; Cristina Baglivo; Alexandra Troi; Paolo Maria Congedo (Energy and Buildings, 2023)

QuOCS: The quantum optimal control suite - Marco Rossignolo; Thomas Reisser; Alastair Marshall; Phila Rembold; Alice Pagano; Philipp J. Vetter; Ressa S. Said; Matthias M. Müller; Felix Motzoi; Tommaso Calarco; Fedor Jelezko; Simone Montangero (Computer Physics Communications, 2023)

Enantiopure β-isocyano-boronic esters: synthesis and exploitation in isocyanide-based multicomponent reactions - Marco Manenti; Simone Gusmini; Leonardo Lo Presti; Giorgio Molteni; Alessandra Silvani (Molecular Diversity, 2023)
Various boron-containing isocyanides have been efficiently synthesized from the corresponding enantiopure β-substituted β-amino boronic acid pinacol esters, without need for protecting group interconversion, through a two-step, purification-free procedure. They were employed in a variety of isocyanide-based multicomponent reactions, proving to be reliable components for all of them and allowing the efficient synthesis of unprecedented, boron-containing peptidomimetics and heteroatom-rich small molecules, including biologically relevant cyclic boronates. Jointing together the β-amido boronic acid moiety, deriving from the isocyanide component, with prominent pharmacophoric rings emerging from the multicomponent process, a successful application of the molecular hybridization concept could be realized. Graphical abstract

Temperature–humidity index monitoring during two summer seasons in dairy cow sheds in Mugello (Tuscany) - Alessandro Messeri; Marco Mancini; Riccardo Bozzi; Silvia Parrini; Francesco Sirtori; Marco Morabito; Alfonso Crisci; Gianni Messeri; Alberto Ortolani; Bernardo Gozzini; Simone Orlandini; Luca Fibbi; et al. (International Journal of Biometeorology, 2023)
Many studies have reported that the impact of high temperatures affects physiology, welfare, health, and productivity of farm animals, and among these, the dairy cattle farming is one of the livestock sectors that suffers the greatest effects. The temperature–humidity index (THI) represents the state of the art in the evaluation of heat stress conditions in dairy cattle but often its measurement is not carried out in sheds. For this reason, the aim of this study was the monitoring of the THI in three dairy cattle farms in Mugello (Tuscany) to understand its influence on dairy cows. THI values were calculated using meteorological data from direct observation in sheds and outdoor environments. Data relating to the animal’s behavior were collected using radio collars. The Pearson test and Mann–Kendall test were used for statistical analysis. The results highlighted a significant ( P < 0.001) upward trend in THImax during the last 30 years both in Low Mugello (+ 1.1 every 10 years) and in High Mugello (+ 0.9 every 10 years). In Low Mugello sheds, during the period 2020–2022, more than 70% of daytime hours during the summer period were characterized by heat risk conditions (THI > 72) for livestock. On average the animals showed a significant ( P < 0.001) decrease in time spent to feeding and rumination, both during the day and the night, with a significant ( P < 0.001) increase in inactivity. This study fits into the growing demand for knowledge of the micro-climatic conditions within farms in order to support resilience actions for protecting both animal welfare and farm productivity from the effects of climate change. This could also be carried out thanks to estimation models which, based on the meteorological conditions forecast, could implement the thermal stress indicator (THI) directly from the high-resolution meteorological model, allowing to get a prediction of the farm’s potential productivity loss based on the expected THI.

Single-step genome-wide association studies and post-GWAS analyses for the number of oocytes and embryos in Gir cattle - Renata de Fátima Bretanha Rocha; Arielly Oliveira Garcia; Pamela Itajara Otto; Mateus Guimarães dos Santos; Marcos Vinícius Barbosa da Silva; Marta Fonseca Martins; Marco Antônio Machado; João Claudio do Carmo Panetto; Simone Eliza Facioni Guimarães (Mammalian Genome, 2023)

Runs of homozygosity and signatures of selection for number of oocytes and embryos in the Gir Indicine cattle - Renata de Fátima Bretanha Rocha; Arielly Oliveira Garcia; Pamela Itajara Otto; Marcos Vinícius Barbosa da Silva; Marta Fonseca Martins; Marco Antônio Machado; João Claudio do Carmo Panetto; Simone Eliza Facioni Guimarães (Mammalian Genome, 2023)

Pliocene Geotourism: Innovative Projects for Valorizing the Paleontological Heritage of Three Different-Staged Quarries of Tuscany (Central Italy) - Marco Merella; Alberto Collareta; Simone Casati; Andrea Di Cencio; Giovanni Bianucci (Geoheritage, 2023)
Quarries are areas of pivotal importance for investigation, popularization, and educational purposes in the field of geosciences. Here, we focus on three quarries of Tuscany (La Serra, Arcille, and Certaldo) that have been home to significant finds of marine vertebrate fossils. The three selected localities are representative of the many active (La Serra), inactive (Arcille), and abandoned (Certaldo) Tuscan quarries where vertebrate-bearing Pliocene deposits are exposed. Given the richness and scientific value of their paleontological content (including holotypes as well as otherwise unique specimens), the abundance of exposed sedimentary structures, and the high potential for open-air musealization, the La Serra, Arcille, and Certaldo quarries should be regarded as geosites. These quarries are thoroughly described, and several suggestions for their preservation and valorization are proposed, focusing on their importance for geotourism, with the goal of reaching out to the broadest audience possible. Many innovative dissemination tools, including 3D technologies, are now available for pursuing such an aim.

Seasonal dynamics of the microbiome-host response to pharmaceuticals and pesticides in Mytilus galloprovincialis farmed in the Northwestern Adriatic Sea - Giorgia Palladino; Simone Rampelli; Daniel Scicchitano; Enrico Nanetti; Letizia Iuffrida; Rajapaksha Haddokara Gedara Rasika Wathsala; Nicolò Interino; Mauro Marini; Emanuele Porru; Silvia Turroni; Jessica Fiori; Silvia Franzellitti; et al. (Science of The Total Environment, 2023)

A comparison of numerical approaches for statistical inference with stochastic models - Marco Bacci; Jonas Sukys; Peter Reichert; Simone Ulzega; Carlo Albert (Stochastic Environmental Research and Risk Assessment, 2023)
Due to our limited knowledge about complex environmental systems, our predictions of their behavior under different scenarios or decision alternatives are subject to considerable uncertainty. As this uncertainty can often be relevant for societal decisions, the consideration, quantification and communication of it is very important. Due to internal stochasticity, often poorly known influence factors, and only partly known mechanisms, in many cases, a stochastic model is needed to get an adequate description of uncertainty. As this implies the need to infer constant parameters, as well as the time-course of stochastic model states, a very high-dimensional inference problem for model calibration has to be solved. This is very challenging from a methodological and a numerical perspective. To illustrate aspects of this problem and show options to successfully tackle it, we compare three numerical approaches: Hamiltonian Monte Carlo, Particle Markov Chain Monte Carlo, and Conditional Ornstein-Uhlenbeck Sampling. As a case study, we select the analysis of hydrological data with a stochastic hydrological model. We conclude that the performance of the investigated techniques is comparable for the analyzed system, and that also generality and practical considerations may be taken into account to guide the choice of which technique is more appropriate for a particular application.

From Early Bronze Age domestic plant production to Middle Bronze Age regional exchange economy: the archaeobotanical assemblages from Tel Kabri - Marco Nicoli’; Simone Riehl; Eric H. Cline; Assaf Yasur-Landau (Archaeological and Anthropological Sciences, 2023)
Recent excavations at the site of Tel Kabri have brought some extraordinary findings, including the earliest wine cellar in the ancient Near East discovered in 2013. During these excavations, archaeobotanical samples were collected continuously and then processed in 2019. The archaeobotanical studies focus on the Middle Bronze Age palace in Area DW and the Early Bronze Age domestic deposits in Area L. The results confirm the different nature of the two contexts. Legumes form a large portion of the crop remains in the Early Bronze Age Area L: Lathyrus sativus (grass pea), Vicia faba var. minor (faba bean), and Lens culinaris (lentil), all showing no drought stress and similar growing conditions in terms of moisture availability, as indicated by stable carbon isotope measurements. For Area L, several wild seeds have been identified to represent weeds of cereal crops, whereas Area DW is strongly affected by small wild seeds that entered the sediments as modern contaminants. Fruit crops are present in both assemblages with Olea europaea (olive), representing the most ubiquitous taxon, and Vitis vinifera (grape), with most of its pips found mineralized. The identified remains also include cereal crops, primarily Triticum dicoccum (emmer), which appears cultivated under exceptionally dry conditions. The stable nitrogen values for emmer also raised some questions regarding the growing location and cultivation strategy. Correspondence analysis has been applied, comparing the archaeobotanical assemblages of Tel Kabri within the wider geographical and chronological Levantine context and determining their placement in sub-regional patterns.

Spatial mismatch between wild bee diversity hotspots and protected areas - Joan Casanelles‐Abella; Simone Fontana; Eliane Meier; Marco Moretti; Betrand Fournier (Conservation Biology, 2023)
Wild bees are critical for multiple ecosystem functions but are currently threatened. Understanding the determinants of the spatial distribution of wild bee diversity is a major research gap for their conservation. We modeled wild bee α and β taxonomic and functional diversity in Switzerland to uncover countrywide diversity patterns and determine the extent to which they provide complementary information, assess the importance of the different drivers structuring wild bee diversity, identify hotspots of wild bee diversity, and determine the overlap between diversity hotspots and the network of protected areas. We used site‐level occurrence and trait data from 547 wild bee species across 3343 plots and calculated community attributes, including taxonomic diversity metrics, community mean trait values, and functional diversity metrics. We modeled their distribution with predictors describing gradients of climate, resource availability (vegetation), and anthropogenic influence (i.e., land‐use types and beekeeping intensity). Wild bee diversity changed along gradients of climate and resource availability; high‐elevation areas had lower functional and taxonomic α diversity, and xeric areas harbored more diverse bee communities. Functional and taxonomic β diversities diverged from this pattern, with high elevations hosting unique species and trait combinations. The proportion of diversity hotspots included in protected areas depended on the biodiversity facet, but most diversity hotspots occurred in unprotected land. Climate and resource availability gradients drove spatial patterns of wild bee diversity, resulting in lower overall diversity at higher elevations, but simultaneously greater taxonomic and functional uniqueness. This spatial mismatch among distinct biodiversity facets and the degree of overlap with protected areas is a challenge to wild bee conservation, especially in the face of global change, and calls for better integrating unprotected land. The application of spatial predictive models represents a valuable tool to aid the future development of protected areas and achieve wild bee conservation goals.

The ontogeny-specific thermal sensitivity of the seagrass Posidonia oceanica - Alessandro Rinaldi; Marco Martinez; Fabio Badalamenti; Giovanni D’Anna; Simone Mirto; Lazaro Marín-Guirao; Gabriele Procaccini; Valeria Montalto (Frontiers in Marine Science, 2023)
Introduction The rapid increase in sea-water temperatures and frequency of extreme thermal events have amplified the risk of functional extinction of Mediterranean species such as the endemic long-lived seagrass Posidonia oceanica . Because of the valuable ecological functions and ecosystem services the species provides, understanding the life-stage specific thermal vulnerability is crucial to accurately predict the consequences of current and future global climate change and to protect and conserve existing meadows. Methods To this end, here we report a study on the ontogeny-specific thermal sensitivity of important physiological functions (i.e. respiration and net production) of three different early life history stages of P. oceanica , namely seed, seedling (4-month-old individuals) and 16-month-old plantlet by measuring thermal performance curves (eleven temperatures treatments between 15-36°C with n=8). Results All three stages examined showed photosynthetic activity during light exposure with similar optimal temperatures for both net and gross production. Gross photosynthesis increased with rising temperature up to 28-30°C, subsequently declining at higher temperatures until complete inhibition at 36°C. The metabolic response of seeds was found to be temperature-dependent up to 26°C, while respiration of seedlings and plantlets was almost stable up to 28-30°C, but increased markedly at higher temperatures, resulting in a negative whole-plant C balance at temperatures above 32°C. Overall, our results show that seedlings and plantlets tolerate a wider temperature range (15 - 32°C) than seeds, which experience metabolic and physiological dysfunction from 26-28°C onwards. Discussion These findings suggest that the impact of warming on recruitment in P. oceanica meadows may vary depending on the timing of marine heatwaves (i.e. mid-spring to mid-autumn) and provide useful knowledge to inform restoration programs using early life stages of the species. In conclusion, the study of physiological responses during the early life stages of species is key to identify life history stages that are particularly vulnerable to climate change, which is vital knowledge for ecosystem management and conservation.

Co-exposure of iron oxide nanoparticles with glyphosate herbicides in Poecilia reticulata: Fish liver damages is reversible during iron accumulation and elimination period - João Marcos de Lima-Faria; Victória Costa da Silva; Lee Chen Chen; Diego Stéfani Teodoro Martinez; Simone Maria Teixeira de Sabóia-Morais (Chemosphere, 2023)

Vaginal temperature modeling in Holstein cows and cluster analysis by the cophenetic correlation coefficient - Marcos Vinícius da Silva; Héliton Pandorfi; Maria Simone Mendes Peixoto; José Antonio Delfino Barbosa Filho; Gledson Luiz Pontes de Almeida; Iran José Oliveira da Silva; Kenio Patrício Lima de Oliveira; Vinícius de Sena Sales Viana; José Francisco de Oliveira-Júnior; Cristiane Guiselini; Gabriel Thales Barboza Marinho; Marcio Mesquita; et al. (Journal of Thermal Biology, 2023)

MHC class II genes mediate susceptibility and resistance to coronavirus infections in bats - Dominik W. Schmid; Magdalena Meyer; Kerstin Wilhelm; Tatiana Tilley; Thomas Link‐Hessing; Ramona Fleischer; Ebenezer K. Badu; Evans Ewald Nkrumah; Samuel Kingsley Oppong; Nina Schwensow; Marco Tschapka; Heather J. Baldwin; et al. (Molecular Ecology, 2023)
Understanding the immunogenetic basis of coronavirus (CoV) susceptibility in major pathogen reservoirs, such as bats, is central to inferring their zoonotic potential. Members of the cryptic Hipposideros bat species complex differ in CoV susceptibility, but the underlying mechanisms remain unclear. The genes of the major histocompatibility complex (MHC) are the best understood genetic basis of pathogen resistance, and differences in MHC diversity are one possible reason for asymmetrical infection patterns among closely related species. Here, we aimed to link asymmetries in observed CoV (CoV‐229E, CoV‐2B and CoV‐2Bbasal) susceptibility to immunogenetic differences amongst four Hipposideros bat species. From the 2072 bats assigned to their respective species using the mtDNA cytochrome b gene, members of the most numerous and ubiquitous species, Hipposideros caffer D , were most infected with CoV‐229E and SARS‐related CoV‐2B. Using a subset of 569 bats, we determined that much of the existent allelic and functional (i.e. supertype) MHC DRB class II diversity originated from common ancestry. One MHC supertype shared amongst all species, ST12, was consistently linked to susceptibility with CoV‐229E, which is closely related to the common cold agent HCoV‐229E, and infected bats and those carrying ST12 had a lower body condition. The same MHC supertype was connected to resistance to CoV‐2B, and bats with ST12 were less likely be co‐infected with CoV‐229E and CoV‐2B. Our work suggests a role of immunogenetics in determining CoV susceptibility in bats. We advocate for the preservation of functional genetic and species diversity in reservoirs as a means of mitigating the risk of disease spillover.

Trait interactions effects on tropical tree demography depend on the environmental context - Vitor de A. Kamimura; Priscilla de P. Loiola; Carlos P. Carmona; Marco A. Assis; Carlos A. Joly; Flavio A.M. Santos; Simone A. Vieira; Luciana F. Alves; Valéria F. Martins; Eliana Ramos; Rafael F. Ramos; Francesco de Bello (Perspectives in Plant Ecology, Evolution and Systematics, 2023)

Resistance mechanisms of Hydrocotyle ranunculoides to Cr(VI): A biolfilter plant - Carolina Faccio Demarco; Daisa Hakbart Bonemann; Anderson Schwingel Ribeiro; Tito Roberto Sant’Anna Cadaval; Marcos Alexandre Gelesky; Marcelo Godinho; Maurízio Silveira Quadro; Simone Pieniz; Robson Andreazza (Journal of Cleaner Production, 2023)

Characterization of color, phenolic profile, and antioxidant activity of Italian pigmented rice varieties after different technological treatments - Francesca Colombo; Carola Cappa; Corinne Bani; Marco Magni; Simone Biella; Patrizia Restani; Chiara Di Lorenzo (Food Bioscience, 2023)

Ovaries of guppies (Poecilia reticulata) investigated in pre-embryonic, embryonic and post-embryonic stages after exposure to maghemite nanoparticles (y-Fe2O3) associated with Roundup® and glyphosate, followed by recovery period evaluation - Victória Costa da Silva; João Marcos de Lima-Faria; Lucas Nunes Guimarães; Matheus Santos Costa; Phâmella Neres de Lima; Karina Simões; Lázaro Wender Oliveira de Jesus; Simone Maria Teixeira de Sabóia-Morais (Environmental Toxicology and Pharmacology, 2023)

The role of grassland for erosion and flood mitigation in Europe: A meta-analysis - Filippo Milazzo; Richard M. Francksen; Laura Zavattaro; Mohamed Abdalla; Stanislav Hejduk; Simone Ravetto Enri; Marco Pittarello; Paul Newell Price; René L.M. Schils; Pete Smith; Tom Vanwalleghem (Agriculture, Ecosystems & Environment, 2023)

Myco-Barriers as Sustainable Tool for Port Seawater Decontamination from Metals - Grazia Cecchi; Laura Cutroneo; Simone Di Piazza; Ester Rosa; Mirca Zotti; Marco Capello (Journal of Marine Science and Engineering, 2023)
Several inputs of metal contamination can affect port seawater, such as industries and sludges. Despite the urge of developing new techniques to face this problem, most of the studies focus on traditional methods of remediation. Bioremediation by fungi represents an innovative and sustainable tool to efficiently remove metals from seawaters. The study’s aim is to develop a new green technology using fungi (myco-barriers) to maintain a good standard for water quality in port areas. A large commercial port (Port of Genoa) and a small marina (Port of Cavo) in Italy were chosen as pilot sites. Myco-barriers were realised by inoculating sterile straw and sawdust with mycelium of macro- and microfungi. After the incubation, myco-barriers were placed in the ports and sampled after 15 and 30 days to verify metal bioaccumulation. Myco-barriers with macrofungi showed the tendency to bioaccumulate more efficiently after 15 treatment days (Zn 7.0 mg kg−1, Cu 6.5 mg kg−1, Pb 1.2 mg kg−1), while myco-barriers with microfungi showed higher bioaccumulation after 30 days (Ni 0.6 mg kg−1, Pb 0.6 mg kg−1, Cu 5 mg kg−1). Results showed that myco-barriers have metal bioaccumulation potential and can represent a significant alternative to traditional techniques of remediation (chemical–physical).

Pedigree reconstruction and population structure using SNP markers in Gir cattle - Arielly Oliveira Garcia; Pamela Itajara Otto; Luiz Afonso Glatzl Junior; Renata de Fátima Bretanha Rocha; Mateus Guimarães dos Santos; Daniele Alves de Oliveira; Marcos Vinicius Gualberto Barbosa da Silva; João Cláudio do Carmo Panetto; Marco Antônio Machado; Rui da Silva Verneque; Simone Eliza Facioni Guimarães (Journal of Applied Genetics, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Sex-mediated changes in foraging behaviour according to breeding stage in a monomorphic seabird adapted to rural habitats - Davide Scridel; Lorenzo Serra; Simone Pirrello; Marco Basso; Alessandro Franzoi; Alberto Cardillo; Chiara Mengoni; Fausto Ramazzotti; Emiliano Verza; Simona Imperio; Jacopo G. Cecere (Animal Behaviour, 2023)

Architecture of active extensional faults in carbonates: Campo Felice and Monte D'Ocre faults, Italian Apennines - Luca Del Rio; Marco Moro; Simone Masoch; Fawzi Doumaz; Michele Saroli; Andrea Cavallo; Giulio Di Toro (Journal of Structural Geology, 2023)

Spatial non-stationarity in the distribution of fish species richness of tropical streams - Thiago Bernardi Vieira; Jorge Iván Sánchez-Botero; Danielle Sequeira Garcez; Sergio Maia Queiroz Lima; Carla Simone Pavanelli; Lilian Casatti; Welber Senteio Smith; Evanilde Benedito; Rosana Mazzoni; Paulo Santos Pompeu; Carlos Sérgio Agostinho; Luciano Fogaça de Assis Montag; et al. (Community Ecology, 2023)

Numerical Investigation into the Performance of an OWC Device under Regular and Irregular Waves - Giovanni Cannata; Marco Simone; Francesco Gallerano (Journal of Marine Science and Engineering, 2023)
A numerical investigation into the hydrodynamic efficiency of an oscillating water column (OWC) device for the production of energy from sea waves under the conditions of regular and irregular waves is proposed. The numerical simulations were carried out using a two-dimensional version of a recently published three-dimensional free-surface nonhydrostatic numerical model, which is based on a conservative form of the contravariant Navier–Stokes equations written for a moving co-ordinate system. The governing equations are spatially discretized by a finite volume shock-capturing scheme based on high-order wave-targeted essentially nonoscillatory reconstructions and an exact Riemann solver. Time discretization was performed by a predictor-corrector method that took into account the nonhydrostatic pressure component. The proposed numerical model allowed us to highlight the significant differences between the hydrodynamic efficiency obtained under irregular waves and those obtained under regular monochromatic waves and provides more realistic evaluations of the OWC device performances. The results of the above comparison showed a reduction in the hydrodynamic efficiency of the OWC from 0.78 to about 0.54 when passing from regular waves to the corresponding irregular ones. The model was applied to assess the potential energy production obtainable by a set of OWCs at the Cetraro harbor (southern Italy). The numerical results show that, by adopting the optimal dimensions of the OWC, the estimated mean annual energy production obtainable at the Cetraro harbor is equal to 1540.52 MWh, which corresponds to the energy production of about 10 wind turbines with a nominal power of 60 KW.

Aqueous extraction processing: An innovative and sustainable approach for recovery of unconventional oils - Guilherme Dallarmi Sorita; Simone Palma Favaro; Alan Ambrosi; Marco Di Luccio (Trends in Food Science & Technology, 2023)

The effect of age and FSH stimulation on the ovarian follicular response, nuclear maturation, and gene expression of cumulus-oocyte complexes in prepubertal gilts - Vivian Angélico Pereira Alfradique; Saullo Vinícius Pereira Alves; Domingos Lollobrigida Souza Netto; Andréia Ferreira Machado; Jurandy Mauro Penitente-Filho; Walmir da Silva; Felipe Zandonadi Brandão; Marcos Soares Lopes; Simone Eliza Facioni Guimarães (Theriogenology, 2023)

Strategies to improve the competitiveness of an agroindustrial system for a macauba based oil production in Minas Gerais State, Brazil - Pâmela da Costa Lima Pires; Aldara da Silva César; Alexandre Nunes Cardoso; Simone Palma Favaro; Marco Antonio Conejero (Land Use Policy, 2023)

Quality of Brazilian stingless bee honeys: Cephalotrigona capitata/mombucão and Melipona scutellaris Latrelle/uruçu - Flávia Izabely Nunes Moreira; Lorena Lucena de Medeiros; Leila Moreira de Carvalho; Lary Souza Olegario; Mércia de Sousa Galvão; Simone Alves Monteiro da Franca; Taliana Kênia Alencar Bezerra; Marcos dos Santos Lima; Marta Suely Madruga (Food Chemistry, 2023)

Developing a tactical nitrogen fertilizer management strategy for sustainable wheat production - Carolina Fabbri; Bruno Basso; Marco Napoli; Anna Dalla Marta; Simone Orlandini; Rafael A. Martinez-Feria (European Journal of Agronomy, 2023)

Testing the effect of sample prevalence and sampling methods on probability- and favourability-based SDMs - Elisa Marchetto; Daniele Da Re; Enrico Tordoni; Manuele Bazzichetto; Piero Zannini; Simone Celebrin; Ludovico Chieffallo; Marco Malavasi; Duccio Rocchini (Ecological Modelling, 2023)

Genomic and physiological characterization of Novosphingobium terrae sp. nov., an alphaproteobacterium isolated from Cerrado soil containing a mega-sized chromid - Aline Belmok; Felipe Marques de Almeida; Rodrigo Theodoro Rocha; Carla Simone Vizzotto; Marcos Rogério Tótola; Marcelo Henrique Soller Ramada; Ricardo Henrique Krüger; Cynthia Maria Kyaw; Georgios J. Pappas (Brazilian Journal of Microbiology, 2023)

Ecological linkages between biotechnologically relevant autochthonous microorganisms and phenolic compounds in sugar apple fruit (Annona squamosa L.) - Ali Zein Alabiden Tlais; Kalliopi Rantsiou; Pasquale Filannino; Luca Simone Cocolin; Ivana Cavoski; Marco Gobbetti; Raffaella Di Cagno (International Journal of Food Microbiology, 2023)

Identifying key parameters through a sensitivity analysis for realistic hygrothermal simulations at wall level supported by monitored data - Simone Panico; Marco Larcher; Valentina Marincioni; Alexandra Troi; Cristina Baglivo; Paolo Maria Congedo (Building and Environment, 2023)

Active breeding seabirds prospect alternative breeding colonies - Jelena Kralj; Aurore Ponchon; Daniel Oro; Barbara Amadesi; Juan Arizaga; Nicola Baccetti; Thierry Boulinier; Jacopo G. Cecere; Robin M. Corcoran; Anna-Marie Corman; Leonie Enners; Abram Fleishman; et al. (Oecologia, 2023)

Disentangling the role of soil bacterial diversity in phosphorus transformation in the maize rhizosphere - Yasmin Florentino Rodrigues; Fernando Dini Andreote; Antonio Marcos Miranda Silva; Armando Cavalcante Franco Dias; Rodrigo Gouvea Taketani; Simone Raposo Cotta (Applied Soil Ecology, 2023)

First report on classical biological control releases of the larval parasitoid Ganaspis brasiliensis against Drosophila suzukii in northern Italy - Lorenzo Fellin; Alberto Grassi; Simone Puppato; Alberto Saddi; Gianfranco Anfora; Claudio Ioriatti; Marco Valerio Rossi-Stacconi (BioControl, 2023)
Current management strategy of the invasive fruit fly Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) exploits different tools but relies mainly on chemical control. In the invaded areas, the local natural enemy community mostly consists of generalist pupal parasitoids unable to control the pest efficiently. Conversely, in the pest native area, there are more specialized sympatric larval parasitoids attacking D. suzukii . Following foreign explorations and quarantine risk assessments, the larval endoparasitoid Ganaspis brasiliensis (Ihering) (Hymenoptera: Figitidae) was selected as the best candidate for classical biological control programs. In 2021, the first ever propagative biocontrol program using a Japanese G1 lineage of G. brasiliensis started in Italy. Here we report the results of the first year of releases in the province of Trento (Northeast Italy), wherein G. brasiliensis was released in 12 locations. Pre- and post-release samplings on fresh and fallen fruits were performed around the release points to assess the recapture rate, the impact of the exotic parasitoid on D. suzukii and its potential interactions with local non-target species. After releases, G. brasiliensis was recovered at 50% of the locations. The exotic parasitoid only emerged from D. suzukii , mostly from fresh fruit still on the plant. Post-overwintering monitoring revealed the presence of a four G. brasiliensis individuals at two release locations.

Coupling Lagrangian simulation models and remote sensing to explore the environmental effect on larval growth rate: The Mediterranean case study of round sardinella (Sardinella aurita) early life stages - Marco Torri; Stefania Russo; Federico Falcini; Biagio De Luca; Simone Colella; Gianluca Volpe; Raffaele Corrado; Francesco Placenti; Luigi Giaramita; Marianna Musco; Tiziana Masullo; Carmelo Bennici; et al. (Frontiers in Marine Science, 2023)
The relationship between environmental conditions and early life-history traits of Sardinella aurita are investigated using material collected in two sites of the Central Mediterranean Sea. Individual mean daily growth during the planktonic phase has been determined by using otolith microstructure analysis, while Lagrangian simulation models allowed to estimate the daily position in space and time of each specimen from the hatching to the catch. Generalized Additive Mixed Models (GAMMs) have been implemented to explore the impact of environmental conditions at time t , t -1 day and t -2 days on the mean daily growth rate occurring at time t . Spatial analysis evidenced a wide dispersion of eggs and larvae in the coastal area of both sampling sites in correspondence to relatively warmer and chlorophyll-a enriched waters. Lagrangian simulations detected a complementary larval dispersal pathway able to transport larvae to a known retention area. Temperature at time t was the most important driver affecting the mean daily larval growth, followed by the food availability. On the other hand, models performed on lagged environmental covariates ( t -1 and t -2) did not show any significant effect on the growth rate at time t . In addition to the sub-linear positive correlation between temperature and mean daily larval growth, model highlighted a decrease in the otolith core width at higher temperature that can be linked to an earlier stage of ontogeny at hatching. This study provided a useful methodological approach that takes advantage of available remote sensing data to perform ecological studies in support to fisheries management.

Biomass-powered thermal weeding in wine farms: An environmental and economic assessment - Nicolò Morselli; Simone Boccaletti; Stefano Meglioraldi; Marco Puglia; Simone Pedrazzi; Giulio Allesina (Journal of Cleaner Production, 2023)

Food waste between environmental education, peers, and family influence. Insights from primary school students in Northern Italy - Simone Piras; Simone Righi; Federico Banchelli; Claudia Giordano; Marco Setti (Journal of Cleaner Production, 2023)

Pre-emergent bioherbicide potential of Schinus terebinthifolia Raddi essential oil nanoemulsion for Urochloa brizantha - Simone Y. Fernandes; Débora de Araújo; Montcharles S. Pontes; Jaqueline S. Santos; Claudia A.L. Cardoso; Euclésio Simionatto; Marco A.U. Martines; Débora R. Antunes; Renato Grillo; Gilberto J. Arruda; Etenaldo F. Santiago (Biocatalysis and Agricultural Biotechnology, 2023)

Plant species selection and impact on tree resprouts by semi-free ranging pigs in a temperate deciduous forest - Ginevra Nota; Roberta Berretti; Davide Ascoli; Davide Barberis; Simone Ravetto Enri; Marco Pittarello; Renzo Motta; Luca Maria Battaglini; Giampiero Lombardi; Michele Lonati (Agroforestry Systems, 2023)
Silvopastoral systems with grazing pigs are mainly concentrated in Mediterranean regions, for instance in Iberian dehesas and montados . Conversely, in European deciduous forests, outdoor pig farming has almost disappeared, despite it could provide several environmental and socioeconomic benefits. For instance, pig grazing could be used for habitat restoration and conservation, while providing high quality meat products and promoting local breeds. In this study, we investigated (i) the plant species selection and (ii) the impact on tree resprouts (after a silvicultural cut) by semi-free ranging pigs in a degraded oak temperate forest in Northwestern Italy. We monitored pigs foraging behavior by direct observations and discriminated the plant species into three groups: preferred, indifferently consumed and avoided plants. The impact on the resprouts of six tree species was assessed by modeling the percentage of damaged shoots and their height through time using Generalized Linear and Additive Mixed Models. Swine expressed a selective foraging behavior, which was likely influenced by the forage quality and toxicity of plant species. The leaves and resprouts of Corylus avellana and Castanea sativa were highly consumed, whereas Acer and Quercus species and Fraxinus ornus were avoided. Mature leaves of Robinia pseudoacacia were highly preferred while its young resprouts were only slightly impacted, suggesting that pig grazing may not be effective to control this alien invasive species. Contrarily, pigs consumed Rubus sp. abundantly, suggesting they could be used to clear the understory in degraded forests.

Agricultural resources in the Bronze Age city of Tel Lachish - Marco Nicolì; Simone Riehl; Lyndelle Webster; Katharina Streit; Felix Höflmayer (Vegetation History and Archaeobotany, 2022)
In this paper, we present the results of the plant macrofossil analyses from the site of Tel Lachish, Israel with focus on the botanical assemblage of the Middle and Late Bronze Age layers collected in two different areas of the tell: Area S, a trench on the western edge of the site, whose samples belong to Late Bronze Age deposits, and Area P, the palace area on the top of the mound with samples ranging from the Middle to Late Bronze Age. Systematic sampling of these areas and analysis of the remains have extended our knowledge of the agricultural resources of one of the most influential Late Bronze Age cities in the southern Levant. Multivariate statistics have been applied to gain insight into regional patterns of crop growing. Fruit crops account for the majority of the identified remains from this site, which also included large quantities of Hordeum vulgare (barley) and Triticum dicoccum (emmer wheat) grains. The virtual lack of chaff remains is not solely a matter of preservation, since the Late Bronze Age assemblage preserved fragile small seeds. Rather, this finding suggests that cereal processing took place some distance from the area of deposition. Overall high diversity, ubiquity and proportions of fruit crops indicate that these played a fundamental role in their cultivation and probably also in cultural life at Lachish throughout the 15th–12th centuries bce .

First evidence of population genetic structure of the deep-water blackmouth catshark Galeus melastomus Rafinesque, 1810 - Simone Di Crescenzo; Alice Ferrari; Claudio Barría; Rita Cannas; Alessia Cariani; Jim Drewery; Lourdes Fernández-Peralta; Daniela Giordano; Manuel Hidalgo; Vasiliki Kousteni; Ilaria Anna Maria Marino; Daniela Massi; et al. (Frontiers in Marine Science, 2022)
Among the main measures adopted to reduce anthropogenic impacts on elasmobranch communities, understanding the ecology of deep-sea sharks is of paramount importance, especially for potentially vulnerable species highly represented in the bycatch composition of commercial fisheries such as the blackmouth catshark Galeus melastomus . In the present work, we unravelled the first indication of population genetic structure of G. melastomus by using a novel and effective panel of nuclear, and polymorphic DNA markers and compared our results with previous findings supporting high genetic connectivity at large spatial scales. Given the lack of species-specific nuclear markers, a total of 129 microsatellite loci (Simple Sequence Repeats, SSRs) were cross-amplified on blackmouth catshark specimens collected in eight geographically distant areas in the Mediterranean Sea and North-eastern Atlantic Ocean. A total of 13 SSRs were finally selected for genotyping, based on which the species exhibited signs of weak, but tangible genetic structure. The clearcut evidence of genetic differentiation of G. melastomus from Scottish waters from the rest of the population samples was defined, indicating that the species is genetically structured in the Mediterranean Sea and adjacent North-eastern Atlantic. Both individual and frequency-based analyses identified a genetic unit formed by the individuals collected in the Tyrrhenian Sea and the Strait of Sicily, distinguished from the rest of the Mediterranean and Portuguese samples. In addition, Bayesian analyses resolved a certain degree of separation of the easternmost Aegean sample and the admixed nature of the other Mediterranean and the Portuguese samples. Here, our results supported the hypothesis that the interaction between the ecology and biology of the species and abiotic drivers such as water circulations, temperature and bathymetry may affect the dispersion of G. melastomus , adding new information to the current knowledge of the connectivity of this deep-water species and providing powerful tools for estimating its response to anthropogenic impacts.

Displacement Effects of Conservation Grazing on Red Deer (Cervus elaphus) Spatial Behaviour - Fabio Weiss; Frank Uwe Michler; Benjamin Gillich; Jörg Tillmann; Simone Ciuti; Marco Heurich; Siegfried Rieger (Environmental Management, 2022)
Conservation grazing uses semi-feral or domesticated herbivores to limit encroachment in open areas and to promote biodiversity. However, we are still unaware of its effects on wild herbivores. This study investigates the influence of herded sheep and goats on red deer ( Cervus elaphus ) spatial behavior by testing three a-priori hypotheses: (i) red deer are expected to avoid areas used by livestock, as well as adjacent areas, when livestock are present, albeit (ii) red deer increase the use of these areas when sheep and goats are temporarily absent and (iii) there is a time-lagged disruption in red deer spatial behavior when conservation grazing practice ends. Using GPS-telemetry data on red deer from a German heathland area, we modelled their use of areas grazed by sheep and goats, using mixed-effect logistic regression. Additionally, we developed seasonal resource selection functions (use-availability design) to depict habitat selection by red deer before, during, and after conservation grazing. Red deer used areas less during conservation grazing throughout all times of the day and there was no compensatory use during nighttime. This effect mostly persisted within 21 days after conservation grazing. Effects on habitat selection of red deer were detectable up to 3000 meters away from the conservation grazing sites, with no signs of either habituation or adaption. For the first time, we demonstrate that conservation grazing can affect the spatio-temporal behavior of wild herbivores. Our findings are relevant for optimizing landscape and wildlife management when conservation grazing is used in areas where wild herbivores are present.

From inshore to offshore: distribution of microplastics in three Italian seawaters - Alice Sbrana; Tommaso Valente; Jessica Bianchi; Simone Franceschini; Raffaella Piermarini; Flavia Saccomandi; Andrea Giuseppe de Lucia; Andrea Camedda; Marco Matiddi; Cecilia Silvestri (Environmental Science and Pollution Research, 2022)
A comprehensive understanding of the concentration of microplastics (MPs) in seawaters is essential to implement monitoring programs and understand the impacts on ecosystems, as required by the European legislation to protect the marine environment. In this context, the purpose of this study is to investigate the composition, quantity, and spatial distribution of microplastics from coastal to offshore areas in three Italian seawaters. In addition, the distribution of microplastics between surface and subsurface water layers was analyzed in order to better understand the dynamics of MPs in the upper layers of the water column. A total number of 6069 MPs (mean total concentration of 0.029 microplastics · m −2 ) were found to be heterogeneous in type, shape, and color. In general, MPs concentrations decrease with coastal distance, except when environmental forcings are predominant (such as sea currents). Moreover, the amount of surface MPs was almost four times that of subsurface microplastics, which consisted mostly of fibers. In light of these results, it becomes clear how critical it is to plan remediation actions and programs to minimize microplastic accumulations in the sea.

Plasticity of the Anemonia viridis microbiota in response to different levels of combined anthropogenic and environmental stresses - Giorgia Palladino; Simone Rampelli; Carles Galià-Camps; Daniel Scicchitano; Giulia Trapella; Enrico Nanetti; Valeria Angelini; Daniela Cleo; Silvia Turroni; Cinzia Corinaldesi; Marco Candela (Frontiers in Marine Science, 2022)
Despite their recognized primary importance, marine coastal ecosystems around the globe are currently under threat, being subject to continuous local and global anthropogenic stressors. In this frame, understanding the response of coastal habitat-forming species to multiple stressors and their resilience is fundamental for the sustainable management of coastal ecosystems. In the present study, to provide some glimpses in this direction, we explored the response of the Anemonia viridis -associated microbiota to the combined anthropogenic stressors, which typically affect touristic hotspots at Mediterranean coastal sites. To this aim, two case studies have been carried out, the first in the Riccione coastal site (Italy, Center Mediterranean) and the second at Cap de Creus (Spain, North-western Mediterranean), where the A. viridis microbiota was assessed under the conditions of both high and low anthropogenic pressure. According to our findings, the A. viridis microbiota showed a relevant degree of plasticity in response to combined anthropogenic and environmental stressors, with changes that also mirrored variations in the surrounding seawater, thus indicating a close connection with the environment, from which potential symbiotic partners are selected. However, this potentially adaptive process also has a limitation, as observed in the highly anthropogenic impact site of Cap de Creus, where A. viridis -associated microbiota appeared completely unstructured, as demonstrated by an increased dispersion according to the Anna Karenina principle. This raises the question about the resilience of the A. viridis -associated microbiota under combined climate and anthropogenic threats, as well as of the anthropogenic factors driving the observed dysbiosis changes.

Thermophilic Hydrocarbon-Utilizing Bacilli from Marine Shallow Hydrothermal Vents as Producers of Biosurfactants - Vincenzo Zammuto; Antonio Spanò; Marco Sebastiano Nicolò; Emanuela Grillo; Maria Teresa Caccamo; Salvatore Magazù; Simone Cappello; Concetta Gugliandolo (Journal of Marine Science and Engineering, 2022)
The exploitation of thermophilic hydrocarbon-utilizing bacilli could provide novel environmentally friendly surfactants. In this work, 80 thermophilic bacilli isolated from shallow hydrothermal vents of the Eolian Islands (Italy) were screened for their ability to utilize hydrocarbons and produce biosurfactants (BSs). Among them, 15 strains grew with kerosene or gasoline (2% v/v) as the only carbon and energy source, and most of them were positive to the methylene blue agar as prescreening assay for BSs production and displayed emulsifying activity. The cell-free supernatants (CFSs) from two selected strains, Bacillus licheniformis B3-15 and Bacillus horneckiae SBP3, were both surface active and able to emulsify different hydrocarbons and vegetable oils. BSs from B3-15 (910 mg L−1) and SBP3 (950 mg L−1) were chemically different surfactin-like lipopeptides, with specific mineral-, castor- and crude oil removal ability from the cotton matrix. CFSs from the 15 thermophilic strains, which harbor both lipolytic and surfactant abilities, could be suitable for industrial-based applications and environmental issues, such as oil recovery and removal from polluted areas or surfaces, (e.g., oil pipelines, bilge tankers, or industrial silos), whereas the crude BSs, as high-value compounds, may be used in different fields of application, as detergent, cosmeceutical, and pharmaceutical industries.

Impacts of the invasive hornet Vespa velutina on native wasp species: a first effort to understand population-level effects in an invaded area of Europe - Luca Carisio; Jacopo Cerri; Simone Lioy; Ettore Bianchi; Sandro Bertolino; Marco Porporato (Journal of Insect Conservation, 2022)
Invasive alien species could generate a multitude of impacts towards native species. The introduction and spread of Vespa velutina in Europe is raising concern for the conservation of insect’s biodiversity, including wasps due to predation, competition or a combination of these two mechanisms. Nevertheless, most evidence for negative effects on other wasps are based on laboratory experiments, direct observations, and on considerations about the biology and ecology of Vespidae. No field study in Europe explored how the abundance of V. velutina could affect the population of native Vespidae, as expected in case of competition and predation. We analysed how the abundance of V. velutina influenced that of Vespa crabro , 4 years after the arrival and establishment of V. velutina in our study area, in Italy. Moreover, we compared the abundances of three native Vespidae ( V. crabro , Vespula vulgaris , Vespula germanica ), between our study area and an adjacent uninvaded area with similar environmental conditions. Bayesian Generalized Linear Models revealed that the abundance of V. velutina and V. crabro was positively associated, where V. velutina was scarce. Covariation disappeared only at those trapping sites where V. velutina was extremely abundant. Moreover, abundances of native wasps were similar between the invaded and the uninvaded areas. Implications for insect conservation The wide-scale monitoring activity performed to investigate the effects of V. velutina on native wasps has not detected any negative effects in relation to the presence of the invasive species. More effort is however requested for understanding if V. velutina could really affect native Vespidae at the population-level.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Ask the shark: blackmouth catshark (Galeus melastomus) as a sentinel of plastic waste on the seabed - Alice Sbrana; Alessandro Cau; Davide Cicala; Simone Franceschini; Tommaso Giarrizzo; Maria Flavia Gravina; Alessandro Ligas; Giulia Maiello; Marco Matiddi; Antonio Parisi; Paolo Sartor; Mario Sbrana; et al. (Marine Biology, 2022)
The presence of plastic waste in the marine environment has driven the scientific community to make significant efforts to study and mitigate its possible effects. One of the critical aspects is to determine if and how an increase in ingestion events may occur as a result of the accumulation of plastic waste on the seabed. In this study, G. melastomus is examined for its ability to indirectly provide information on the amount of macroplastics accumulating on the seafloor. Plastic ingestion is explored by describing the feeding habits of the species, which have the potential to provide very useful information regarding biological or ecological issues. The diet of G. melastomus mainly consisted of cephalopods, bathypelagic fishes, and decapod crustaceans, increasing in diversity during growth. The generalist-opportunistic feeding behaviour of this species leads to the incidental ingestion of plastic particles ( N = 47, with a mean (± SD) of 1.47 ± 0.28 per specimen) which can be indirectly associated to the presence of macroplastics on the seafloor. Indeed, our results indicate a significant relationship between the amount of macroplastics present on the seabed and the frequency of ingestion of plastic particles by blackmouth catshark. We propose G. melastomus as an excellent candidate for developing a valid monitoring strategy for the presence of plastics on the seabed, as requested by the EU Marine Strategy Framework Directive.

Livestock displace European mouflon from optimal foraging sites - Francesca Brivio; Simone Ciuti; Anna Pipia; Stefano Grignolio; Marco Apollonio (European Journal of Wildlife Research, 2022)
The conflict between free-ranging livestock and wildlife is a serious conservation concern across rural communities worldwide. Livestock may affect wild herbivores via direct competition for resources due to spatial and diet overlap or via behavioural interference. It is imperative that we disentangle the effects of livestock on wildlife behaviour to obtain an empirical basis able to stir management and conservation decisions. Here, we studied the effect of livestock presence on the habitat selection in a free-ranging European mouflon ( Ovis aries musimon ) population in Sardinia, where the species is under strict protection. We collected spatial data on mouflon and livestock during two consecutive years to investigate whether the mouflon selection of key feeding grassland sites was negatively impacted by the livestock presence. We found that mouflon preferably selected grassland, and its selection significantly increased when grass was of better quality (greener). We showed that livestock presence led to the displacement of mouflon from such preferred feeding sites, an effect clearly exacerbated by livestock proximity. We indeed found that the selection of grassland by mouflon dropped significantly when the distance between livestock and mouflon was below ~ 650 m, providing a useful management threshold indication. Livestock presence in close proximity displaced mouflon to sub-optimal habitat, and its effects may have negative impact on the population dynamic of this species which is already characterized by low female productivity within harsh Mediterranean environment. Our results give clear management indications aimed at better managing livestock grazing within natural areas to ultimately improve wildlife conservation.

Interaction between MHC diversity and constitution, gut microbiota and Astrovirus infections in a neotropical bat - Ramona Fleischer; Dominik W. Schmid; Wasimuddin; Stefan D. Brändel; Andrea Rasche; Victor M. Corman; Christian Drosten; Marco Tschapka; Simone Sommer (Molecular Ecology, 2022)
Astroviruses (AstVs) infect numerous mammalian species including reservoirs such as bats. Peptides encoded by the genes of the highly polymorphic Major Histocompatibility Complex (MHC) form the first line of host defence against pathogens. Aside from direct involvement in mounting adaptive immune responses, MHC class II genes are hypothesized to regulate gut commensal diversity and shape the production of immune‐modulatory substances by microbes, indirectly affecting host susceptibility. Despite initial empirical evidence for the link between host MHC and the microbiota, associations among these factors remain largely unknown. To fill this gap, we examined MHC allelic diversity and constitution, the gut bacterial community and abundance pattern of a wild population of a neotropical bat ( Artibeus jamaicensis ) challenged by AstV infections. First, we show an age‐dependent relationship between the host MHC class II diversity and constitution and the gut microbiota in AstV‐uninfected bats. Crucially, these associations changed in AstV‐infected bats. Additionally, we identify changes in the abundance of specific bacterial taxa linked to the presence of certain MHC supertypes and AstV infection. We suggest changes in the microbiota to be either a result of AstV infection or the MHC‐mediated modulation of microbial communities. The latter could subsequently affect microbe‐mediated immunity and resistance against AstV infection. Our results emphasize that the reciprocal nature of host immune genetics, gut microbial diversity and pathogen infection require attention, which are particularly important given their repercussions for disease susceptibility and severity in wild animal populations with a history of zoonotic spillover and frequent human contact.

Assessing the Image Concept Drift at the OBSEA Coastal Underwater Cabled Observatory - Ennio Ottaviani; Marco Francescangeli; Nikolla Gjeci; Joaquin del Rio Fernandez; Jacopo Aguzzi; Simone Marini (Frontiers in Marine Science, 2022)
The marine science community is engaged in the exploration and monitoring of biodiversity dynamics, with a special interest for understanding the ecosystem functioning and for tracking the growing anthropogenic impacts. The accurate monitoring of marine ecosystems requires the development of innovative and effective technological solutions to allow a remote and continuous collection of data. Cabled fixed observatories, equipped with camera systems and multiparametric sensors, allow for a non-invasive acquisition of valuable datasets, at a high-frequency rate and for periods extended in time. When large collections of visual data are acquired, the implementation of automated intelligent services is mandatory to automatically extract the relevant biological information from the gathered data. Nevertheless, the automated detection and classification of streamed visual data suffer from the “concept drift” phenomenon, consisting of a drop of performance over the time, mainly caused by the dynamic variation of the acquisition conditions. This work quantifies the degradation of the fish detection and classification performance on an image dataset acquired at the OBSEA cabled video-observatory over a one-year period and finally discusses the methodological solutions needed to implement an effective automated classification service operating in real time.

Reef complexity influences distribution and habitat choice of the corallivorous seastar Culcita schmideliana in the Maldives - Enrico Montalbetti; Luca Fallati; Marco Casartelli; Davide Maggioni; Simone Montano; Paolo Galli; Davide Seveso (Coral Reefs, 2022)
The cushion seastar Culcita schmideliana has gained major attention in the last few years because of its selective predation on juvenile corals, as well as its ability to generate large demographic assemblages, causing delays in coral recovery after large mortality events in the Republic of Maldives. However, a lack of data regarding the factors affecting its distribution and habitat selection still persists in this area. Here, we adopted a novel approach in the study of corallivorous seastar habitat selection that combined ecological and digital photogrammetry data. In this regard, we tested 3 different parameters as factors influencing seastar habitat choice in the South-East region of Faafu Atoll, Republic of Maldives, namely prey abundance, Linear Rugosity Index (LRI), and Average Slope (AS). The analysis of selectivity coefficient (Ei) of seastars for different habitat types showed a preference for reefs characterized by medium AS values (Ei = 0.268), a LRI included between 2 and 2.5 (Ei = 0.180), and a juvenile coral density ranging between 10 and 20 colonies m −2 (Ei = 0.154). A multiple linear regression analysis showed that different AS and LRI values explained the 43.1% ( R 2 = 0.431, P = 0.007) and the 48.1% ( R 2 = 0.481, P = 0.024) of variance in seastars abundance, respectively, while juvenile coral densities did not significantly affect this ( R 2 = 0.132, P = 0.202). These results provide new information on the distribution and behaviour of an important corallivore of Maldivian reefs, such as C. schmideliana .

Conservation by trans-border cooperation: population genetic structure and diversity of geoffroy’s bat (Myotis emarginatus) at its north-western european range edge - Alain C. Frantz; Andrea Viglino; Elodie Wilwert; Ana-Paula Cruz; Julian Wittische; Alexander M. Weigand; Jacky Buijk; Pierrette Nyssen; Daan Dekeukeleire; Jasja J.A. Dekker; Gavin J. Horsburgh; Simone Schneider; et al. (Biodiversity and Conservation, 2022)
In the European Union, all bat species are strictly protected and member states must ensure their conservation. However, if populations are genetically structured, conservation units that correspond to whole countries may be too large, putting small populations with specific conservation requirements at risk. Geoffroy’s bat ( Myotis emarginatus ) has undergone well-documented declines at its north-western European range edge between the 1960 and 1990s and is considered to be negatively affected by habitat fragmentation. Here we analysed the species’ genetic population structure and diversity to identify subpopulations with reduced genetic diversity and to scientifically inform conservation management. We generated 811 microsatellite-based genetic profiles obtained from 42 European nursery colonies and analysed a total of 932 sequences of the hypervariable region II of the mitochondrial control region sampled from across Europe. While two geographically widespread genetic populations were inferred to be present in north-western Europe, both nuclear and mitochondrial genetic diversity were lowest in the areas that had experienced a decline during the last century. A microsatellite-based analysis of demographic history did not permit, however, to unequivocally link that reduced genetic diversity to the population contraction event. Given the large geographic extent of the genetic populations, preserving the connectivity of mating sites requires concerted conservation efforts across multiple political jurisdictions. Genetic monitoring ought to be done on a regular basis to ensure that large-scale connectivity is maintained and further loss of genetic diversity is prevented.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Treatment of cosmetic industry wastewater by flotation with Moringa oleifera Lam. and aluminum sulfate and toxicity assessment of the treated wastewater - Nathalia Santos Araújo; Nathália Ferreira Souza; João Marcos de Lima-Faria; Andressa Tuane Santana Paz; Paulo Sérgio Scalize; Simone Maria Teixeira de Sabóia-Morais; Humberto Carlos Ruggeri Junior; Edemilson Cardoso da Conceição (Environmental Science and Pollution Research, 2022)

Plastic and Us: looking at the marine litter problem from inside the rubbish. An unusual temporary exhibition at the Natural History Museum of the University of Pisa - SILVIA MERLINO; MARINA LOCRITANI; SIMONE FARINA; CHIARA SORBINI; SILVIA BATTAGLINI; MARCO DELLACASA; PATRIZIA SCAGLIA; DAMIANO MARCHI; ELENA BONACCORSI (Mediterranean Marine Science, 2021)
In this paper, we will describe a temporary exhibition held at the Museo di Storia Naturale dell’Università di Pisa (Natural History Museum of the University of Pisa, hereafter MSN), Italy, in year 2020-2021, and the educational and awareness raising results that the proposed approach has produced. The aim of this exhibition was to guide the visitor along a path of awareness on the very topical issue of “plastic in our environment”. It focused not only on the environmental impact produced by the dispersal of anthropogenic plastic waste, especially in the sea, but also on the awareness of what actions need to be taken, both on a governmental and personal level, by each of us, to limit it in the future. The exhibition started from the data and images proposed by the media, which shocked us with the seriousness of the plastic emergency and triggered worldwide attention. Then the emphasis of the exhibition shifted to scientific data, rigorously presented by researchers who study the issue directly in the field, in the Mediterranean Sea and along its coasts. Finally, the last exhibits addressed the issue of plastic disposal, inviting visitors to check their real knowledge about the concepts of degradable, compostable, or recyclable plastic, and to reflect on what could be the most effective means to limit plastic problems in the future. The plastic problem is exquisitely anthropogenic, and the exhibit was designed to make visitors feel involved. The mismanagement of the lifecycle of this material (from manufacturing processes to products’ end life) can be addressed on a global scale by drastically reducing the use and production of single-use plastic items, promoting proper waste management, and improving the effectiveness of recycling. The exhibition message was that laws are essential, as well as calling plastic producers to their responsibility, but something can also be done locally by us as individuals, through proper disposal and by producing less single-use plastic waste. Visitors' attitudes and knowledge on this topic were investigated through online questionnaires prepared by experts in the field, and the data collected are presented and discussed in this paper.

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Conservation status of the Italian flora under the 92/43/EEC ‘Habitats’ Directive - Giuseppe Fenu; Consolata Siniscalco; Gianluigi Bacchetta; Donatella Cogoni; Maria Silvia Pinna; Marco Sarigu; Thomas Abeli; Elena Barni; Fabrizio Bartolucci; Daniela Bouvet; Annalena Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

Reconciling trait based perspectives along a trait‐integration continuum - Simone Fontana; Sergio Rasmann; Francesco de Bello; Francesco Pomati; Marco Moretti (Ecology, 2021)
Trait based ecology has developed fast in the last decades, aiming to both explain mechanisms of community assembly, and predict patterns in nature, such as the effects of biodiversity shifts on key ecosystem processes. This body of work has stimulated the development of several conceptual frameworks and analytical methods, as well as the production of trait databases covering a growing number of taxa and organizational levels (from individuals to guilds). However, this breeding ground of novel concepts and tools currently lacks a general and coherent framework, under which functional traits can help ecologists organize their research aims, and serve as the common currency to unify several scientific disciplines. Specifically, we see a need to bridge the gaps between community ecology, ecosystem ecology, and evolutionary biology, in order to address the most pressing environmental issues of our time. To achieve this integration goal, we define a trait‐integration continuum, which reconciles alternative trait definitions and approaches in ecology. This continuum outlines a coherent progression of biological scales, along which traits interact and hierarchically integrate from genetic information, to whole organism fitness‐related traits, to trait syndromes and functional groups. Our conceptual scheme proposes that lower‐level trait integration is closer to the inference of ecoevolutionary mechanisms determining population and community properties, whereas higher‐level trait integration is most suited to the prediction of ecosystem processes. Within these two extremes, trait integration varies on a continuous scale, which relates directly to the inductive‐deductive loop that should characterize the scientific method. With our proposed framework, we aim to facilitate scientists in contextualising their research based on the trait‐integration levels that matter most to their specific goals. Explicitly acknowledging the existence of a trait‐integration continuum is a promising way for framing the appropriate questions, thus obtaining reliable answers and results that are comparable across studies and disciplines.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Can we replace observed forcing with weather generator in land surface modeling? Insights from long-term simulations at two contrasting boreal sites - Marco Alves; Daniel F. Nadeau; Biljana Music; François Anctil; Simone Fatichi (Theoretical and Applied Climatology, 2021)

Trophic, Chemo-Ecological and Sex-Specific Insights on the Relation Between Diplodus sargus (Linnaeus, 1758) and the Invasive Caulerpa cylindracea (Sonder, 1845) - Andrea Miccoli; Emanuele Mancini; Marco Boschi; Francesca Provenza; Veronica Lelli; Francesco Tiralongo; Monia Renzi; Antonio Terlizzi; Simone Bonamano; Marco Marcelli (Frontiers in Marine Science, 2021)
Biological invasions result in negative and unpredictable impacts on oceans worldwide. Non-indigenous macrophytes often synthesize secondary metabolites for defensive purposes and increased competition efficiency: this is the case of Caulerpa cylindracea , which has entered the Mediterranean Sea in 1990 and competed against local flora and fauna since. It was demonstrated that the white seabream Diplodus sargus (i) has included the algae into its diet, (ii) is subject to the peculiar Abnormally Tough Specimen (ATS) condition post-cooking, and (iii) suffers physiological and behavioral disturbances from caulerpin, one of the three major algal secondary metabolites. This paper confirms a feeding relationship between the fish and the algae, quantifies caulerpin accumulation in the liver, suggests a possible mollusk- and echinoderm-driven biomagnification, and highlights the fact that all ATS specimens were males. Multivariate analyses on a multi-biomarker panel reveals differential correlations to key cellular processes such as oxidative stress, metabolism, neurotoxicity, and lipid peroxidation as well as to condition indexes.

Serum N-glycan profiles differ for various breast cancer subtypes - Gerda C. M. Vreeker; Kiki M. H. Vangangelt; Marco R. Bladergroen; Simone Nicolardi; Wilma E. Mesker; Manfred Wuhrer; Yuri E. M van der Burgt; Rob A. E. M. Tollenaar (Glycoconjugate Journal, 2021)
Breast cancer is the most prevalent cancer in women. Early detection of this disease improves survival and therefore population screenings, based on mammography, are performed. However, the sensitivity of this screening modality is not optimal and new screening methods, such as blood tests, are being explored. Most of the analyses that aim for early detection focus on proteins in the bloodstream. In this study, the biomarker potential of total serum N -glycosylation analysis was explored with regard to detection of breast cancer. In an age-matched case-control setup serum protein N -glycan profiles from 145 breast cancer patients were compared to those from 171 healthy individuals. N -glycans were enzymatically released, chemically derivatized to preserve linkage-specificity of sialic acids and characterized by high resolution mass spectrometry. Logistic regression analysis was used to evaluate associations of specific N -glycan structures as well as N -glycosylation traits with breast cancer. In a case-control comparison three associations were found, namely a lower level of a two triantennary glycans and a higher level of one tetraantennary glycan in cancer patients. Of note, various other N -glycomic signatures that had previously been reported were not replicated in the current cohort. It was further evaluated whether the lack of replication of breast cancer N -glycomic signatures could be partly explained by the heterogenous character of the disease since the studies performed so far were based on cohorts that included diverging subtypes in different numbers. It was found that serum N -glycan profiles differed for the various cancer subtypes that were analyzed in this study.

Smoking-related cue reactivity in a virtual reality setting: association between craving and EEG measures - Stefano Tamburin; Denise Dal Lago; Federica Armani; Marco Turatti; Riccardo Saccà; Simone Campagnari; Cristiano Chiamulera (Psychopharmacology, 2021)
Background Cue-reactivity is the array of responses that smokers exhibit when exposed to conditioned and contextual stimuli previously associated to substance use. The difficulty to experimentally recreate the complexity of smokers’ spatial experience and context requires more ecological models. Virtual reality (VR) creates a state of immersion close to reality allowing controlled assessments of behavioral responses. To date, no studies investigated brain activation associated to smoking cue-reactivity in VR using electroencephalography (EEG). Aims To investigate whether a VR cue-reactivity paradigm (a) may increase smoking craving, (b) is feasible with EEG recording, and (c) induces craving levels associated to EEG desynchronization. Methods Smokers ( N = 20) and non-smokers ( N = 20) were exposed to neutral and smoking-related VR scenarios, without and with smoking conditioned stimuli, respectively. EEG was recorded from occipital and parietal leads throughout the sessions to assess alpha band desynchronization. Smoking and food craving and presence visual analogue scales (VAS) were assessed during the session. Results To be smoker, but not non-smoker, significantly influenced smoking craving VAS induced by smoking cue VR but not by neutral VR. No significant food craving changes was observed during the VR sessions. The new finding was that EEG alpha band power in posterior leads was significantly increased by the smoking context scenario only in smokers, and that the degree of smoking (i.e., heavy vs. light) was significantly associated to this neurophysiological measure. Conclusions This study demonstrated, for the first time, the feasibility of EEG recording in a VR setting, suggesting that EEG desynchronization may be a neurophysiological marker of smoking cue-reactivity.

Subjective resource value affects aggressive behavior independently of resource-holding-potential and color morphs in male common wall lizard - Roberto Sacchi; Alan J. Coladonato; Mara Battaiola; Carlotta Pasquariello; Simone Buratti; Cristian Matellini; Marco Mangiacotti; Stefano Scali; Marco A. L. Zuffi (Journal of Ethology, 2021)
Game theory models predict the outcome of a dyadic contest to depend on opponents’ asymmetries in three main traits: resource-holding potential (RHP), resource value (RV) and aggressiveness. Using male common wall lizards Podarcis muralis , a polymorphic species showing three discrete morphs (white, yellow, and red), we investigated how the aggressive behavior varies according to a change in subjective RV and color morphs, while controlling for the asymmetry in RHP (using mirrors). By comparing the aggression of the same individual towards its mirror image in two different arenas (familiar = high subjective RV; novel = low subjective RV), we showed that lizard aggressive behavior was more intense and prolonged in the familiar arena than in the new one, thus supporting the occurrence of a direct relationship between motivation and aggression in this species. We also found the overall aggressiveness to differ from individual to individual, supporting the general hypothesis that aggressiveness is a trait associated with personality. By contrast, no effect of morphs was detected, ruling out the occurrence of morph specific variation in the aggressiveness. Our results highlight that an individual’s motivation and personality might be as important as RHP and RV in the resolution of animal contests.

Trace-metal distribution and ecological risk assessment in sediments of a sheltered coastal area (Gulf of Gaeta, central-eastern Tyrrhenian Sea, Italy) in relation to hydrodynamic conditions - SIMONE BONAMANO; DANIELE PIAZZOLLA; SERGIO SCANU; VIVIANA PIERMATTEI; MARCO MARCELLI (Mediterranean Marine Science, 2021)
This study investigates the relationship between sediment contamination and hydrodynamic conditions in the Gaeta Gulf (Tyrrhenian Sea, Italy), an anthropogenically impacted and sheltered coastal area. The pollution levels, potential toxicity, and ecological risk of trace metals were analysed in 16 sediment sampling sites using Sediment Quality Guidelines (SQGs), the Adverse Effect Index (AEI), and the Mean ERM Quotient (m-ERM-Q). The bottom shear stress of the study area, evaluated using an annual simulation of a 3D numerical model, was used to calculate a new Sediment Mobilisation Index (SMI) that detects the coastal zones where a low probability of sediment resuspension occurs. As, Ni, and Cu concentrations exceeded the Threshold Effects Level (TEL) guideline value and AEI limit in several sampling sites, indicating their ability to produce adverse effects on biota. Moreover m-ERM-Q showed the highest values of potential ecological risk in most of the sampling sites located in the inner part of the Gulf of Gaeta. In this area, the highest SMI values were also identified, demonstrating that there is a tight relationship between the two indexes (R2 = 0.8214). The application of SMI in sheltered areas will help achieve high performance of monitoring and hazard assessment tools through obtaining predictable responses on hotspot identification.

Near Real-Time Monitoring of Significant Sea Wave Height through Microseism Recordings: Analysis of an Exceptional Sea Storm Event - Laura Cutroneo; Gabriele Ferretti; Simone Barani; Davide Scafidi; Francesco De Leo; Giovanni Besio; Marco Capello (Journal of Marine Science and Engineering, 2021)
Microseisms are used to estimate significant sea wave heights (Hs) in different parts of the world and also during extreme events (e.g., typhoons and hurricanes), as they are generated by the effect of sea waves on the sea bottom and are strictly related to the wave height. On 29 October 2018, an exceptional sea storm event (the Adrian storm) occurred in the Ligurian Sea (NW Mediterranean Sea), producing severe damage to coastal constructions and infrastructures. However, the microseism measured at seismic stations located near the coast did not show equivalent high energy, thus resulting in a severe underestimation of the Hs predicted. In the present study, the Adrian storm was compared to other sea storms that have occurred in the Ligurian Sea in recent decades. The aim of this paper is to statistically examine the distinctive peculiarities of the Adrian storm in order to find new parameters to insert in the empirical models used in the procedure recently implemented for monitoring of Hs through microseism recordings in the Ligurian Sea, improving the effectiveness in Hs estimates in cases of extreme events that do not produce high-energy microseisms. The results show that the additional parameters to be taken into account into the predictive model are the atmospheric pressure gradient and the wind intensity. A correction term is finally proposed and applied to the predictive model to significantly reduce the Hs underestimation.

Remarkable multicuspid teeth in a new elusive skate (Chondrichthyes, Rajiformes) from the Mediterranean Pliocene - Alberto Collareta; Frederik H. Mollen; Marco Merella; Simone Casati; Andrea Di Cencio (PalZ, 2021)
Here we report on four highly peculiar skate teeth from Arcille and Certaldo, two Pliocene localities of Tuscany (central Italy). While being attributable to Rajiformes and somewhat reminiscent of Dipturus and Rostroraja , these specimens display an unusual multicuspid tooth design that does not match any extinct or extant skate taxon known to date. The studied teeth are thus referred to a new genus and species of Rajiformes, Nebriimimus wardi gen. et sp. nov., which is here tentatively assigned to the family Rajidae. Based on pronounced morphological similarities between the rather large-sized teeth of the latter and those of extant nurse sharks, we hypothesise that N. wardi might have been capable of actively foraging upon relatively large food items compared to other rays. This extinct skate species was likely not a common component of the Pliocene Tuscan marine vertebrate assemblages. The palaeoenvironmental scenarios that N. wardi inhabited were marginal-marine and open shelf settings characterised by tropical climate conditions. As N. wardi is currently known only from lower to mid-Pliocene deposits of the Mediterranean Basin, it is tempting to speculate that its speciation dates back to an earliest Pliocene phase of diversification that also contributed to the emergence of the Mediterranean endemic stock of extant skate species.

Culturable fungi from dredged and marine sediments from six ports studied in the framework of the SEDITERRA Project - Grazia Cecchi; Laura Cutroneo; Simone Di Piazza; Marco Capello; Mirca Zotti (Journal of Soils and Sediments, 2021)

Muricauda brasiliensis sp. nov., isolated from a mat-forming cyanobacterial culture - Carla Simone Vizzotto; Julianna Peixoto; Stefan Joshua Green; Fabyano Alvares C. Lopes; Marcelo Henrique S. Ramada; Osmindo R. Pires Júnior; Otávio Henrique B. Pinto; Marcos Rogério Tótola; Fabiano Lopes Thompson; Ricardo Henrique Krüger (Brazilian Journal of Microbiology, 2021)

Impact of Plastic Debris on the Gut Microbiota of Caretta caretta From Northwestern Adriatic Sea - Elena Biagi; Margherita Musella; Giorgia Palladino; Valeria Angelini; Sauro Pari; Chiara Roncari; Daniel Scicchitano; Simone Rampelli; Silvia Franzellitti; Marco Candela (Frontiers in Marine Science, 2021)
Plastic pollution is nowadays a relevant threat for the ecological balance in marine ecosystems. Small plastic debris (PD) can enter food webs through various marine organisms, with possible consequences on their physiology and health. The loggerhead sea turtle ( Caretta caretta ), widespread across the whole Mediterranean Sea, is a “flagship species,” useful as indicator of the general pollution level of marine ecosystems. Ingested PD accumulate in the final section of turtles’ digestive tract before excretion. During their transit and accumulation, PD also interact with the residing microbial community, with possible feedback consequences on the host’s health. To explore the possible relationship between fecal microbial composition and PD ingestion, we collected fecal samples from 45 turtles rescued between 2017 and 2019 in the Northwestern Adriatic Sea (Italy), assessing occurrence and content of PD in the samples and in parallel the microbiome structure by 16S rRNA gene sequencing. According to our findings, almost all samples contained PD, mirroring the high level of plastic pollution in the area. We identified phylotypes associated to a high amount of PD, namely Cetobacterium somerae and other taxa, possibly responding to contamination by plastic-associated chemicals. Furthermore, putative marine pathogens were found associated to higher plastic contamination, supporting the hypothesis that PD can act as a carrier for environmental pathogenic bacteria into marine organisms. Besides confirming the role of the sea turtle as relevant flagship species for plastic pollution of the marine environment, our study paves the way to the exploration of the impact that PD ingestion can have on the microbial counterpart of large marine organisms, with potential feedback consequences on the animal and ecosystem health.

Seasonal Changes in Microbial Communities Associated With the Jewel Anemone Corynactis viridis - Giorgia Palladino; Elena Biagi; Simone Rampelli; Margherita Musella; Federica D’Amico; Silvia Turroni; Patrizia Brigidi; Gian Marco Luna; Marco Candela (Frontiers in Marine Science, 2021)
Increasing evidence indicates that host-associated microbial communities play a key role in the biology of marine eukaryotic organisms. Amongst them, Corallimorpharia are extensively found on reefs, carpeting vast reef areas, where they can exert important roles as habitat forming holobionts, being at the base of complex trophic webs. Here we explore the bacterial community structure, and its changes across different seasons, associated with the jewel anemone Corynactis viridis , an anthozoan Cnidaria that is widely distributed in the northeastern Atlantic Ocean and the Mediterranean Sea. Samples were collected in the North Adriatic Sea in three seasons and the community composition was studied using 16S rDNA sequencing. We show that C. viridis- associated microbial communities are unique and significantly different from those in the surrounding seawater. Interestingly, we observe remarkable changes in the C. viridis microbiome according to seasonality. In particular, the C. viridis microbiome is capable of rearranging its overall ecological structure with the winter-summer transition, moving from an oligotrophic anaerobic community to a heterotrophic ecosystem, with the propensity to ferment proteins and complex polysaccharides. Our findings demonstrate that C. viridis has a unique associated microbiota and suggest that this is capable of adapting to seasonal changes in the host physiology, by establishing a microbiome-host interaction process whose relevance to C. viridis has yet to be determined.

Brain tissue transcriptomic analysis of SIV-infected macaques identifies several altered metabolic pathways linked to neuropathogenesis and poly (ADP-ribose) polymerases (PARPs) as potential therapeutic targets - Carla Mavian; Andrea S. Ramirez-Mata; James Jarad Dollar; David J. Nolan; Melanie Cash; Kevin White; Shannan N. Rich; Brittany Rife Magalis; Simone Marini; Mattia C. F. Prosperi; David Moraga Amador; Alberto Riva; et al. (Journal of NeuroVirology, 2021)
Despite improvements in antiretroviral therapy, human immunodeficiency virus type 1 (HIV-1)-associated neurocognitive disorders (HAND) remain prevalent in subjects undergoing therapy. HAND significantly affects individuals’ quality of life, as well as adherence to therapy, and, despite the increasing understanding of neuropathogenesis, no definitive diagnostic or prognostic marker has been identified. We investigated transcriptomic profiles in frontal cortex tissues of Simian immunodeficiency virus (SIV)-infected Rhesus macaques sacrificed at different stages of infection. Gene expression was compared among SIV-infected animals ( n = 11), with or without CD8+ lymphocyte depletion, based on detectable ( n = 6) or non-detectable ( n = 5) presence of the virus in frontal cortex tissues. Significant enrichment in activation of monocyte and macrophage cellular pathways was found in animals with detectable brain infection, independently from CD8+ lymphocyte depletion. In addition, transcripts of four poly (ADP-ribose) polymerases (PARPs) were up-regulated in the frontal cortex, which was confirmed by real-time polymerase chain reaction. Our results shed light on involvement of PARPs in SIV infection of the brain and their role in SIV-associated neurodegenerative processes. Inhibition of PARPs may provide an effective novel therapeutic target for HIV-related neuropathology.

Development of a New Predictive index (Bathing Water Quality Index, BWQI) Based on Escherichia coli Physiological States for Bathing Waters Monitoring - Simone Bonamano; Alice Madonia; Gabriella Caruso; Giuseppe Zappalà; Marco Marcelli (Journal of Marine Science and Engineering, 2021)
Bacterial pathogens in coastal aquatic ecosystems pose a potential public health hazard for bathing water use. The European Bathing Water Directive (2006/7/EC) currently relies on the culturability of fecal pollution bacterial indicators such as Escherichia coli, without considering dormant or quiescent (Viable But Not Culturable, VBNC) cells, whose possible resuscitation after bathers ingestion cannot be excluded. Standard methods are also time-consuming and therefore hardly meet early warning needs of marine monitoring. To solve this issue, a new index, the Bathing Water Quality Index (BWQI), has here been developed, allowing to identify the most favorable coastal zones for recreational use. The index was calculated by combining numerical simulations of living and dormant E. coli abundances and their residence times. To specifically set up the model with the different physiological states of the whole E. coli population, an ad hoc experiment based on the fluorescent antibody method was performed. The BWQI application to Santa Marinella bathing area highlights a potential risk for human health in the zone most frequented by bathers. This study provides a predictive tool to support preventive decisions of the competent authorities and to properly protect bathers’ health, stressing the need for improved methods for environmental monitoring.

Sensitivity of trends to estimation methods and quantification of subsampling effects in global radiosounding temperature and humidity time series - Souleymane SY; Fabio Madonna; Marco Rosoldi; Emanuele Tramutola; Simone Gagliardi; Monica Proto; Gelsomina Pappalardo (International Journal of Climatology, 2021)
Climate trends estimated using historical radiosounding time series may be significantly affected by the choice of the regression method to use, as well as by a subsampling of the dataset often adopted in specific applications. These are contributions to the uncertainty of trend estimations, which have been quantified in literature, although on specific pairs of regression methods, and in the not very recent past characterized by smaller trends in temperature than those observed over the last two decades. This paper investigates the sensitivity of trend estimations to four linear regression methods (parametric and nonparametric) and to the artificial subsampling of the same dataset using historical radiosounding time series from 1978 onwards, available in the version 2 of the Integrated Global Radiosonde Archive (IGRA). Results show that long‐term decadal trends may have not negligible uncertainties related to the choice of the regression method, the percentage of data available, the amount of missing data and the number of stations selected in the dataset. The choice of the regression methods increases uncertainties in the decadal trends ranging from −0.10 to −0.01 K⋅da –1 for temperature in the lower stratosphere at 100 hPa and from 0.2 to 0.8% da –1 for relative humidity (RH) in the middle troposphere at 300 hPa. Differences can also increase up to 0.4 K⋅da –1 at 300 hPa when the amount of missing data exceeds 50% of the original dataset for temperature, while for RH, significant differences are observed in the lower troposphere at 925 hPa for almost all datasets. Finally, subsampling effects on trend estimation are quantified by artificially reducing the size of the IGRA dataset: Results show that subsampling effects on trend estimations when at least 60 stations, up to 76% of data available, are considered for temperature and at least 40 stations for RH.

A review of studies on observed precipitation trends in Italy - Enrica Caporali; Marco Lompi; Tommaso Pacetti; Valentina Chiarello; Simone Fatichi (International Journal of Climatology, 2021)
Research to detect changes in precipitation variables has become a topic of particular interest to understand modifications in water resources availability. The review is focused on the Italian territory, outlining the “state of the art” of changes in precipitation regime through a review of 54 published studies on observed rainfall trend analyses, in the period 1999–2018. The aim is to combine a large body of knowledge in a single review and to explain the main patterns of rainfall changes occurred in Italy over the last decades. The analysis focused on the Total Precipitation (TP) and the number of Wet Days (WDs) indices at the annual and seasonal scale. A weight factor is introduced to take into account the differences among studies in geographical area, time series length, and number of stations. The review is accompanied by the discussion of other rainfall related variables, that is, precipitation intensity, extreme rainfall events and meteorological droughts, which are useful to provide a broader picture of rainfall changes. Overall, there is an agreement about the tendency of a decrease in wet days on the entire Italy, with limited discrepancies in the various regions. A decrease in wet days is accompanied by a negative trend (although less evident) in total precipitation, especially in winter. Nevertheless, a univocal direction of trends (or lack of thereof) in annual total precipitation and mostly hydrological extreme events is difficult to achieve.

Autozygosity-driven genetic diagnosis in consanguineous families from Italy and the Greater Middle East - Flavia Palombo; Claudio Graziano; Nadia Al Wardy; Nayereh Nouri; Caterina Marconi; Pamela Magini; Giulia Severi; Chiara La Morgia; Gaetano Cantalupo; Duccio Maria Cordelli; Simone Gangarossa; Mohammed Nasser Al Kindi; et al. (Human Genetics, 2020)

Phylogenetic relationships and taxonomic issues in Gastridium (Poaceae) inferred from plastid and nuclear DNA sequence analysis - Anna Scoppola; Simone Cardoni; Mariangela Pellegrino; Javier López-Tirado; Marco Cosimo Simeone (Plant Biosystems, 2020)

Nitrogen assimilation under different nitrate nutrition in Tunisian durum wheat landraces and improved genotypes - Sawsen Ayadi; Salma Jallouli; Simone Landi; Giorgia Capasso; Zoubeir Chamekh; Manuela Cardi; Valeria Paradisone; Marco Lentini; Chahine Karmous; Youssef Trifa; Sergio Esposito (Plant Biosystems, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Microbial Abundance and Enzyme Activity Patterns: Response to Changing Environmental Characteristics along a Transect in Kongsfjorden (Svalbard Islands) - Gabriella Caruso; Alice Madonia; Simone Bonamano; Stefano Miserocchi; Federico Giglio; Giovanna Maimone; Filippo Azzaro; Franco Decembrini; Rosabruna La Ferla; Viviana Piermattei; Daniele Piazzolla; Marco Marcelli; et al. (Journal of Marine Science and Engineering, 2020)
Svalbard archipelago is experiencing the effects of climate changes (i.e., glaciers’ thickness reduction and glacier front retreat), but how ice melting affects water biogeochemistry is still unknown. Microbial communities often act as environmental sentinels, modulating their distribution and activity in response to environmental variability. To assess microbial response to climate warming, within the ARctic: present Climatic change and pAst extreme events (ARCA) project, a survey was carried out along a transect in Konsfjorden from off-shore stations towards the Kronebreen glacier. Total bacterial abundance and the fraction of actively respiring cells (labelled by cyanotetrazolium chloride, CTC), cultivable heterotrophic bacterial abundance, and extracellular enzymatic activities (leucine aminopeptidase (LAP), beta-glucosidase (GLU), and alkaline phosphatase (AP)) were measured. In addition, water temperature, salinity, dissolved oxygen, turbidity, total suspended matter (TSM), particulate and chromophoric dissolved organic matter (CDOM), chlorophyll-a (Chl-a), and inorganic compounds were determined, in order to evaluate whether variations in microbial abundance and metabolism were related with changes in environmental variables. Colder waters at surface (3.5–5 m) depths and increased turbidity, TSM, and inorganic compounds found at some hydrological stations close to the glacier were signals of ice melting. CDOM absorption slope values (275–295 nm) varied from 0.0077 to 0.0109 nm−1, and total bacterial cell count and cultivable heterotrophic bacterial abundance were in the order of 106 cells/mL and 103 colony forming units/mL, respectively. Enzymatic rates

A multifunctional alternative lawn where warm-season grass and cold-season flowers coexist - Francesca Bretzel; Monica Gaetani; Francesca Vannucchi; Claudia Caudai; Nicola Grossi; Simone Magni; Lisa Caturegli; Marco Volterrani (Landscape and Ecological Engineering, 2020)

High-throughput microRNA profile in adult and pediatric primary glioblastomas: the role of miR-10b-5p and miR-630 in the tumor aggressiveness - Luiz Guilherme Darrigo Junior; Mirella Baroni; Régia Caroline Peixoto Lira; Silvia Teixeira; Paola Fernanda Fedatto; Vanessa Silva Silveira; Veridiana Kill Suazo; Luciana Chain Veronez; Rodrigo Alexandre Panepucci; David Santos Marco Antônio; José Andres Yunes; Silvia Regina Brandalise; et al. (Molecular Biology Reports, 2020)

Benefits of conservation-driven mowing for the EU policy species Gladiolus palustris Gaudin in mountain fen meadows: a case-study in the European Alps - Marco Canella; Gianni Poloniato; Cesare Lasen; Simone Orsenigo; Graziano Rossi; Jonas V. Müller; Thomas Abeli (Journal of Mountain Science, 2020)
The sword lily Gladiolus palustris Gaudin is protected on European level and listed in Annexes II and IV of the EC Habitat Directive 92/43/EEC. It grows in nutrient-poor, calcareous meadows in central and eastern Europe. Tree encroachment in montane meadows of the European Alps as a result of recent land use changes and the abandonment of traditional farming practices threaten the survival of this species. Conservation-driven mowing is considered a feasible conservation measure for maintaining high species diversity in abandoned semi-natural grasslands. To assess the effects of ten years of biennial mowing on a grassland community in the Dolomiti Bellunesi National Park, Italy (Site of Community Importance, Natura 2000 network), ten 25 m 2 plots were established whereby four plots were placed in the mowed area, four in the non-mowed area and two in a small non-mowed patch of grassland inside the mowed area. In each plot the following variables were recorded, total percentage of plant cover, percentage cover of woody species, percentage cover of herbaceous species, percentage cover and number of flowering ramets of G. palustris and a complete list of species and their percentage abundance. Mowed plots showed a higher species richness than non-mowed plots. The number of G. palustris flowering ramets and percentage cover increased manifold in mowed plots compared to non-mowed plots. The resumption of mowing for conservation purposes undertaken by the managing authority halted the process of tree encroachment and avoided a drastic change in plant composition. Periodic mowing (every second or third year) was demonstrated to be a cost-effective conservation measure in non-productive grasslands to keep grasses at bay in favour of forbs of high conversation value.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Moving Toward a Strategy for Addressing Climate Displacement of Marine Resources: A Proof-of-Concept - M. Cristina Mangano; Nova Mieszkowska; Brian Helmuth; Tiago Domingos; Tania Sousa; Giuseppe Baiamonte; Giuseppe Bazan; Angela Cuttitta; Fabio Fiorentino; Antonio Giacoletti; Magnus Johnson; Giuseppe D. Lucido; et al. (Frontiers in Marine Science, 2020)

Temporal Changes in Microbial Communities Beneath Fish Farm Sediments Are Related to Organic Enrichment and Fish Biomass Over a Production Cycle - Grazia Marina Quero; Francesca Ape; Elena Manini; Simone Mirto; Gian Marco Luna (Frontiers in Marine Science, 2020)

Chromophoric Dissolved Organic Matter as a Tracer of Fecal Contamination for Bathing Water Quality Monitoring in the Northern Tyrrhenian Sea (Latium, Italy) - Alice Madonia; Gabriella Caruso; Daniele Piazzolla; Simone Bonamano; Viviana Piermattei; Giuseppe Zappalà; Marco Marcelli (Journal of Marine Science and Engineering, 2020)
Dissolved organic matter present in natural aquatic environments is a heterogeneous mixture of allochthonous and autochthonous materials. In coastal areas vulnerable to sewage waste, its biologically active component, the chromophoric dissolved organic matter (CDOM), is expected to change its composition and distribution in relation to anthropogenic activities, suggesting the possible use of CDOM as a proxy of fecal contamination. This study aimed at testing such hypothesis by investigating and relating the optical properties of CDOM with Escherichia coli abundance, physiological state, and enzymatic activities in a bathing area of the Northern Tyrrhenian Sea (Latium, Italy) affected by urban wastewaters. The parallel factor analysis (PARAFAC) applied to the excitation–emission matrices (EEMs) of CDOM allowed us to distinguish three main components: C1 (λEx/λEm = 342 nm/435 nm), C2 (λEx/λEm = 281–373 nm/460 nm), and C3 (λEx/λEm = 286 nm/360 nm). C1 and C2 corresponded to humic acids of terrestrial origin, while C3 to tryptophan, whose fluorescence peak was detected close to sewage sites, strongly related to active E. coli cells. The comparison between spectral and microbiological methods is suggested as a suitable approach to monitor bathing water quality for the implementation of coastal observing system capability.

From waste to resource: mycoremediation of contaminated marine sediments in the SEDITERRA Project - Grazia Cecchi; Laura Cutroneo; Simone Di Piazza; Greta Vagge; Marco Capello; Mirca Zotti (Journal of Soils and Sediments, 2020)

Neutralization of extracellular NAMPT (nicotinamide phosphoribosyltransferase) ameliorates experimental murine colitis - Giorgia Colombo; Nausicaa Clemente; Andrea Zito; Cristiano Bracci; Federico Simone Colombo; Sabina Sangaletti; Elena Jachetti; Davide Giuseppe Ribaldone; Gian Paolo Caviglia; Luca Pastorelli; Marco De Andrea; Samuele Naviglio; et al. (Journal of Molecular Medicine, 2020)

Not a marginal loss: genetic diversity of the endangered freshwater snail Melanopsis etrusca (Brot, 1862) from thermal springs in Tuscany, Italy - Marco T. Neiber; Simone Cianfanelli; Fabrizio Bartolini; Matthias Glaubrecht (Conservation Genetics, 2020)

Preliminary Investigation of Microlitter Pollution in Low-Energy Hydrodynamic Basins Using Sabella spallanzanii (Polychaeta: Sabellidae) Tubes - Daniele Piazzolla; Valentina Cafaro; Emanuele Mancini; Sergio Scanu; Simone Bonamano; Marco Marcelli (Bulletin of Environmental Contamination and Toxicology, 2020)

Cumulative biomass curves describe past and present conditions of Large Marine Ecosystems - Fabio Pranovi; Simone Libralato; Matteo Zucchetta; Marco Anelli Monti; Jason S. Link (Global Change Biology, 2020)
Implementing the Ecosystem Approach in marine ecosystems is moving from preliminary steps—dedicated to defining the optimal features for indicators and developing efficient indicator frameworks—towards an operational phase where multisector marine management decisions are executed using this information. Within this operational context, emergent ecosystem properties are becoming quite promising as they have been demonstrated to be globally widespread and repeatable, and to be quite effective in detecting significant state variations of complex systems. Biomass accumulation across TLs (CumB‐TL) combines two important emergent properties of an ecosystem (energy flow, in terms of transfer efficiency, and storage, expressed as biomass), both amenable to detecting rapid ecosystem change. However, for further application, it is crucial to understand which types of drivers an indicator is sensitive to and how robust it is in relation to modifications of the external conditions and/or the system state. Here we address some outstanding questions of these CumB‐TL curves related to their sensitivity to various drivers by carrying out a global scale assessment (using data from 62 LMEs) over six decades (1950–2010). We confirm the consistency of the S‐pattern across all the LMEs, independent from latitude, ecosystem, environmental conditions, and stress level. The dynamics of the curve shape showed a tendency to stretch (i.e. decrease of steepness), in the presence of external disturbance and conversely to increase in steepness and shift towards higher TL in the case of recovery from stressed conditions. Our results suggest the presence of three main types of ecosystem dynamics, those showing an almost continuous increase in ecological state over time, those showing a continuous decrease in ecological state over time, and finally those showing a mixed behaviour flipping between recovering and degrading phases. These robust patterns suggest that the CumB‐TL curve approach has some useful properties for use in further advancing the implementation of the Ecosystem Approach, allowing us to detect the state of a given marine ecosystem based on the dynamics of its curve shape, by using readily available time series data. The value of being able to identify conditions that might require management actions is quite high and, in many respects, represents the main objective in the context of an Ecosystem Approach, with large applications for detecting and responding to global changes in marine ecosystems.

Normalized Difference Vegetation Index versus Dark Green Colour Index to estimate nitrogen status on bermudagrass hybrid and tall fescue - Lisa Caturegli; Monica Gaetani; Marco Volterrani; Simone Magni; Alberto Minelli; Ada Baldi; Giada Brandani; Marco Mancini; Anna Lenzi; Simone Orlandini; Filippo Lulli; Claudia de Bertoldi; et al. (International Journal of Remote Sensing, 2020)

Molecular phylogeny and host‐plant use (Lamiaceae) of the Thymogethes pollen beetles (Coleoptera) - Simone Sabatelli; Meike Liu; Davide Badano; Emiliano Mancini; Marco Trizzino; Andrew Richard Cline; Anders Endrestøl; Min Huang; Paolo Audisio (Zoologica Scripta, 2020)
The 24 members of the Euro‐Asiatic genus Thymogethes are highly specialized pollen beetles associated as larvae with flowers of Lamiaceae Nepetoideae. All members of the genus were analysed in within the framework of an integrative taxonomy approach, which was aimed to reconstruct the phylogenetic relationships, as well as the possible pattern of evolution of their larval‐host‐plant association. Evidence from multiple molecular markers [COI; 16S; H3], combined with an estimation of divergence times using an average rate of 0.0177 substitutions/site/My among branches, placed the origin of the genus at a minimum of 9–10 Mya. This date of origin approximates the known evolution of the host plants in Euro‐Mediterranean areas. Evidence from combined molecular and cladistic morphological analyses resulted in suitable agreement with the previously established morphology‐based systematics of the genus, although members of the exilis species‐group were split into three clades. The only disagreement between results of this new combined phylogeny and previous classification is in the exclusion of “ Thymogethes ” grenieri . This species is herein positioned outside the genus, based on molecular evidence. Our analysis depicts several Thymogethes species differentiating in the last few Mys, specifically those included in the T. lugubris species‐group. Combined evidence from DNA, morphology and ancestral state parsimony reconstruction of larval‐host‐plant associations suggests that subtribe Menthinae likely represents the ancestral host plants, with a series of independent host shifts during the radiation of the clade, in association first with Menthinae and subsequently with Lavandulinae and Nepetinae. Steno‐oligophagy is the most frequent (86%) condition, while strictly monophagous species are less numerous (14%).

Detection of selected pathogens in Apennine wolf (Canis lupus italicus) by a non-invasive GPS-based telemetry sampling of two packs from Majella National Park, Italy - Cristina E. Di Francesco; Camilla Smoglica; Barbara Paoletti; Simone Angelucci; Marco Innocenti; Antonio Antonucci; Giovanna Di Domenico; Fulvio Marsilio (European Journal of Wildlife Research, 2019)

Fungi as potential tool for polluted port sediment remediation - Grazia Cecchi; Greta Vagge; Laura Cutroneo; Giuseppe Greco; Simone Di Piazza; Massimo Faga; Mirca Zotti; Marco Capello (Environmental Science and Pollution Research, 2019)

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Removal of chromium from wastewater by swine hair residues applied as a putative biofilter - Orlando de Paris Júnior; Thamarys Scapini; Aline Frumi Camargo; Bruno Venturin; Caroline Dalastra; Simone Kubeneck; Fabiane Fernanda Czapela; Karina P. Preczeski; Fábio Spitza Stefanski; Eduardo Pavan Korf; Alexsandra Valério; Marco Di Luccio; et al. (Environmental Science and Pollution Research, 2019)

Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Joaquín Tintoré; Nadia Pinardi; Enrique Álvarez-Fanjul; Eva Aguiar; Diego Álvarez-Berastegui; Marco Bajo; Rosa Balbin; Roberto Bozzano; Bruno Buongiorno Nardelli; Vanessa Cardin; Benjamin Casas; Miguel Charcos-Llorens; et al. (Frontiers in Marine Science, 2019)

Grazing Management Plans improve pasture selection by cattle and forage quality in sub-alpine and alpine grasslands - Marco Pittarello; Massimiliano Probo; Elisa Perotti; Michele Lonati; Giampiero Lombardi; Simone Ravetto Enri (Journal of Mountain Science, 2019)

Can extreme MHC class I diversity be a feature of a wide geographic range? The example of Seba’s short-tailed bat (Carollia perspicillata) - Tamar Qurkhuli; Nina Schwensow; Stefan Dominik Brändel; Marco Tschapka; Simone Sommer (Immunogenetics, 2019)

Skill assessment of global, regional, and coastal circulation forecast models: evaluating the benefits of dynamical downscaling in IBI (Iberia–Biscay–Ireland) surface waters - Pablo Lorente; Marcos García-Sotillo; Arancha Amo-Baladrón; Roland Aznar; Bruno Levier; José C. Sánchez-Garrido; Simone Sammartino; Álvaro de Pascual-Collar; Guillaume Reffray; Cristina Toledano; Enrique Álvarez-Fanjul (Ocean Science, 2019)
In this work, a multi-parameter inter-comparison of diverse ocean forecast models was conducted at the sea surface ranging from global to local scales in a two-phase stepwise strategy. Firstly, a comparison of CMEMS GLOBAL and the nested CMEMS IBI regional system was performed against satellite-derived and in situ observations. Results highlighted the overall benefits of both the GLOBAL direct data assimilation in open water and the increased horizontal resolution of IBI in coastal areas. Besides, IBI (Iberia–Biscay–Ireland) proved to capture shelf dynamics by better representing the horizontal extent and strength of a river freshwater plume, according to the results derived from the validation against in situ observations from a buoy moored in NW Spain. Secondly, a multi-model inter-comparison exercise for 2017 was performed in the Strait of Gibraltar among GLOBAL, IBI, and SAMPA (Sánchez-Garrido et al., 2013) high-resolution coastal forecast systems (partially nested to IBI) in order to elucidate the accuracy of each system to characterize the Atlantic Jet (AJ) inflow dynamics. A quantitative validation against hourly currents from high-frequency radar (HFR) highlighted both the steady improvement in AJ representation in terms of speed and direction when zooming from global to coastal scales through a multi-nesting model approach and also the relevance of a variety of factors at local scale such as a refined horizontal resolution, a tailored bathymetry, and a higher spatio-temporal resolution of the atmospheric forcing. The ability of each model to reproduce a 2 d quasi-permanent full reversal of the AJ surface inflow was examined in terms of wind-induced circulation patterns. SAMPA appeared to better reproduce the reversal events detected with HFR estimations, demonstrating the added value of imposing accurate meteorologically driven barotropic velocities in the open boundaries (imported from the NIVMAR (Álvarez-Fanjul et al., 2001) storm surge model) to take into account the remote effect of the atmospheric forcing over the entire Mediterranean basin, which was only partially included in IBI and GLOBAL systems. Finally, SAMPA coastal model outputs were also qualitatively analysed in the western Alboran Sea to put in a broader perspective the context of the onset, development, and end of such flow reversal episodes.

Lead and copper in hunted wild boars and radiographic evaluation of bullet fragmentation between ammunitions - Alessandro Menozzi; Simonetta Menotta; Giorgio Fedrizzi; Antonio Lenti; Anna Maria Cantoni; Rosanna Di Lecce; Giacomo Gnudi; Marcos Pérez-López; Simone Bertini (Food Additives & Contaminants Part B-Surveillance, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Effects of deciduous shade trees on surface temperature and pedestrian thermal stress during summer and autumn - Luciano Massetti; Martina Petralli; Marco Napoli; Giada Brandani; Simone Orlandini; David Pearlmutter (International Journal of Biometeorology, 2019)

Wild ungulates and environmental temperature: analysis on the possible utilization of data from sensor placed on GPS collars - Alessandro Messeri; Valentina Becciolini; Gianni Messeri; Marco Morabito; Alfonso Crisci; Simone Orlandini; Maria Paola Ponzetta (International Journal of Biometeorology, 2019)

Landsat 8 OLI satellite data for mapping of the Posidonia oceanica and benthic habitats of coastal ecosystems - Flavio Borfecchia; Natalizia Consalvi; Carla Micheli; Filippo M. Carli; Selvaggia Cognetti De Martiis; Valentina Gnisci; Viviana Piermattei; Alessandro Belmonte; Luigi De Cecco; Simone Bonamano; Marco Marcelli (International Journal of Remote Sensing, 2019)

Mediterranean ocean colour Level 3 operational multi-sensor processing - Gianluca Volpe; Simone Colella; Vittorio E. Brando; Vega Forneris; Flavio La Padula; Annalisa Di Cicco; Michela Sammartino; Marco Bracaglia; Florinda Artuso; Rosalia Santoleri (Ocean Science, 2019)
The Mediterranean near-real-time multi-sensor processing chain has been set up and is operational in the framework of the Copernicus Marine Environment Monitoring Service (CMEMS). This work describes the main steps operationally performed to enable single ocean colour sensors to enter the multi-sensor processing applied to the Mediterranean Sea by the Ocean Colour Thematic Assembly Centre within CMEMS. Here, the multi-sensor chain takes care of reducing the inter-sensor bias before data from different sensors are merged together. A basin-scale in situ bio-optical dataset is used both to fine tune the algorithms for the retrieval of phytoplankton chlorophyll and the attenuation coefficient of light, Kd, and to assess the uncertainty associated with them. The satellite multi-sensor remote sensing reflectance spectra agree better with the in situ observations than those of the single sensors. Here, we demonstrate that the operational multi-sensor processing chain compares sufficiently well with the historical in situ datasets to also confidently be used for reprocessing the full data time series.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

The orbitofrontal cortex projects to the parvafox nucleus of the ventrolateral hypothalamus and to its targets in the ventromedial periaqueductal grey matter - Alexandre Babalian; Simone Eichenberger; Alessandro Bilella; Franck Girard; Viktoria Szabolcsi; Diana Roccaro; Gonzalo Alvarez-Bolado; Chun Xu; Marco R. Celio (Brain Structure and Function, 2019)

Some strains that have converged to infect Prunus spp. trees are members of distinct Pseudomonas syringae genomospecies and ecotypes as revealed by in silico genomic comparison - Simone Marcelletti; Marco Scortichini (Archives of Microbiology, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Genomic prediction ability for beef fatty acid profile in Nelore cattle using different pseudo-phenotypes - Hermenegildo Lucas Justino Chiaia; Elisa Peripolli; Rafael Medeiros de Oliveira Silva; Fabiele Loise Braga Feitosa; Marcos Vinícius Antunes de Lemos; Mariana Piatto Berton; Bianca Ferreira Olivieri; Rafael Espigolan; Rafael Lara Tonussi; Daniel Gustavo Mansan Gordo; Lucia Galvão de Albuquerque; Henrique Nunes de Oliveira; et al. (Journal of Applied Genetics, 2018)

Industrial Development of a 3D-Printed Nutraceutical Delivery Platform in the Form of a Multicompartment HPC Capsule - Alice Melocchi; Federico Parietti; Simone Maccagnan; Marco Aldo Ortenzi; Stefano Antenucci; Francesco Briatico-Vangosa; Alessandra Maroni; Andrea Gazzaniga; Lucia Zema (AAPS PharmSciTech, 2018)

Anthropogenic and environmental factors affect the tree line position of Fagus sylvatica along the Apennines (Italy) - Giuliano Bonanomi; Angelo Rita; Emilia Allevato; Gaspare Cesarano; Luigi Saulino; Gaetano Di Pasquale; Marina Allegrezza; Simone Pesaresi; Marco Borghetti; Sergio Rossi; Antonio Saracino (Journal of Biogeography, 2018)
Aim High‐elevation forest line or tree line is an ecological ecotone representing the upper elevation thermal limit for forest development. The current tree line position is the result of the past human activity interacting with climatic and topographic conditions. In this study, we investigate how climate, local topographic factors and anthropogenic disturbance currently affect tree line distribution. Location Apennine Mountains, 900 km latitudinal gradient along the Italian Peninsula. Methods Overall, 302 mountain peaks were studied, comprising 3,622 km of measured tree lines. The position of the Fagus sylvatica tree line in all peaks was assessed and correlated with 58 selected variables representing climate, topography and human disturbance. Results The mean tree line elevation was 1,589 m a.s.l., with considerable variability among peaks. Contrary to our expectations, the tree line elevation was lower in the warmer southerly exposed slopes compared to north‐facing aspects, where we found the highest tree line (2,141 m a.s.l.). Correlation analysis indicates that both climatic and human density variables are associated with tree line elevation, with the climate having more influence in high elevation mountains, while human impact plays a prominent role in low elevation mountain peaks. Specifically, we found negative correlations between density of the resident population around each peak and tree line elevation at all examined dates (1861, 1921, and 2011), suggesting a pervasive negative impact of human activity on tree lines. As regards climatic variables, tree line elevation showed a stronger negative correlation with winter and spring months temperature than with mean annual temperature. Noteworthy, climatic variables had stronger effect on high elevation peaks (>1,900 m a.s.l.) compared with low elevation ones ( Main Conclusion Our data provide evidence that the current position of the F. sylvatica tree line in the Apennines is heavily depressed as a result of a complex interaction between climatic factors and the past human pressure.

Early responses to cadmium exposure in barley plants: effects on biometric and physiological parameters - Marco Lentini; Alessia De Lillo; Valeria Paradisone; Daniela Liberti; Simone Landi; Sergio Esposito (Acta Physiologiae Plantarum, 2018)

Association study between copy number variation and beef fatty acid profile of Nellore cattle - Marcos Vinicius Antunes de Lemos; Elisa Peripolli; Mariana Piatto Berton; Fabiele Loise Braga Feitosa; Bianca Ferreira Olivieri; Nedenia Bonvino Stafuzza; Rafael Lara Tonussi; Sabrina Kluska; Hermenegildo Lucas Justino Chiaia; Lenise Mueller; Adrielli Mathias Ferrinho; Angelica Simone Cravo Prereira; et al. (Journal of Applied Genetics, 2018)

Agroecosystem energy transitions in the old and new worlds: trajectories and determinants at the regional scale - Simone Gingrich; Inés Marco; Eduardo Aguilera; Roc Padró; Claudio Cattaneo; Geoff Cunfer; Gloria I. Guzmán; Joshua MacFadyen; Andrew Watson (Regional Environmental Change, 2018)

Fungal Endophyte Communities in Begonia Species from the Brazilian Atlantic Rainforest - Ana M. L. Correia; Simone P. Lira; Marco A. Assis; Andre Rodrigues (Current Microbiology, 2018)

Reconstructing geographical parthenogenesis: effects of niche differentiation and reproductive mode on Holocene range expansion of an alpine plant - Bernhard Kirchheimer; Johannes Wessely; Andreas Gattringer; Karl Hülber; Dietmar Moser; Christoph C. F. Schinkel; Marc Appelhans; Simone Klatt; Marco Caccianiga; Agnes Dellinger; Antoine Guisan; Michael Kuttner; et al. (Ecology Letters, 2018)
Asexual taxa often have larger ranges than their sexual progenitors, particularly in areas affected by Pleistocene glaciations. The reasons given for this ‘geographical parthenogenesis’ are contentious, with expansion of the ecological niche or colonisation advantages of uniparental reproduction assumed most important in case of plants. Here, we parameterized a spread model for the alpine buttercup Ranunculus kuepferi and reconstructed the joint Holocene range expansion of its sexual and apomictic cytotype across the European Alps under different simulation settings. We found that, rather than niche broadening or a higher migration rate, a shift of the apomict's niche towards colder conditions per se was crucial as it facilitated overcoming of topographical barriers, a factor likely relevant for many alpine apomicts. More generally, our simulations suggest potentially strong interacting effects of niche differentiation and reproductive modes on range formation of related sexual and asexual taxa arising from their differential sensitivity to minority cytotype disadvantage.

Carnosic Acid Suppresses the H2O2-Induced Mitochondria-Related Bioenergetics Disturbances and Redox Impairment in SH-SY5Y Cells: Role for Nrf2 - Marcos Roberto de Oliveira; Gustavo da Costa Ferreira; Alessandra Peres; Simone Morelo Dal Bosco (Molecular Neurobiology, 2018)

Thermal sensitivity of the crab Neosarmatium africanum in tropical and temperate mangroves on the east coast of Africa - Marco Fusi; Simone Babbini; Folco Giomi; Sara Fratini; Farid Dahdouh-Guebas; Daniele Daffonchio; Christopher David McQuaid; Francesca Porri; Stefano Cannicci (Hydrobiologia, 2017)

Characterization of the human DNA gut virome across populations with different subsistence strategies and geographical origin - Simone Rampelli; Silvia Turroni; Stephanie L. Schnorr; Matteo Soverini; Sara Quercia; Monica Barone; Andrea Castagnetti; Elena Biagi; Giorgio Gallinella; Patrizia Brigidi; Marco Candela (Environmental Microbiology, 2017)
Summary It is a matter of fact that the human gut microbiome also includes a non‐bacterial fraction represented by eukaryotic cells and viruses. To further explore the gut microbiome variation in human populations, here we characterized the human DNA viral community from publicly available gut metagenome data sets from human populations with different geographical origin and lifestyle. In particular, such data sets encompass microbiome information from two western urban societies (USA and Italy), as well as two traditional hunter‐gatherer communities (the Hadza from Tanzania and Matses from Peru) and one pre‐agricultural tribe (Tunapuco from Peru). Our results allowed for the first taxonomic reconstruction of the complex viral metacommunities within the human gut. The core virome structure included herpesviruses, papillomaviruses, polyomaviruses, adenoviruses and anelloviruses. Using Random Forests and a co‐occurrence analysis approach, we identified the viruses that distinguished populations according to their geographical origin and/or lifestyle. This paves the way for new research aimed at investigating the biological role of the gut virome in human physiology, and the importance of our viral counterpart in the microbiome‐host co‐evolutionary process.

Pinocembrin Provides Mitochondrial Protection by the Activation of the Erk1/2-Nrf2 Signaling Pathway in SH-SY5Y Neuroblastoma Cells Exposed to Paraquat - Marcos Roberto de Oliveira; Alessandra Peres; Clarissa Severino Gama; Simone Morelo Dal Bosco (Molecular Neurobiology, 2017)

Carnosic Acid Protects Mitochondria of Human Neuroblastoma SH-SY5Y Cells Exposed to Paraquat Through Activation of the Nrf2/HO-1Axis - Marcos Roberto de Oliveira; Alessandra Peres; Gustavo Costa Ferreira; Patrícia Fernanda Schuck; Clarissa S. Gama; Simone Morelo Dal Bosco (Molecular Neurobiology, 2017)

Gene networks for total number born in pigs across divergent environments - Lucas L. Verardo; Marcos S. Lopes; Pramod Mathur; Ole Madsen; Fabyano F. Silva; Martien A. M. Groenen; Egbert F. Knol; Paulo S. Lopes; Simone E. F. Guimarães (Mammalian Genome, 2017)

Is it time to revise linezolid dose in elderly patients? - Marco Tinelli; Cristina Gervasoni; Manuela Piazza; Roberta Terzi; Valeria Cozzi; Elena Maffezzini; Chiara Cerri; Simone Castoldi; Sara Baldelli; Dario Cattaneo (European Journal of Clinical Pharmacology, 2017)

Tanshinone I Induces Mitochondrial Protection through an Nrf2-Dependent Mechanism in Paraquat-TreatedHuman Neuroblastoma SH-SY5Y Cells - Marcos Roberto de Oliveira; Patrícia Fernanda Schuck; Simone Morelo Dal Bosco (Molecular Neurobiology, 2017)

VASA expression suggests shared germ line dynamics in bivalve molluscs - Liliana Milani; Andrea Pecci; Fabrizio Ghiselli; Marco Passamonti; Simone Bettini; Valeria Franceschini; Maria Gabriella Maurizii (Histochemistry and Cell Biology, 2017)

Effect of tannery effluent on oxidative status of brain structures and liver of rodents - Felipe dos Santos Moysés; Karine Bertoldi; Viviane Rostirola Elsner; Laura Reck Cechinel; Carla Basso; Simone Stülp; Marco Antônio Siqueira Rodrigues; Ionara Rodrigues Siqueira (Environmental Science and Pollution Research, 2017)

Time–Space Evolution of Seismic Strain Release in the Area Shocked by the August 24–October 30 Central Italy Seismic Sequence - Simone Barani; Claudia Mascandola; Enrico Serpelloni; Gabriele Ferretti; Marco Massa; Daniele Spallarossa (Pure and Applied Geophysics, 2017)

Shell fluctuating asymmetry in the sea-dwelling benthic bivalve Mytilus galloprovincialis (Lamarck, 1819) as morphological markers to detect environmental chemical contamination - Massimiliano Scalici; Lorenzo Traversetti; Federica Spani; Valentina Malafoglia; Monica Colamartino; Tiziana Persichini; Simone Cappello; Giuseppe Mancini; Giulia Guerriero; Marco Colasanti (Ecotoxicology, 2017)

Phylogeographic structuring of plastome diversity in Mediterranean oaks (Quercus Group Ilex, Fagaceae) - Martina Vitelli; Federico Vessella; Simone Cardoni; Paola Pollegioni; Thomas Denk; Guido W. Grimm; Marco Cosimo Simeone (Tree Genetics & Genomes, 2017)

Genetic correlation estimates between beef fatty acid profile with meat and carcass traits in Nellore cattle finished in feedlot - Fabieli Loise Braga Feitosa; Bianca Ferreira Olivieri; Carolyn Aboujaoude; Angélica Simone Cravo Pereira; Marcos Vinicius Antunes de Lemos; Hermenegildo Lucas Justino Chiaia; Mariana Piatto Berton; Elisa Peripolli; Adrielle Matias Ferrinho; Lenise Freitas Mueller; Mônica Roberta Mazalli; Lucia Galvão de Albuquerque; et al. (Journal of Applied Genetics, 2017)

Spread of the invasive yellow-legged hornet Vespa velutina (Hymenoptera: Vespidae) in Italy - Sandro Bertolino; Simone Lioy; Daniela Laurino; Aulo Manino; Marco Porporato (Applied Entomology and Zoology, 2016)

Carnosic Acid Affords Mitochondrial Protection in Chlorpyrifos-Treated Sh-Sy5y Cells - Marcos Roberto de Oliveira; Alessandra Peres; Gustavo Costa Ferreira; Patrícia Fernanda Schuck; Simone Morelo Dal Bosco (Neurotoxicity Research, 2016)

Genome-wide comparison and taxonomic relatedness of multiple Xylella fastidiosa strains reveal the occurrence of three subspecies and a new Xylella species - Simone Marcelletti; Marco Scortichini (Archives of Microbiology, 2016)

Role of brain hemispheric dominance in anticipatory postural control strategies - David Cioncoloni; Deborah Rosignoli; Matteo Feurra; Simone Rossi; Marco Bonifazi; Alessandro Rossi; Riccardo Mazzocchio (Experimental Brain Research, 2016)

Morphological, genetic and host-plant diversification in pollen-beetles of the Brassicogethes coracinus group (Coleoptera: Nitidulidae: Meligethinae) - Emiliano Mancini; Alessio De Biase; Andrew Richard Cline; Gloria Antonini; Marco Trizzino; Tom Clayhills; Simone Sabatelli; Pierfilippo Cerretti; Paolo Audisio (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Artificial Muscle Devices: Innovations and Prospects for Fecal Incontinence Treatment - Elisa Fattorini; Tobia Brusa; Christian Gingert; Simone E. Hieber; Vanessa Leung; Bekim Osmani; Marco D. Dominietto; Philippe Büchler; Franc Hetzer; Bert Müller (Annals of Biomedical Engineering, 2016)

A matter of scale: apparent niche differentiation of diploid and tetraploid plants may depend on extent and grain of analysis - Bernhard Kirchheimer; Christoph C. F. Schinkel; Agnes S. Dellinger; Simone Klatt; Dietmar Moser; Manuela Winkler; Jonathan Lenoir; Marco Caccianiga; Antoine Guisan; Diego Nieto‐Lugilde; Jens‐Christian Svenning; Wilfried Thuiller; et al. (Journal of Biogeography, 2016)
Aim Emerging polyploids may depend on environmental niche shifts for successful establishment. Using the alpine plant Ranunculus kuepferi as a model system, we explore the niche shift hypothesis at different spatial resolutions and in contrasting parts of the species range. Location European Alps. Methods We sampled 12 individuals from each of 102 populations of R. kuepferi across the Alps, determined their ploidy levels, derived coarse‐grain (100 × 100 m) environmental descriptors for all sampling sites by downscaling WorldClim maps, and calculated fine‐scale environmental descriptors (2 × 2 m) from indicator values of the vegetation accompanying the sampled individuals. Both coarse and fine‐scale variables were further computed for 8239 vegetation plots from across the Alps. Subsequently, we compared niche optima and breadths of diploid and tetraploid cytotypes by combining principal components analysis and kernel smoothing procedures. Comparisons were done separately for coarse and fine‐grain data sets and for sympatric, allopatric and the total set of populations. Results All comparisons indicate that the niches of the two cytotypes differ in optima and/or breadths, but results vary in important details. The whole‐range analysis suggests differentiation along the temperature gradient to be most important. However, sympatric comparisons indicate that this climatic shift was not a direct response to competition with diploid ancestors. Moreover, fine‐grained analyses demonstrate niche contraction of tetraploids, especially in the sympatric range, that goes undetected with coarse‐grained data. Main conclusions Although the niche optima of the two cytotypes differ, separation along ecological gradients was probably less decisive for polyploid establishment than a shift towards facultative apomixis, a particularly effective strategy to avoid minority cytotype exclusion. In addition, our results suggest that coarse‐grained analyses overestimate niche breadths of widely distributed taxa. Niche comparison analyses should hence be conducted at environmental data resolutions appropriate for the organism and question under study.

Therapeutic drug monitoring of second-generation antipsychotics in pediatric patients: an observational study in real-life settings - Marco Pozzi; Dario Cattaneo; Sara Baldelli; Serena Fucile; Annalisa Capuano; Carmela Bravaccio; Liberata Sportiello; Silvana Bertella; Fabiana Auricchio; Renato Bernardini; Carmen Ferrajolo; Giuseppe Guastella; et al. (European Journal of Clinical Pharmacology, 2016)

Molecular ecology and phylogenetics of the water beetle genus Ochthebius revealed multiple independent shifts to marine rockpools lifestyle - Simone Sabatelli; Paolo Audisio; Gloria Antonini; Emanuela Solano; Adriano Martinoli; Marco Trizzino (Zoologica Scripta, 2016)
Marine rockpools represent a dynamic ecosystem where inhabiting species usually suffer changeable conditions, with consequent phenomena of local populations’ size expansions and reductions. Nevertheless, a few specialized insect groups are known to live in marine rockpools, and among them, several species belong to the water beetle family Hydraenidae. Three groups of Ochthebius sensu lato (s.l.) live in fact in marine rockpools: the putative subgenus Calobius , the former subgenus Cobalius (both mostly Mediterranean–Macaronesian) and two species of the O. capicola group from South Africa. In this work, we performed a molecular phylogeny of Ochthebius s.l., running molecular clocks, aiming to address the following questions: Are these three groups related? Which is their position within Ochthebius s.l.? How many different times and in how many lineages of Ochthebius s.l. a shift from inland waters to marine rockpools environments happened? Is the current taxonomic status of these three groups supported by genetics? We found that Calobius , Cobalius and the O. capicola group represent three distinct groups, with no sister relationships, suggesting that a shift from fresh/brackish waters to marine rockpools happened independently at least three different times along the diversification of the genus. Cobalius represents an effective separate subgenus, whereas such a rank is not supported by molecular data for Calobius , which represents a monophyletic clade within the nominal subgenus Ochthebius sensu stricto (s.str.). However, as Calobius is monophyletic and characterized by strongly peculiar and distinguishing morphology, we suggest referring to this group as the ‘ Calobius ’ lineage. Three Mediterranean taxa within this lineage represent likely valid new species, to be described soon. In the same way, the taxonomy of Cobalius should be revised, with two previously formally recognized species found to be paraphyletic, and the possible presence of two additional cryptic species.

Inhibition of hippocampal plasticity in rats performing contrafreeloading for water under repeated administrations of pramipexole - Chiara Schepisi; Annabella Pignataro; Salvatore Simone Doronzio; Sonia Piccinin; Caterina Ferraina; Silvia Di Prisco; Marco Feligioni; Anna Pittaluga; Nicola Biagio Mercuri; Martine Ammassari-Teule; Robert Nisticò; Paolo Nencini (Psychopharmacology, 2016)

Where is the best site for wave energy exploitation? Case study along the coast of northern Latium (ITALY) - Francesco Paladini de Mendoza; Simone Bonamano; Giuseppe Stella; Monica Giovacchini; Dario Capizzi; Fulvio Fraticelli; Sergio Muratore; Calogero Burgio; Sergio Scanu; Maximo A. Peviani; Marco Marcelli (Journal of Coastal Conservation, 2016)

Contrasting environments shape thermal physiology across the spatial range of the sandhopper Talorchestia capensis - Simone Baldanzi; Nicolas F. Weidberg; Marco Fusi; Stefano Cannicci; Christopher D. McQuaid; Francesca Porri (Oecologia, 2015)

The “SYSTEMS BIOLOGY” in the study of xenobiotic effects on marine organisms for evaluation of the environmental health status: biotechnological applications for potential recovery strategies - Salvatore Fasulo; Giulia Guerriero; Simone Cappello; Marco Colasanti; Trifone Schettino; Claudio Leonzio; Giuseppe Mancini; Rosalba Gornati (Reviews in Environmental Science and Bio/Technology, 2015)

Challenges and opportunities for web-shared publication of quality-assured life cycle data: the contributions of the Life Cycle Data Network - Marco Recchioni; Gian Andrea Blengini; Simone Fazio; Fabrice Mathieux; David Pennington (The International Journal of Life Cycle Assessment, 2015)

Palladium uptake by Pisum sativum: partitioning and effects on growth and reproduction - Matteo Ronchini; Laura Cherchi; Simone Cantamessa; Marco Lanfranchi; Alberto Vianelli; Paolo Gerola; Graziella Berta; Alessandro Fumagalli (Environmental Science and Pollution Research, 2015)

GeoEye-1 satellite versus ground-based multispectral data for estimating nitrogen status of turfgrasses - Lisa Caturegli; Marco Casucci; Filippo Lulli; Nicola Grossi; Monica Gaetani; Simone Magni; Enrico Bonari; Marco Volterrani (International Journal of Remote Sensing, 2015)

A hidden Markov approach to the analysis of space–time environmental data with linear and circular components - Francesco Lagona; Marco Picone; Antonello Maruotti; Simone Cosoli (Stochastic Environmental Research and Risk Assessment, 2015)

Metabarcoding analysis of European hake diet in the Mediterranean Sea - Riccioni Giulia; Stagioni Marco; Tinti Fausto; Piccinetti Corrado; Libralato Simone (Frontiers in Marine Science, 2015)

The state of the art of Xyalidae (Nematoda, Monhysterida) with reference to the Brazilian records - Virág Venekey; Paula F. Gheller; Tatiana F. Maria; Marco C. Brustolin; Noelia Kandratavicius; Danilo C. Vieira; Simone Brito; Guilherme S. Souza; Gustavo Fonseca (Marine Biodiversity, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Prenatal corticosterone and adolescent URB597 administration modulate emotionality and CB1 receptor expression in mice - Chiara Ceci; Virginia Mela; Simone Macrì; Eva M. Marco; Maria-Paz Viveros; Giovanni Laviola (Psychopharmacology, 2014)

Multilingual education of students on a global scale and perspective—international networking on the example of bioindication and biomonitoring (B&B technologies) - Bernd Markert; Edita Baltrėnaitė; Ewa Chudzińska; Silvia De Marco; Jean Diatta; Zahra Ghaffari; Svetlana Gorelova; Jorge Marcovecchio; Guntis Tabors; Meie Wang; Naglaa Yousef; Stefan Fraenzle; et al. (Environmental Science and Pollution Research, 2014)

Emission of air pollutants from burning candles with different composition in indoor environments - Marco Derudi; Simone Gelosa; Andrea Sliepcevich; Andrea Cattaneo; Domenico Cavallo; Renato Rota; Giuseppe Nano (Environmental Science and Pollution Research, 2014)

Disturbances, elevation, topography and spatial proximity drive vegetation patterns along an altitudinal gradient of a top biodiversity hotspot - Pedro V. Eisenlohr; Luciana F. Alves; Luís Carlos Bernacci; Maíra C. G. Padgurschi; Roseli B. Torres; Eduardo M. B. Prata; Flavio Antonio M. dos Santos; Marco Antônio Assis; Eliana Ramos; André Luís C. Rochelle; Fernando R. Martins; Mariana C. R. Campos; et al. (Biodiversity and Conservation, 2013)

Mediterranean climate patterns and wine quality in North and Central Italy - John David Dalu; Marina Baldi; Anna Dalla Marta; Simone Orlandini; Gianpiero Maracchi; Giovanni Dalu; Daniele Grifoni; Marco Mancini (International Journal of Biometeorology, 2013)

Differentially-regulated defence genes in Malus domestica during phytoplasma infection and recovery - Rita Musetti; Khaled Farhan; Federica De Marco; Rachele Polizzotto; Annarita Paolacci; Mario Ciaffi; Paolo Ermacora; Simone Grisan; Simonetta Santi; Ruggero Osler (European Journal of Plant Pathology, 2013)

A modeling language to support the interoperability of global navigation satellite systems - Daniele Gianni; Joachim Fuchs; Pierluigi De Simone; Marco Lisi (GPS Solutions, 2013)

The role of geological substrate for horn growth in ungulates: a case study on Alpine chamois - Roberta Chirichella; Simone Ciuti; Stefano Grignolio; Michele Rocca; Marco Apollonio (Evolutionary Ecology, 2013)

Insulin Receptor β-Subunit Haploinsufficiency Impairs Hippocampal Late-Phase LTP and Recognition Memory - Robert Nisticò; Virve Cavallucci; Sonia Piccinin; Simone Macrì; Marco Pignatelli; Bisan Mehdawy; Fabio Blandini; Giovanni Laviola; Davide Lauro; Nicola B. Mercuri; Marcello D’Amelio (NeuroMolecular Medicine, 2012)

Methylglyoxal alters glucose metabolism and increases AGEs content in C6 glioma cells - Fernanda Hansen; Daniela Fraga de Souza; Simone da Luz Silveira; Ana Lúcia Hoefel; Júlia Bijoldo Fontoura; Ana Carolina Tramontina; Larissa Daniele Bobermin; Marina Concli Leite; Marcos Luiz Santos Perry; Carlos Alberto Gonçalves (Metabolic Brain Disease, 2012)

Heat-related mortality in the Florentine area (Italy) before and after the exceptional 2003 heat wave in Europe: an improved public health response? - Marco Morabito; Francesco Profili; Alfonso Crisci; Paolo Francesconi; Gian Franco Gensini; Simone Orlandini (International Journal of Biometeorology, 2012)

Space coding for sensorimotor transformations can emerge through unsupervised learning - Michele De Filippo De Grazia; Simone Cutini; Matteo Lisi; Marco Zorzi (Cognitive Processing, 2012)

Analysis of the miR-34a locus in 62 patients with familial cutaneous melanoma negative for CDKN2A/CDK4 screening - Angela M. Cozzolino; Lucia Pedace; Marco Castori; Paola De Simone; Nicoletta Preziosi; Isabella Sperduti; Chiara Panetta; Valerio Mogini; Carmelilia De Bernardo; Aldo Morrone; Caterina Catricalà; Paola Grammatico (Familial Cancer, 2012)

Polymorphic NumtS trace human population relationships - Martin Lang; Marco Sazzini; Francesco Maria Calabrese; Domenico Simone; Alessio Boattini; Giovanni Romeo; Donata Luiselli; Marcella Attimonelli; Giuseppe Gasparre (Human Genetics, 2012)

Endothelial colony-forming cells show a mature transcriptional response to shear stress - Anastasia D. Egorova; Marco C. DeRuiter; Hetty C. de Boer; Simone van de Pas; Adriana C. Gittenberger-de Groot; Anton J. van Zonneveld; Robert E. Poelmann; Beerend P. Hierck (In Vitro Cellular & Developmental Biology - Animal, 2012)

Determining optimal clothing ensembles based on weather forecasts, with particular reference to outdoor winter military activities - Marco Morabito; Daniela Z. Pavlinic; Alfonso Crisci; Valerio Capecchi; Simone Orlandini; Igor B. Mekjavic (International Journal of Biometeorology, 2011)

Electrospun Hydroxyapatite-Functionalized PLLA Scaffold: Potential Applications in Sternal Bone Healing - Alberto Rainer; Cristiano Spadaccio; Pietro Sedati; Federico De Marco; Simone Carotti; Mario Lusini; Gianluca Vadalà; Alberto Di Martino; Sergio Morini; Massimo Chello; Elvio Covino; Vincenzo Denaro; et al. (Annals of Biomedical Engineering, 2011)

Multiplatform observation of the surface circulation in the Gulf of Naples (Southern Tyrrhenian Sea) - Marco Uttieri; Daniela Cianelli; Bruno Buongiorno Nardelli; Berardino Buonocore; Pierpaolo Falco; Simone Colella; Enrico Zambianchi (Ocean Dynamics, 2011)

Critical Age Windows for Neurodevelopmental Psychiatric Disorders: Evidence from Animal Models - Eva M. Marco; Simone Macrì; Giovanni Laviola (Neurotoxicity Research, 2011)

Detecting short-term evolution of Etnean scoria cones: a LIDAR-based approach - Alessandro Fornaciai; Boris Behncke; Massimiliano Favalli; Marco Neri; Simone Tarquini; Enzo Boschi (Bulletin of Volcanology, 2010)

An integrated evaluation of thirteen modelling solutions for the generation of hourly values of air relative humidity - Simone Bregaglio; Marcello Donatelli; Roberto Confalonieri; Marco Acutis; Simone Orlandini (Theoretical and Applied Climatology, 2010)

A strong motion network in northern Italy: detection capabilities and first analysis - Paolo Augliera; Ezio D’Alema; Simone Marzorati; Marco Massa (Bulletin of Earthquake Engineering, 2010)

Experimental Validation of Modified Barton’s Model for Rock Fractures - Pooyan Asadollahi; Marco C. A. Invernizzi; Simone Addotto; Fulvio Tonon (Rock Mechanics and Rock Engineering, 2010)

Sensitivity of bistatic scattering to soil moisture and surface roughness of bare soils - Marco Brogioni; Simone Pettinato; Giovanni Macelloni; Simonetta Paloscia; Paolo Pampaloni; Nazzareno Pierdicca; Francesca Ticconi (International Journal of Remote Sensing, 2010)

Modeling ground deformations of Panarea volcano hydrothermal/geothermal system (Aeolian Islands, Italy) from GPS data - Alessandra Esposito; Marco Anzidei; Simone Atzori; Roberto Devoti; Guido Giordano; Grazia Pietrantonio (Bulletin of Volcanology, 2010)

An endocannabinoid system is localized to the hypophysial pars tuberalis of Syrian hamsters and responds to photoperiodic changes - Shinobu Yasuo; Marco Koch; Helmut Schmidt; Simone Ziebell; Joerg Bojunga; Gerd Geisslinger; Horst-Werner Korf (Cell and Tissue Research, 2010)

Cutaneous and gastrointestinal pythiosis in a dog in Brazil - Daniela Isabel Brayer Pereira; Ana Lucia Schild; Marco Aurélio Motta; Rafael Almeida Fighera; Eliza Simone Viégas Sallis; Clairton Marcolongo-Pereira (Veterinary Research Communications, 2010)

Space use, habitat selection and activity patterns of female Sardinian mouflon (Ovis orientalis musimon) during the lambing season - Simone Ciuti; Anna Pipia; Stefano Grignolio; Fabio Ghiandai; Marco Apollonio (European Journal of Wildlife Research, 2009)

Habitat variation at different scales and biotic linkages in lotic systems: consequences for monitorization - Rui Manuel Vitor Cortes; Samantha Jane Hughes; Simone Graça Pinto Varandas; Marco Magalhães; Maria Teresa Ferreira (Aquatic Ecology, 2009)

Predation has a greater impact in less productive environments: variation in roe deer, Capreolus capreolus , population density across Europe - Claudia Melis; Bogumiła Jędrzejewska; Marco Apollonio; Kamil A. Bartoń; Włodzimierz Jędrzejewski; John D.C. Linnell; Ilpo Kojola; Josip Kusak; Miha Adamic; Simone Ciuti; Ivan Delehan; Ihor Dykyy; et al. (Global Ecology and Biogeography, 2009)
Aim We aimed to describe the large‐scale patterns in population density of roe deer Caprelous capreolus in Europe and to determine the factors shaping variation in their abundance. Location Europe. Methods We collated data on roe deer population density from 72 localities spanning 25° latitude and 48° longitude and analysed them in relation to a range of environmental factors: vegetation productivity (approximated by the fraction of photosynthetically active radiation) and forest cover as proxies for food supply, winter severity, summer drought and presence or absence of large predators (wolf, Canis lupus , and Eurasian lynx, Lynx lynx ), hunter harvest and a competitor (red deer, Cervus elaphus ). Results Roe deer abundance increased with the overall productivity of vegetation cover and with lower forest cover (sparser forest cover means that a higher proportion of overall plant productivity is allocated to ground vegetation and thus is available to roe deer). The effect of large predators was relatively weak in highly productive environments and in regions with mild climate, but increased markedly in regions with low vegetation productivity and harsh winters. Other potentially limiting factors (hunting, summer drought and competition with red deer) had no significant impact on roe deer abundance. Main conclusions The analyses revealed the combined effect of bottom‐up and top‐down control on roe deer: on a biogeographical scale, population abundance of roe deer has been shaped by food‐related factors and large predators, with additive effects of the two species of predators. The results have implications for management of roe deer populations in Europe. First, an increase in roe deer abundance can be expected as environmental productivity increases due to climate change. Secondly, recovery plans for large carnivores should take environmental productivity and winter severity into account when predicting their impact on prey.

On the dimensionality of the System Usability Scale: a test of alternative measurement models - Simone Borsci; Stefano Federici; Marco Lauriola (Cognitive Processing, 2009)

Effect of predation risk on grouping pattern and whistling behaviour in a wild mouflonOvis aries population - Anna Pipia; Simone Ciuti; Stefano Grignolio; Sara Luchetti; Rossana Madau; Marco Apollonio (Mammal Research, 2009)

Recent trends in Tuscany (Italy) summer temperature and indices of extremes - Giorgio Bartolini; Marco Morabito; Alfonso Crisci; Daniele Grifoni; Tommaso Torrigiani; Martina Petralli; Giampiero Maracchi; Simone Orlandini (International Journal of Climatology, 2008)
In the past few decades, many studies showed a significant worldwide warming, and consequently, changes in frequency and persistence of extreme high‐temperature events were observed. In order to analyse summer Tuscany (Italy) patterns of climate change during the period 1955–2004, indices of temperature and of extreme events were investigated for evidence of trend and change in inter‐annual variability by using data of 40 weather stations. Least square regression analysis and Theil‐Sen nonparametric regression were applied for evidence of trends. The Mann–Kendall test was applied to each time series to look for statistically significant trends. The results showed a general increase in minimum and maximum temperatures and extreme temperature events. Maximum temperature increase (+0.44 °C/decade) was slightly greater than minimum temperature (+0.38 °C/decade) and consequently, an increase in summer daily temperature range (DTR) was noted (+0.06 °C/decade). Inter‐annual summer climate variability showed an increasing trend in the whole region, especially in regard to extreme event occurrences while a small decreasing trend concerning diurnal temperature range was observed. Copyright © 2008 Royal Meteorological Society

Suramin induces and enhances apoptosis in a model of hyperoxia-induced oligodendrocyte injury - Simone Stark; Alexandra SchÜller; Marco Sifringer; Bettina Erstner; Felix Brehmer; Sven Weber; Rodica Altmann; Michael Obladen; Christoph BÜhrer; Ursula Felderhoff-Mueser (Neurotoxicity Research, 2008)

A biometeorological procedure for weather forecast to assess the optimal outdoor clothing insulation - Marco Morabito; Alfonso Crisci; Lorenzo Cecchi; Pietro Amedeo Modesti; Giampiero Maracchi; Gian Franco Gensini; Simone Orlandini (European Journal of Applied Physiology, 2008)

Ecological sexual segregation in fallow deer (Dama dama): a multispatial and multitemporal approach - Simone Ciuti; Marco Apollonio (Behavioral Ecology and Sociobiology, 2008)

Animal xenodiversity in Italian inland waters: distribution, modes of arrival, and pathways - Francesca Gherardi; Sandro Bertolino; Marco Bodon; Sandra Casellato; Simone Cianfanelli; Marco Ferraguti; Elisabetta Lori; Graziella Mura; Annamaria Nocita; Nicoletta Riccardi; Giampaolo Rossetti; Emilia Rota; et al. (Biological Invasions, 2008)

Influence of meteorological conditions on male flower phenology of Cupressus sempervirens and correlation with pollen production in Florence - Tommaso Torrigiani Malaspina; Lorenzo Cecchi; Marco Morabito; Marzia Onorari; Maria Paola Domeneghetti; Simone Orlandini (Trees, 2007)

Bioconversion of l-phenylalanine into 2-phenylethanol by Kluyveromyces marxianus in grape must cultures - Juliano Garavaglia; Simone Hickmann Flôres; Tania Mara Pizzolato; Maria do Carmo Peralba; Marco Antônio Záchia Ayub (World Journal of Microbiology and Biotechnology, 2007)

Lateglacial and Holocene vegetation history in the Insubrian Southern Alps—New indications from a small-scale site - Simone Hofstetter; Willy Tinner; Verushka Valsecchi; Gabriele Carraro; Marco Conedera (Vegetation History and Archaeobotany, 2006)

Time-lapse tracking of barley androgenesis reveals position-determined cell death within pro-embryos - Simone de F. Maraschin; Marco Vennik; Gerda E. M. Lamers; Herman P. Spaink; Mei Wang (Planta, 2005)

Could the predation risk hypothesis explain large-scale spatial sexual segregation in fallow deer (Dama dama)? - Simone Ciuti; Sara Davini; Siriano Luccarini; Marco Apollonio (Behavioral Ecology and Sociobiology, 2004)

The C 4 biochemical pathway, and the anatomy of lemongrass ( Cymbopogon citratus (DC) Stapf.) cultivated in temperate climates - Cinzia Margherita Bertea; Giorgio Buffa; Wanda Camusso; Simone Bossi; Silvano Scannerini; Massimo Maffei; Manuela Tesio; Giovanni D'Agostino; Marco Mucciarelli (Plant Biosystems, 2003)

Effect of agrometeorological parameters on the phenology of pollen emission and production of olive trees (Olea europea L.) - Marco Moriondo; Simone Orlandini; Paola De Nuntiis; Paolo Mandrioli (Aerobiologia, 2001)

Evidence for a C 4 NADP-ME photosynthetic pathway in Vetiveria zizanioides Stapf - Cinzia M. Bertea; Silvano Scannerini; Wanda Camusso; Simone Bossi; Giorgio Buffa; Massimo Maffei; Giovanni D'Agostino; Marco Mucciarelli (Plant Biosystems, 2001)

Miocene carbonate factories in the syn-rift Sardinia Graben Subbasins (Italy) - Antonietta Cherchi; Marco Murru; Lucia Simone (Facies, 2000)